MiR-4327 targets TP53 to promote cervical cancer cell proliferation - Mei-Lin Chen; Chen-Yang Chu; Feng-Xian Zhang; Li-Pei Zhang; Ying Yang; Bai-Zhao Peng; Chuang-Hai Wu; Xiao-Mei Chen; Yan-Ting You; Bing-Ying Rong; Hiu Yee Kwan; Xiao-Shan Zhao; et al. (Functional & Integrative Genomics, 2026)
Cervical cancer is a leading cause of female malignancy worldwide. While microRNA-4327 (miR-4327) has been implicated as a potential oncogene, its functional role and molecular mechanisms in cervical cancer pathogenesis remain unclear. This study aimed to determine the oncogenic function of miR-4327 and elucidate its downstream regulatory mechanism in cervical cancer pathogenesis. We measured miR-4327 expression in clinical cervical cancer tissues and cell lines using quantitative real-time PCR (qRT-PCR). We then assessed its effects on proliferation, migration, invasion, and cell cycle progression through functional assays including cell counting kit-8 (CCK-8), colony formation, transwell, and flow cytometry. To evaluate tumor growth in vivo, we established a xenograft model in non-obese diabetic (NOD)-severe combined immune-deficient (scid) mice. Using bioinformatic analysis and luciferase reporter assays, we identified TP53 as a direct target of miR-4327 and further validated this regulatory relationship with gain- and loss-of-function experiments. We found that miR-4327 was significantly upregulated in cervical cancer and promoted malignant phenotypes such as proliferation, migration, invasion, and cell cycle progression in vitro. Consistent with this, overexpression of miR-4327 accelerated tumor growth in vivo. Mechanistically, we confirmed TP53 as a direct functional target of miR-4327. Knocking down TP53 phenocopied the oncogenic effects of miR-4327, while restoring TP53 expression rescued the tumor-promoting effects mediated by miR-4327. These findings reveal a novel miR-4327/TP53 regulatory axis and nominate miR-4327 as a potential therapeutic target for intervention.

DBF4B promotes hepatocellular carcinoma progression by regulating CCNA2 and PSMD11 expression - Bing Dong; Pengju Xi; Guangxin Yang; Zhiqi Jiao; Shijie Xu; Lin Han; Zhenming Gao (Molecular Biology Reports, 2026)

Discovery of cytotoxic 1,4-benzodioxane oxyneolignan analogues from Glechoma longituba - Ming-Ming Yuan; Xi Wu; Yang-Bing Zheng; Yu-Lin Feng; Er-Lei Xie (Phytochemistry, 2026)

Phylogenomics of Tanypodinae (Diptera: Chironomidae) redefines relationships in Procladiini and Tanypodini and supports a new tribe - Xiu-Ru Xiao; Yi-Ni Zhang; Hai-Feng Xu; Zhi-Chao Zhang; Yu-Yi Jiang; Yan-Xin Chen; Chen-Hong Li; Bing-Jiao Sun; Fabio Laurindo da Silva; Xiao-Long Lin (Molecular Phylogenetics and Evolution, 2026)

Defining optimal elevation thresholds for mangrove restoration through dynamic tidal simulation: Evidence from morphological and physiological assessment of five species in Zhanjiang Bay, China - Jianjian Huang; Bing Yang; Xin Zhou; Jie Chen; Suqing Liu; Kangyi Deng; Xiuxuan Lin; Yiting Chen; Ruixuan Wang; Yuzhong Zheng; Qinghan Wu; Hui Zhu; et al. (Ecological Engineering, 2026)

Tailoring lattice confinement and conductivity of AlF co-doped Li2TiO3 ion sieves for highly selective lithium electrosorption - Ruini Zou; Yaxuan Wang; Ming Gao; Yijiao Chang; Bing Li; Xiao-yan Li; Lin Lin (Desalination, 2026)

Overlooked effects of common alcohol quenching agents on electron transfer pathway in persulfate activation system - Xuerong Zhou; Lin Zhang; Shiyu Liu; Huchuan Yan; Dengsheng Ma; Qihong Yang; Bing Ding; Cui Lai; Ming Yan; Zizhu Peng (Chemical Engineering Journal, 2026)

Fold-crease induced paper wicking enhancement enabling rapid and high-yield plasma separation - Xianchang Wu; Tonghuan Zhan; Fuzhou Niu; Yange Huang; Heng Wang; Lin Hu; Bing Xu (Analytica Chimica Acta, 2026)

Cefpirome biodegradation by enriched bacterial consortia and isolated strain Bosea sp. MYQ: Novel insights on biodegradation pathway and bacterial interaction patterns - Hongchao Min; Yuyang Wang; Qi Wang; Jiayu Zhang; Lin Lin; Xiaoyan Li; Bing Li (Water Research, 2026)

Temporal sulfur redox reprogramming enables control-oriented intensification of sulfur-based autotrophic denitrification - Kun Zheng; Han-Bing Xiao; Yi-Lu Sun; Zhou-Yang Li; Jing-Zhe Zhang; Han-Lin Wang; Ai-Jie Wang; Xue-Ning Zhang (Water Research, 2026)

Single-site amino acid residue mutation reshapes the characteristics of double bond positions for protostadienol-type triterpenols - Pengyang Lin; Yunpeng Wang; Bing Li; Xuebingting Zhang; Baolian Fan; Ruoshi Huang; Zhongju Ji; Fan Zhang; Jingcai Liang; Lixin Duan (Phytochemistry, 2026)

Generative imaging sonar forward depth estimation for underwater dense scene reconstruction - Zhengyan Zhang; Yanze Lu; Haochen Hu; Bing Wang; Jinghua Lin; Chih-yung Wen (Ocean Engineering, 2026)

Aerobic biodegradation of cefpirome sulfate by Sphingomonas melonis P33: Performance, pathways, and genomic characterization - Yuyang Wang; Hongchao Min; Qi Wang; Tingting Zhang; Yin Li; Jiayu Zhang; Lin Lin; Xiaoyan Li; Bing Li (Journal of Water Process Engineering, 2026)

Leveraging machine learning to optimize hydrothermal technology for antibiotic degradation in antibiotic fermentation residues - Guomin Li; Yuxiang Zhang; Xiaomeng Lin; Bing Wang; Hong Jiang (Journal of Environmental Chemical Engineering, 2026)

Synergistic activation of CO2 and H2 by Ru-Oxygen vacancy pairs over porous CeO2 for efficient formic acid synthesis - Liujun Wang; Shufeng Lin; Junfeng Qian; Yingjun Wang; Zhe Wang; Zhonghua Sun; Zhihui Zhang; Bing Lu; Mingyang He; Zhenzhen Wang (Fuel, 2026)

Cooling-driven polymorphic transition of lipid crystal particles enhancing interfacial rheology and foaming stability in polyunsaturated foams - Jiarong Li; Yuyan Zeng; Qihong Jiang; Bing Li; Lin Li; Xia Zhang (Food Research International, 2026)

Icariin-mediated photodynamic inactivation in antimicrobial packaging films for cherry preservation - Lin Yang; Wentao Zhang; Kaiyuan Su; Zhuoran Guo; Bingzhi Li; Yajie Wang; Zhenqing Guo; Jianlong Wang; Bing Shao (Food Research International, 2026)

Characterization of soybean proteins with various 7S/11S globulin ratios plus machine learning analysis for associating their corresponding physical and chemical functionalities - Yilai Wan; Xinyu Guo; Zhen Liu; Yanhong Lin; Guandi Chen; Yong Zhan; Shengwei Hu; Bing Wang; Chris Blanchard; Zhongkai Zhou; Guohua Zhao (Food Chemistry, 2026)

Corrigendum to “Multiple environmental drivers shape zooplankton community structure in a subtropical-tropical transitional coastal system” [Estuar. Coast Shelf Sci. 340 (2026) 110113] - Zhao-Lang Huang; Shuang Liu; Yan-Guo Wang; Pu-Qing Song; Rou-Xin Sun; Bing-Peng Xing; Su-Min Wang; Jian-Hua Kang; Geng-Ming Lin; Ping Li (Estuarine, Coastal and Shelf Science, 2026)

Multiple environmental drivers shape zooplankton community structure in a subtropical-tropical transitional coastal system - Zhao-Lang Huang; Shuang Liu; Yan-Guo Wang; Pu-Qing Song; Rou-Xin Sun; Bing-Peng Xing; Su-Min Wang; Jian-Hua Kang; Geng-Ming Lin; Ping Li (Estuarine, Coastal and Shelf Science, 2026)

Interlocking architecture-enabled ultrasensitive iontronic pressure sensor based on [BMIM]BF4-functionalized sponge - Xiaohui Guo; Xiaomeng Yao; Bing Hu; Xinran He; Hongtao Tan; Yaqi Yu; Haining Wang; Jiashu Cao; Zhiyuan Liu; Zhangling Duan; Ting-Jung Lin; Yunong Zhao (Chemical Engineering Journal, 2026)

A universal chemical strategy towards the use of diluent for carbonate localized high-concentration electrolytes - Qingjiang Liu; Min Niu; Xingyu Chen; Zongfan Yang; Yan Meng; Yi-Bing Wang; Xian-Xin Feng; Liwei Dong; Lin Mei; Libao Chen; Changsong Dai; Bo Song; et al. (Chemical Engineering Journal, 2026)

Straw pyrolysis reverses forest soil N2O emissions from stimulation to suppression by altering organic C quality and N cycling pathways - Yanfei Dong; Dafeng Hui; Jiashu Zhou; Tida Ge; Junjie Lin; Yu Luo; Yuxue Liu; Bing Yu; Yanjiang Cai; Jason C. White; Yongfu Li (Chemical Engineering Journal, 2026)

Bamboo expansion into broadleaf forests restructures topsoil carbon, nitrogen, phosphorus and potassium pools: A trade-off between carbon sink enhancement and nutrient limitation - Qiudi Wu; Xin Wang; Bing Ma; Hongwei Zhou; Chenyang Huang; Liangjie Wang; Youjin Yan; Ziqiang Liu; Lina Mei; Haibo Hu; Lin Chen; Fengling Gan; et al. (CATENA, 2026)

Pyridoxine and valproic acid co-exposure induces ER-mediated calcium dysregulation and cardiac toxicity in zebrafish - Wei-Hsiang Chen; Po-Yuan Chen; Wen-Yu Chung; Tein-Yu Chiu; Wei-Ling Lin; Chen-Yu Huang; Hui-Hua Chang; Chin-Wei Huang; Bing-Hung Chen; Lin Kang; Tzu-Fun Fu (Chemico-Biological Interactions, 2026)

Voltage-gradient-driven microbial selection and functional gene abundance elucidate aniline and nitrogen degradation in algal-bacterial symbiotic systems - Bing Lin; Qian Zhang; Xiangyu Liu; Hongyu Wang; Bin Ji (Algal Research, 2026)

A parallel electrical impedance tomography system for tissue-resolved imaging of relative stem conductivity dynamics in sunflower under PEG-induced stress - Liu-Deng Zhang; Ao-Wen Wang; Bing-Zhou Chen; Yang Xiang; Yu-Bin Lin; Chang Chen; Huan-Rui Ge; Ke-Lei Xia; Li-Feng Fan; Lan Huang; Zhong-Yi Wang (Biosystems Engineering, 2026)

Mechanical behaviour, deformation mechanisms and support optimization of tunnels in gentle dip layered rock after freeze–thaw cycles - Xiao-Hu Zhang; Jia-Bing Zhang; Jun-Bin Fu; Rong-Huan Du; Han-Lin Wang (Tunnelling and Underground Space Technology, 2026)

Global design and dynamic analysis of floating offshore wind turbines with actively ballasted concrete floater - Guanfeng Lin; Hongyun Zou; Jing Li; Bing Liu; Zili Zhang (Ocean Engineering, 2026)

Evaluation and forecasting of habitat suitability and thermal growth responses in the mud clam Geloina coaxans under climate change - Bing-Xian Liu; Yu-Yang Zhang; Cheng-Rui Yan; Zhan-Wei Zhao; Ning Zhang; Lin-Xuan Ma; Xian-Bo Qiu; Yun-Wei Dong (Marine Environmental Research, 2026)

Deciphering the effects of sulfonamide antibiotics on denitrification from a metagenomic perspective: inhibition of nitrite reduction and succession patterns of functional microorganisms - Qinmao Zhou; Yuyang Wang; Hebin Liang; Jin Huang; Jiayu Zhang; Ke Yu; Lin Lin; Xiaoyan Li; Bing Li (Journal of Hazardous Materials, 2026)

Human-relevant co-exposure to 6:2 Cl-PFESA and PFHxS impairs sperm motility and blood-testis barrier integrity in male mice: Evaluation of combined effects - Lan Shi; Tianrui Gao; Zhipeng Zhu; Fan Yang; Bing Han; Jia Lv; Lin Tao; Yang Gao; Rong Hua; Huan Wu; Yichao Huang; Xiaojin He (Journal of Hazardous Materials, 2026)

WTAP upregulates HK2 expression via m6A methylation to reprogram cell glycolysis and stemness under Cr(VI) exposure - Yunxia Xie; Lin Wang; Ruike Zhang; Wenwen Ran; Bing-Hua Jiang; Xiaoming Xing (Journal of Environmental Sciences, 2026)

Comprehensive investigations reveal high occurrence of tet(X) in blaNDM-positive Acinetobacter spp. from Chinese cattle production systems - Weiwei Wang; Qing Wang; Yanhua Qiu; Guonian Dai; Bing Li; Honglin Lin; Yaxin Zhou; Jiyu Zhang (International Journal of Food Microbiology, 2026)

Outdoor light at night, sleep disorder, and atopic diseases among children and adolescents: a cross-sectional study - Si-Han Wu; Le-Bing Wang; Xiao-Fan Lu; Yang-Yang Li; Joachim Heinrich; Lidia Morawska; Steve Hung Lam Yim; Shao Lin; Bin Jalaludin; Yi-Ran Chen; Xiao-Yi Liu; Yuan-Yuan Fan; et al. (International Journal of Hygiene and Environmental Health, 2026)

Indole biodegradation by Burkholderia contaminans DM32: Process characteristics and the IifR-mediated molecular mechanism - Ying-Si Wang; Jie Wang; Hong-Bing Tao; Hui-Zhong Liu; Bei-Bei Wang; Zhen-Lin Liao; Hong Qi; Qing-Shan Shi; Gang Zhou; Xiao-Bao Xie (International Biodeterioration & Biodegradation, 2026)

Particulate manganese shuttling shapes molybdenum and thallium isotope compositions in surface sediments of the Arabian Sea oxygen minimum zone - Xinming Chen; Niels A.G. M. van Helmond; Bing Xia; Hainan Lu; Zili Zhao; Yu Zhang; Lulu Wang; Yi-Bo Lin; Feifei Zhang; Gert-Jan Reichart; Caroline P. Slomp (Geochimica et Cosmochimica Acta, 2026)

Outdoor light at night exposure and hypertension risk in adults: A longitudinal cohort study from the FLORA project - Shuo Zhang; Xiao-Fan Lu; Muhammad Amjad; Lin-Jing Gong; Na Liu; Hong-Xing Zou; Xiao-Yi Liu; Le-Bing Wang; Yuan-Yuan Fan; Yang-Yang Li; Yi-Ran Chen; Wen-Wen Bao; et al. (Environmental Research, 2026)

Eccentric compressive performance of CFST columns reinforced with annular stiffeners - Ke-Rong Luo; Bing-Lin Lai; Liang Yu; Bu-Hui Li; Gan-Ping Shu (Engineering Structures, 2026)

Dynamic pedestrian light exposure in urban commercial streets: A spatial–temporal–spectral assessment framework - Bing Zhang; Jinghan Qiu; Xianxian Zeng; Zhichao Ma; Shenfei Chen; Zehua Wen; Qi Shi; Yi Lin (Environmental Impact Assessment Review, 2026)

Hierarchical hemispheres microstructure-based iontronic pressure sensor with high sensitivity and wide linear range for gait analysis - Xiaohui Guo; Hao Guo; Bing Hu; Yunjie Peng; Chuanwen Li; Shuting Cao; Junhao Li; Honglin Chen; Zhiyuan Liu; Ming Hou; Ting-Jung Lin; Yunong Zhao; et al. (Chemical Engineering Journal, 2026)

Fluid-like polarization rotation in interpenetrating diffuse phase boundary for dielectric capacitors - Ya Yang; Yawen Cui; Linqiong Xu; Jiarong Lv; Dingheng Lin; Bing Kong; Jinjun Liu; Ning Liu; Zhongbin Pan (Chemical Engineering Journal, 2026)

Pd single atoms anchored on mesoporous C3N5: An exceptional photocatalyst for hydrogen production - Yang Wang; Cun-Feng Fan; Jiao-Yan Li; Xiao-Qin Zheng; Xuan-Yi Liu; Ying Zhou; Jiahui Kou; Hengming Huang; Lin-Bing Sun (Chemical Engineering Journal, 2026)

Multi-stimuli responsive cellulose nanocrystal-based microcapsules with enhanced insecticidal efficacy and environmental safety - Er-min Zhou; Jia-wei Ding; Dao-bing Kang; Yi-lin Tan; Yong-jiang Li; De-qiang Li; Jun Li (Carbohydrate Polymers, 2026)

PFOA promotes PMAIP1–MCL1 apoptotic vulnerability within a BHLHE41-associated macrophage regulatory architecture in atherosclerosis - Hou-liang Chen; Run Wang; Wei-jun Tao; Wang Zhang; Yan-lin Gao; Xiao-bing Cheng (Chemico-Biological Interactions, 2026)

Mixed-carbon co-feeding of formate, acetate, and propionate enables tunable polyhydroxyalkanoate biosynthesis - Zhangdi Peng; Xiaoman He; Chen Deng; Bing Song; Alec Foster; Wenlei Zhu; Richen Lin (Bioresource Technology Reports, 2026)

Toward improved conservation risk assessments in the marine aquarium fish trade: Reply to Biondo and Calado (2026) - Bing Lin; Andrew L. Rhyne; Michael Tlusty; Yiwen Zeng; Bryan To; Robert J. Holmberg; David S. Wilcove (Conservation Biology, 2026)

Tropical legume plants benefit more when grown with interspecific plants than intraspecific under soil phosphorus-limited conditions - Jan Sher; Yun-Bing Zhang; Ghulam Mujtaba Shah; Stephen P. Bonser; Jiao-Lin Zhang (Plant and Soil, 2026)

Electron push-pull engineered Fe-Co dual-atom hollow nanofiber membranes drive super-efficient and sustainable electro-Fenton water purification - Ruiquan Yu; Wutong Chen; Ming Gao; Hao Lin; Chao Yang; Bing Li; Xiao-yan Li; Lin Lin (Water Research, 2026)

Semi-permeable membrane coverage accelerates composting through modulated bacterial succession and organic matter transformation - Fu-Sheng Sun; Chao Wang; Nader Mohamed; Lin Shi; Bo-Hao Yin; Yue-Bing Sun; Guang-Hui Yu (Waste Management, 2026)

Shifting the processing boundary: On-Farm Pulsed Electric Field Intervention (OFPI) for proactive bioburden reduction and functionalization of raw milk - Bing Yan; Lang-Hong Wang; Jin-Lin Cai; Xiao-Jun Zhang; Cai-Yun Wang; Jian Li; Rui Wang; Xin-An Zeng; Jian He (Trends in Food Science & Technology, 2026)

Minutes-long soft X-ray prompt emission from a compact object merger - An Li; Chen-Wei Wang; Niccolò Passaleva; Jie An; Bin-Bin Zhang; Eleonora Troja; Yi-Han Iris Yin; Yuan Liu; Shao-Lin Xiong; Li-Ping Xin; Yi-Xuan Shao; Jun Yang; et al. (Science Bulletin, 2026)

Numerical investigation with viscosity of nonlinear wave forces on a dual-tube submerged floating tunnel - Hong-fei Mao; Kai-lin Chen; Long Han; Zhong-bing Zhou; Yan-li He; Li-min Wang; Jing Xie (Ocean Engineering, 2026)

The maize CMS-C fertility restore gene ZmRf4b encodes a SPL transcription factor that represses ZmMAP1D-mediated co-translational turnover of mitochondrial toxic ATP6C protein - Bing Li; Huaisheng Zhang; Runbo Zhang; Shicheng Feng; Fanli Yang; Congnian Ding; Xuyuan Shen; Keke Shao; Lu Yang; Yanan Lin; Dong Ding; Quancan Hou; et al. (Molecular Plant, 2026)

Brachyspira hyodysenteriae enriched by maternal deoxynivalenol exposure impairs lactation and offspring growth via the bacterial extracellular vesicle-mediated gut-mammary gland axis - Bing Zhang; Senlin Su; Huiping Lin; Mingzhu Zhu; Guanghao Shao; Ronghua Yao; Wutai Guan; Shihai Zhang (Journal of Hazardous Materials, 2026)

Co-contamination of hybrid microplastics and PFOA/GenX alters rhizosphere bacterial–fungal communities and root performance of Eichhornia crassipes - Zu-lin Hua; Zi-wei Chen; Ye-bing Shi; Li Gu (Journal of Hazardous Materials, 2026)

From radical/electron competition to interfacial shielding: How PFOA and its derivatives obstruct electrochemical degradation of microplastics - Yuehua Zhang; Shengping Yang; Yinghui Lin; Xianfang Fan; Mengjuan Yao; Shihua Yin; Yuanji Shi; Linyan Yang; Zhijie Chen; Bing-Jie Ni; Xueming Chen (Journal of Hazardous Materials, 2026)

Formation and exhumation of the Yudai porphyry Cu deposit in the Kalatage region, Eastern Tianshan, NW China - Lin Gong; Huayong Chen; Zhiyong Zhang; Bing Xiao; Lin Wu (Journal of Geochemical Exploration, 2026)

Early microbial succession and matrix destabilization guide long-term preservation of refrigerated kelp - Neng-Pai Shi; Si-Chuang Tu; Bing-Bing Wu; Ru-Meng Xiao; Hai-Bin Pan; Sheng-Nan Lin; Roger Ruan; Xue-Mei Hou; Xiang-Yang Lin (Food Chemistry, 2026)

The role of exogenous electron donors in steering microbial electrosynthesis of multi-carbon fatty acids from carbon dioxide - Chenjia Miao; Xiaoman He; Chen Deng; Bing Song; Alec Foster; Yang Yu; Dekui Shen; Richen Lin (Bioresource Technology, 2026)

Retraction Note: Role of Glibenclamide in Brain Injury After Intracerebral Hemorrhage - Bing Jiang; Lin Li; Qianwei Chen; Yihao Tao; Liming Yang; Bo Zhang; John H. Zhang; Hua Feng; Zhi Chen; Jun Tang; Gang Zhu (Translational Stroke Research, 2026)

True‐triaxial deformation, cracking and strength failure characteristics of chemically corroded flawed sandstone - Bing-Lei Li; Jia-Yao Jiang; Yi Long; Yao Lin; Ming Jiang (Bulletin of Engineering Geology and the Environment, 2026)

Spatiotemporal dual-network assessment of land-use carbon metabolism in Hubei Province: An integrated ENA-SNA framework - Xuehan Lin; Chengliang Liu; Lu Zhang; Bing Kuang; Qingsong He (Applied Geography, 2026)

Chemical constituents from the roots of Illigera celebica - Si-Feng Yang; Lin-Wen Yi; Qiu-Xia Huang; Xing-Meng Luo; Xiao-Bing Su; Lin Hu; Wen-Ting Li; Xiang-Zhong Huang; Meng-Yuan Jiang (Natural Product Research, 2026)

The undescribed alkaloids from Jacobaea cannabifolia (less.) E. Wiebe and their anti-inflammatory activities - Jian-Zhe Li; Juan Pan; Yu Bi; Zhi-Chao Hao; Wei Guan; Hai-Xue Kuang; Qing-Shan Chen; Li-Li Zhang; Xin-Yue Wu; Da-Lin Li; Bing-You Yang; Yan Liu (Natural Product Research, 2026)

Undescribed triterpenoid ellagitannins from Castanopsis calathiformis and their potential antiproliferative and hypoglycemic activity - Ya-feng Wang; Ying-rong Bao; Rui-jie He; Nao Pang; Zhang-bin Liu; Bing-yuan Yang; Gui-qin Li; Yong-lin Huang (Phytochemistry, 2026)

Numerical examination of hydrodynamic forces on a submerged forced rotating circular cylinder under wave action - Hong-Fei Mao; Long Han; Kai-Lin Chen; Jin-Bo Lin; Zheng-Lin Tian; Zhong-Bing Zhou; Hui Yang; Dong-Bin He; Li-Min Wang (Ocean Engineering, 2026)

Is BPA only the tip of the iceberg? Occurrence and risk assessment of 32 bisphenol analogues in landfill leachate - Zhi-Zhong Zhang; Lin-Hui Zhang; Hang Li; Fei Chen; Sakhayana Nikolaevna Danilova; Ming-Han Li; Bing-Feng Liu; Yi-Fan Li; Zi-Feng Zhang (Journal of Hazardous Materials, 2026)

Application of short-wave infrared spectroscopy in sandstone-type uranium deposits: A case study of the Yuejin-II uranium deposit in the Qaidam Basin, China - Wen-Yi Wu; Ming-Sen Fan; Pei Ni; Jun-Yi Pan; Yi-Han Lin; Yan Zhou; Chen Zhang; Ruo-Yu Shi; Xue-Feng Gao; Duo Wang; Bin Guo; Xiao-Qin Xu; et al. (Journal of Geochemical Exploration, 2026)

Life cycle assessment of regionally functionally-zoned intensive pig farming systems: Carbon footprint analysis and mitigation strategies for sustainable production - Bing Wu; Zhiqi Wen; Zhepu Ruan; Xiaoxuan Lin; Yongjie Li; Zhuobiao Ni; Gengyuan Cai; Rongliang Qiu (Journal of Environmental Management, 2026)

The potential mechanism of nitrous oxide accumulation in wastewater treatment plants under different load conditions - Wen-Jiao Sang; Bing Gong; Chong-Yang Xing; Bei-Bei Chen; Zhi-Lin Zhang; Hui-Min Fu; Ya-Song Chen; Wan Sun; Meng-Meng Liu; Shun-Li Cheng; Yu-Lin Wang; Qiang Wang; et al. (International Biodeterioration & Biodegradation, 2026)

Short anti-aging peptides from edible microalgae using a multi-targets virtual screening strategy combined with Caenorhabditis elegans model - Yan-yan Yuan; Xin Li; Ming-hui Han; Xue An; Yong-Qiang Lin; Hong-Bing Liu (Food Research International, 2026)

Influence of salt ionic strength on the freeze-thaw stability of sodium caseinate-modified solid lipid particle-stabilized pickering emulsions: regulation of lipid crystallization behavior and interfacial rheology - Qihong Jiang; Jiarong Li; Xin Luo; Lin Li; Bing Li; Xia Zhang (Food Chemistry, 2026)

Mechanisms of core browning in ‘Yali’ pears during shelf life: insights from integrated physiological and transcriptomic analyses after prolonged cold storage - Jingling Dai; Hongyan Zhang; Ying Li; Xiaohui Lin; Bing Deng; Liya Liang (Food Bioscience, 2026)

Ultrasound-driven structural and functional modifications of grape seed protein revealed by power- and duration-dependent experiments - Ying-Yang Liu; Da-Rui Tang; Shi-Ling Wang; Wei-Wei Li; Jun-Wei Xu; Lian-Bing Lin; Yu-Hang Jiang; Qi-Lin Zhang (Food Hydrocolloids, 2026)

The mediation and interaction roles of hypertension on the pathway between occupational noise and cardiac arrhythmia: insights from a large cross-sectional occupational population of 229,686 workers - Zhiqiang Li; Wenjing Wu; Xinyue Li; Bing Xia; Shao Lin; Xiaowen Wang; Xudan Chen; Yanji Qu; Ziqiang Lin; Jinghua Li; Guanghui Dong; Yongshun Huang; et al. (Environmental Pollution, 2026)

Constructing compatible LLZTO/PEO interfaces with fast Li+ transport channels for high-performance composite polymer electrolytes - Yimei Jin; Yiting Lin; Zekai Zhang; Bing Li; Ru Wang; Cheng Lian; Xia Han; Honglai Liu; Haiping Su; Jingkun Li (Chemical Engineering Journal, 2026)

The antimicrobial arsenal of endophytes in Lilium pumilum: active components of Fusarium tricinctum and antifungal mechanisms - Yong-Jiao Niu; Lin-Bo Liu; Zhong-Duo Yang; Cui-Juan Xu; Tian-Kun Zhao; Lei-Lei Chen; Qian-Qian Wang; Bing Sun; Sahyun Kim (Archives of Microbiology, 2026)

WNT4 reprograms dental pulp stem cells to resist PANoptosis and rebuild neurogenic potential for facial nerve injury repair - Wanqiu Xu; Hualei Xi; Song Lin; Lihong Yao; Jian Sun; Bing Xue; Guiyan Piao; Ying Liu; Wenjing Sun; Xiumei Wang (Inflammation Research, 2026)

Seismic dynamic response and sensitivity analysis of high-speed railway catenary systems under multidirectional excitations and traveling wave effects - Jin Chen; Qing-Bing Wan; Hao-Lin Xin; Bo Fu; Deliang Ma (Bulletin of Earthquake Engineering, 2026)

Non-equilibrium criticality-enhanced quantum sensing with superconducting qubits - Hao Li; Yaoling Yang; Yun-Hao Shi; Zheng-An Wang; Ziting Wang; Jintao Li; Yipeng Zhang; Kui Zhao; Yueshan Xu; Cheng-Lin Deng; Yu Liu; Wei-Guo Ma; et al. (Science Bulletin, 2026)

Effects of inoculum sources from different depths and oxygen concentration on bioleaching and microbial community assembly in mine waste dump - Zi Han Lin; Bing Zhou; Chen Sheng Zhang; Xuan Qi Zhang; Yan Bo Chen; Min Liang Fei; Xiao Fei Wei; Zhang Zheng Cai; Tian Shou Hu; Jie Hu; Han Ke (Journal of Hazardous Materials, 2026)

Liquid-phase hydrogenation of benzaldehyde to benzyl alcohol over NiCoAl‑R catalysts: Synergistic metal–metal oxide interfaces for enhanced catalytic performance - Lingmei Yang; An Wei; Ru kuan Liu; Guo ling Zhang; Bing Han; Baining Lin; Lianhua Li (Journal of Environmental Chemical Engineering, 2026)

Clay minerals reduced antibiotic resistance gene dissemination in the plant rhizosphere through inhibiting horizontal gene transfer and reshaping microbial community structure - Yuxin Qin; Yuqiu Luo; Haihui Fu; Haopeng Pang; Xiaoyu Long; Qian Zhang; Hai Lin; Bing Li (Journal of Environmental Chemical Engineering, 2026)

Copper nanoparticles enhance azo dye decolorization by Shewanella putrefaciens CN32: enhanced effect and underlying mechanisms - Bai-Hang Zhao; Rui-Xuan Liu; Bing-Lin Zhang; Xin-Yu Zhang; Xu-Ming Liu (Journal of Environmental Sciences, 2026)

Sustainable stabilisation of collapsible loess with quicklime-recycled GGBS mixtures - Bao-Lin Dai; Chao Zhou; Qing-Yi Mu; Jian-Bing Peng (Geomechanics for Energy and the Environment, 2026)

Rosa laevigata Michx. as a fermentation adjunct modulates microbial succession, metabolic profiles, and sensory quality of Traditional Hakka Huangjiu during brewing - Lin Cheng; Xin Feng; Yujing Wang; Yifang Chen; Bing Li; Feiliang Zhong; Xuegang Luo (Food Bioscience, 2026)

Two purified polysaccharides from Anemarrhena asphodeloides alleviate type 2 diabetes in mice through remodeling gut microbiota and modulating glycolipid metabolism - Juncheng Chen; Li Zhu; Liqian Chen; Guihong Fang; Baolian Li; Jing Zhou; Meijuan Lan; Lin Li; Bing Li (Food Bioscience, 2026)

Chitosan oligosaccharides activate PPARγ to alleviate aflatoxin B1-induced testicular inflammation and barrier damage - Pei-Yu Dong; Zhuang-Bing Li; Sheng-Lin Liang; Xi-Feng Zhang; Yan-Ni Feng; Wei You (Food Bioscience, 2026)

Boron species with negative Poisson's ratio alleviating expansion-induced degradation in silicon-based anode for enhanced cycling stability - Yihao Fan; Junzhe Zhang; Lei Ma; Zhi Chen; Minglu Li; Shunan Lin; Danfeng Zhang; Peng Li; Liyong Wang; Yan-Bing He; Huiqi Wang (Chemical Engineering Journal, 2026)

A chemical softening–microfiltration platform for simultaneous hardness control and phosphorus fertilizer recovery from agricultural saline-alkaline water - Wuyi Liu; Weifeng Chen; Xun Zhu; Chi Zhang; Enyu Zhang; Viola Somogyi; Zhijun Zhou; Danjun Zheng; Zhikan Yao; Bing Tian; Lin Zhang (Chemical Engineering Journal, 2026)

Hydrogen-bonding guided isoreticular supramolecular frameworks with self-recovery for efficient natural gas purification - Zhou-Rui Yan; Xiao-Han Li; Shi-Kai Zheng; Ze-Jiu Diao; Fan Li; Jin-Peng Liu; Guoliang Liu; Lin-Bing Sun (Chemical Engineering Journal, 2026)

Engineering a siderophore-macrolide conjugate via Trojan horse strategy for targeting Pseudomonas aeruginosa and related resistant pathogens - Chun-Yan Zhang; Wei-Min Chen; Guo-Bin Yang; Jing-Hua Wei; Zu-Ju Liang; Xi-Bing Hu; Ping Lan; Jing Lin; Jun Liu (Chemical Engineering Journal, 2026)

Electric field drives assimilation enhancement and deterministic assembly in algae-bacteria symbiosis for enhanced aniline biodegradation - Bing Lin; Qian Zhang; Xiangyu Liu; Nanping Wu; Hongyu Wang; Bin Ji (Bioresource Technology, 2026)

Acupuncture improves neurological function in ICH rats via suppression of WNK-SPAK-NKCC1 signaling activation - Bai-Wen Zhang; Lei Zheng; Bing-Lin Kuang; Jia Zheng; Xue-Ping Yu; Xiao-Hong Dai; Wei Zou (Journal of Molecular Histology, 2026)

The specificity and selectivity of aptamer depends on the binding epitope: insights from aptamer Hislxl-2a - Xiaoli Liu; Xiangru Zhang; Xinhui Zhao; Mingyan Wu; Xinyue Li; Hengyi Lin; Mingxin Zhang; Zhenhao Long; Tao Bing (Analytica Chimica Acta, 2026)

Microbial adaptation and synergistic networks in simultaneous anammox-denitrification using food waste as a low-cost carbon source for complete nitrogen removal - Xiangling Wu; Chunxiao Wang; Zuohong Chen; Songping Deng; Bing Li; Xiao-yan Li; Lin Lin (Resources, Conservation and Recycling, 2026)

RDX as the sole nitrogen source affects the nitrogen metabolism in Rhodococcus sp. LMD - Songwei Hu; Mengdi Li; Yaya Huang; Yanchao Li; Songrui Zhang; Wenjia Li; Bing Lin; Jiaxin Zhengchen; Qi Lv; Xuanrui Shen; Huibin Zou; Fengbing Liang; et al. (Journal of Hazardous Materials, 2026)

Improving the yield of Monacolin K in solid-state fermentation of Monascus purpureus H164 based on fermentation optimization strategy - Sixu Lin; Xue Yang; Qinghua Yu; Junyao Wang; Bing Li; Yuning Zhang; Xuerui Yan (Fungal Biology, 2026)

A novel direct solid pyrolysis coupled microplasma optical emission spectrometry for rapid determination of dithiocarbamates in food samples - Bing Qian; Xuan Zhu; Changhuang Lin; Qiong Wu; Meng Zhang; Bei Li; Bingjun Han (Food Chemistry, 2026)

Innovative silk protein peptide-modified soy protein isolate-xanthan gum films for food packaging - Meixia Zheng; Shaojie Zhong; Cheng Lin; Jianfu Chen; Yangyang Liu; Kok Bing Tan; Yujing Zhu (Food Chemistry, 2026)

Synergistic LiNO3/FEC modification to nonflammable LiOTf-TMP electrolyte for durable lithium metal batteries - Chun-Jern Pan; Chia-Ho Liu; Shih-Che Lin; Chun-I Lee; Chia-Hsin Wang; Bing-Joe Hwang (Chemical Engineering Journal, 2026)

The light side of the microbiome in trauma: Mechanism and applications - Han-Yue Luo; Lei-Ming Cao; Kan Zhou; Yi-Fu Yu; Yao Xiao; Guang-Rui Wang; Bing Liu; Qiu-Ji Wu; Xiao-Long Wang; Zhi-Yong Song; Lin-Lin Bu (Chemical Engineering Journal, 2026)

A high-performance bimodal sub-nanoporous polyelectrolyte complex membrane for organic solvent nanofiltration constructed by MOF-reinforced nano-unit - Hui-Qian Huo; Bing-Xin Gu; Jin-Lin Wang; Jia-Chen Zhang; Kai Zhang; Ming-Jie Yin; Yan-Li Ji; Quan-Fu An (Chemical Engineering Journal, 2026)

Dual-valence Ce substitution in SmFeO3 constructing vacancy-rich structure for high-response VOCs gas-sensing material - Yuan Zhuang; Le-Zhong Li; Xing Zhang; Junjie Li; Lin-Jie Guo; Bing-jie Wang; Feng Xu; Yao Xiao; Jian Tang; Yi-Lei Li (Chemical Engineering Journal, 2026)

Tailoring pore architecture in hard carbons: Clarifying the distinct sodium storage roles of closed pores and ultra-micropores - Wei-wei Kang; Hai-tao Zeng; Guang-xu Huang; Jian-bo Jia; Qiang Li; Han Hu; Bing Xu; Wei-jie Guo; Rui Hao; Bao-lin Xing; Chuan-xiang Zhang (Chemical Engineering Journal, 2026)

Corrigendum to “Pulsatilla saponin D inhibited the growth of osteosarcoma by regulating the JNK/ATF3 signaling pathway” [Chem.-Biol. Interact. 410 (2025) 111420] - Kaipeng Jin; Chengchun Shen; Wei Yu; Jinti Lin; Jian Zhu; Huimin Tao; Bing Liu (Chemico-Biological Interactions, 2026)

Nighttime cloud cover from multi-site observations and its relationships with ground- and satellite-based measurements - Nofel Lagrosas; Sheng-Hsiang Wang; Bing-Qian Wu; Neng-Huei Lin; Yotsumi Yoshii; Masanori Yabuki; Moe Ishii; Kein Itou; Tatsuo Shiina; Hitoshi Irie; Hiroaki Kuze; Atsushi Shimizu (Atmospheric Research, 2026)

Wnt signaling dysregulation drives Stargardt disease pathogenesis - Xiao Zhang; Zhuo-Lin Liu; Xiao Lin; Shu-Ning Sun; Dandan Shi; Lu Tian; Yang Li; Zi-Bing Jin (Science China Life Sciences, 2026)

Dopamine modulation of aggression - Bing Dai; Dayu Lin (Psychopharmacology, 2026)
Rationale Aggression is an innate social behavior prevalent across animal species. However, in modern human society, inter-personal aggression is considered disruptive and detrimental to both families and communities. Clinically, antipsychotics, which primarily target dopamine (DA) receptors, have been widely used to suppress hyper-aggression. However, the mechanisms underlying the effect of the antipsychotics remain incompletely understood. Objectives We reviewed key steps in brain DA synthesis and summarized genetic and pharmacological evidence supporting the role of the mesolimbic DA system in aggression. Next, we discussed recent circuit studies that elucidate the DA action in modulating aggression-related brain regions. These lines of evidence collectively suggest that DA acts on different brain regions to facilitate aggression and self-learning, and signals the valence of the fighting experience.

Mechanical and microstructural responses of yellow sandstone with prefabricated fissures to tailings water immersion - Wenyu Dong; Fei Lin; Zhiguo Xia; Jun Hu; Hailong Wang; Bing Chen; Tianqi Jiang (Bulletin of Engineering Geology and the Environment, 2026)

Young adulthood adiposity in relation to all-cause and cause-specific mortality: a prospective study of 0.5 million Chinese adults - Lei Fan; Andri Iona; Shixian Feng; Gang Zhou; Huarong Sun; Pang Yao; Canqing Yu; Yiping Chen; Dianjianyi Sun; Pei Pei; Ling Yang; Mingshu Yan; et al. (Science Bulletin, 2026)

Hydrogeochemical properties and health risks of high-fluoride groundwater in southern Jiaolai Basin - Menghan Tan; Zongjun Gao; Jiutan Liu; Bing Jiang; Linlin Lin; Qiang Li; Yiru Niu (Process Safety and Environmental Protection, 2026)

Geochemistry of tourmaline in granitic rocks from the Zharigana and Caolong areas, Northern Tibet: Implications for the identification of lithium-mineralizing plutons - Ling Ma; Jin-Sheng Zhou; Qiang Wang; Lin Ma; Jin-Heng Liu; Wu-Fu Li; Bing-Zhang Wang; Chun-Tao Wang; Jian-Dong Liu; Xin-Yuan Zhang; Mao-Rui Liu; Zhi-Wei Yu; et al. (Lithos, 2026)

Optimizing VOC destruction via reaction-thermal coupling in porous media oxidizers: A case study on ethane oxidation - Bing Zhou; Yujia Wu; Beilong Lin; Fan Yao; Hao Zhang; Shengyong Lu (Journal of Environmental Chemical Engineering, 2026)

Surface reflectance in homogeneous regions follows a Gamma distribution: principles, validation and applications - Yuanhong Liao; Yuqi Bai; Yanping You; Jie Wang; Shuang Chen; Ming Lin; Jin Chen; Jing M. Chen; Bing Xu; Peng Gong (ISPRS Journal of Photogrammetry and Remote Sensing, 2026)

Interface synergy in aqueous Pickering foams: Effects of food gums and sodium Caseinate on the interfacial properties of fat crystal - Qihong Jiang; Shiqi He; Yuan Liu; Jiarong Li; Lin Li; Bing Li; Xia Zhang (Food Research International, 2026)

Interfacial assembly behavior of temperature-controlled surface-activated fat crystals at oil/water interfaces: characterization, interfacial dynamics, and emulsion-stabilizing capabilities - Yuting Song; Xia Zhang; Shuang Su; Ying Song; Bing Li; Lin Li (Food Hydrocolloids, 2026)

Round-ended concrete-filled FRP tubes subjected to monotonic axial compression: Experimental study and design-oriented model - Bing Zhang; Yunhao Yan; Guan Lin; Yutao Peng; Chong Zhou (Engineering Structures, 2026)

Green flocculant of Aspergillus niger fungus cultured from food waste hydrolysate for enhanced sludge dewatering - Yingfei Sun; Yijiao Chang; Yuxuan Wang; Zuohong Chen; Zhu Liang; Jiao Chen; Bing Li; Yongcheng Wang; Xiao-yan Li; Lin Lin (Bioresource Technology, 2026)

Identification and validation of a QTL, QSNS.caas-3D.1, for spikelet number per spike in wheat - Xuezhong Liang; Junli Yang; Ze Liu; Fuping Zhang; Haiming Han; Shenghui Zhou; Jinpeng Zhang; Bing Han; Yida Lin; Hong-Qing Ling; Li Zheng; Junbo Yang; et al. (Theoretical and Applied Genetics, 2026)

Efficacy and Safety of Probiotic Supplementation for Neonatal Jaundice: A Systematic Review and Meta-analysis - Hui-Min Huang; Bing-Hua Lin; Yi-No Kang; Nai Ming Lai; Kee-Hsin Chen (Probiotics and Antimicrobial Proteins, 2026)

Observational characteristics of cloud-radiation-precipitation during 2019 drought period in Yunnan of Southwest China - Yuwei Tan; Xinqiang Zhou; Bing Chen; Jiandong Li; Guo Lin; Xiaohong Liu; Tao Luo (Climate Dynamics, 2026)

From SPP to RTK: promoting the satellite navigation potential of acoustically excited antenna - Shangyang Wang; Yifan Fu; Rui Hu; Du Li; Bing Xu; Ruofan Liu; Yinuo Song; Junru Li; Bin Fang; Wenkui Lin; Zhongming Zeng; Xiangwei Zhu (GPS Solutions, 2026)

Agroforestry balances plant–soil–microbe–enzyme interactions and improves its connectivity and homeostasis: Evidence from C:N:P stoichiometric networks - Qi-Wen Xu; Meng-Die Feng; Tian-Yang Li; Lin Xiong; Bo-Yu Ren; Yan-Zheng He; Bing-Hui He (Agriculture, Ecosystems & Environment, 2026)

Decumbic acid derivatives from soil fungus Lasiodiplodia sp. BG1083 - Hong-Qiao Dai; Xiao-Bing Su; En-Tao Zhou; Wen-Ting Li; Shuang-Shuang Chen; Hui-Yang Cao; Lin Hu; Meng-Yuan Jiang (Natural Product Research, 2026)

QSAR-enhanced machine learning for mechanistic insights and real-time prediction of DBPs in drinking water distribution systems - Dai-Xu Zhang; Tian-Yang Zhang; Zhen-Ning Luo; Zhu Peng; Zheng-Xiong Zheng; Yun-Qiao Zeng; Qi Fu; Ling Hu; Bing Geng; Chao-Yi Tong; Yu-Lin Tang; Bin Xu (Water Research, 2026)

Combined exposure of enrofloxacin and disinfection byproducts under environmentally relevant concentrations enhances antibiotic resistance risks in livestock wastewater - Jin Huang; Jingjia Zhang; Uli Klümper; Jianhua Guo; Thomas U. Berendonk; Ryo Honda; Hebin Liang; Lin Lin; Xiaoyan Li; Bing Li (Water Research, 2026)

Lessons learned from shield machine penetrating beneath the existing diaphragm walls using artificial ground freezing (AGF) - Yu-Yong Jiao; Jian-Feng Qi; Xue-Feng Yan; Lin-Chong Huang; Qian-Bing Zhang (Tunnelling and Underground Space Technology, 2026)

A novel mechanism of uranium mineralization: The role of zircon adsorption at the Qigequan deposit, Qaidam Basin, NW China - Yi-Han Lin; Ming-Sen Fan; Pei Ni; Jun-Yi Pan; Zhe Chi; Zhi-Lin Cheng; Wen-Yi Wu; Chen Zhang; Bing-De Qi; Xue-Bin Wei (Sedimentary Geology, 2026)

Impact of sulfonamides on microbial community and antibiotic resistome profiles in anaerobic digestion of swine wastewater - Qinmao Zhou; Hebin Liang; Jin Huang; Uli Klümper; Peiju Fang; Zehui Yu; Yuyang Wang; Thomas U. Berendonk; Lin Lin; Xiaoyan Li; Bing Li (Journal of Hazardous Materials, 2026)

Continuous-flow CO2 hydrogenation to formic acid over Pd-based catalysts on amine-functionalized Zr-SBA-15 - Zhenzhen Wang; Shufeng Lin; Liujun Wang; Zhe Wang; Bing Lu; Zhonghua Sun; Zhihui Zhang; Mingyang He; Junfeng Qian (Fuel, 2026)

Novel FRP-UHPC-steel double-skin tubular columns subjected to horizontal impact loading: Experimental study and FE modelling - Yuexin Jiang; Zechao Lu; Bing Zhang; Boyi Zhang; Shuhong Lin; Songjiang Guo (Engineering Structures, 2026)

Preferential N2-transport thin-film composite membrane for energy-efficient CO2 capture - Jin-Lin Wang; Cheng-Gang Jin; Hui-Qian Huo; Bing-Xin Gu; Yue Li; Wen-Hai Zhang; Ming-Jie Yin; Quan-Fu An (Chemical Engineering Journal, 2026)

Regulated deficit irrigation strategy for greenhouse melons based on water status classification model and crop coefficient–reference evapotranspiration approach - Shih-Lun Fang; Bing-Yun Tsai; Sheng-Chih Chang; Yi-Lung Chang; Min-Hwi Yao; Ming-Kun Chi; Wen-Lin Wang; Bo-Jein Kuo (Irrigation Science, 2026)

Research progress on quorum-quenching strategies for membrane biofouling control - Hongwei Wu; Kuo Yang; Yifan Gao; Rui Xu; Yuzhang Feng; Yinning Wang; Huimin Lin; Siqi Hu; Gege Tian; Jiaying Li; Pingfeng Yu; Bing Zhang (ENGINEERING Environment, 2026)

ASSR-mediated sludge yield reduction couples deterministic enrichment of Nitrospira with metabolic resource partitioning - Huanzhong Deng; Junling Yang; Ruohong Li; Kewen Li; Hui Lu; Bing Lin; Xingquan Xu; Jiajun Liao; Congrong Ye; Jie Deng; Bo Wu; Lianpeng Sun (Water Research, 2026)

Histone H3.3 phosphorylation facilitates H3K9me3-heterochromatin formation during retrotransposon silencing and X-chromosome inactivation via H3.3K27me3–CBX7–KAP1 axis - Jun Chen; Jiyu Chen; Zhouliang Yu; Liwei Zhang; Yanchao Liu; Xuan Ouyang; Juan Yu; Menghan Wang; Shangqiang Xie; Ming Wang; Tiantian Zhang; Zhaohui Jin; et al. (Science Bulletin, 2026)

Temporal variation of water content in the lithospheric mantle beneath the central North China Craton: New evidence from mantle xenocrystic pyroxenes - Yao Xu; Hong-Fu Zhang; A-Bing Lin; Chao Zhang (Lithos, 2026)

Energy-saving and fire/water-resistant recyclable aerogel coatings for thermal-insulating polyurethane foam - Cong-Mei Lin; Xue-Lian Chen; Fu-Rong Zeng; Li-Xiao Hao; Yu-Shi Wen; Bing-Ru Zhang; Bo-Wen Liu; Lin Zhang; Hai-Bo Zhao (Chemical Engineering Journal, 2026)

Tunable synthesis of tailored high-energy-density fuels from coal-based fluorene - Bing-Wei Chen; Hua-Jun Zhai; Yan-Cheng Hu; Yan-Hong Tan; Jia Li; Zhilian Wu; Lin Shao; Jing-Pei Cao (Chemical Engineering Journal, 2026)

Submerge-emerge alternation regulates per(poly)fluoroalkyl substance fate in emergent plants: Insights from growth, physiology, and metabolomics - Ye-bing Shi; Zu-lin Hua; Zi-wei Chen; Xiao-qing Li; Li Gu (Aquatic Toxicology, 2026)

Development of a Sensitive Real‐Time PCR Method for Detection of Carp Oedema Virus - Huilin He; Ruixue Feng; Siyi Guo; Bing Han; Jinshan Huang; Xu Lin; Jiyuan Yin; Defeng Zhang; Min Liu; Wen Shi (Journal of Fish Diseases, 2026)
Carp oedema virus disease (CEVD), caused by the carp oedema virus (CEV), results in significant economic losses to the common carp and koi aquaculture industry. The CEVD symptoms resemble those of koi herpesvirus (KHV) and include lethargy, swollen gills, sunken eyes, and skin haemorrhages. Consequently, the development of efficient detection methods is imperative for the prevention and diagnosis of CEVD. In this study, we developed a quantitative real‐time PCR assay for the sensitive detection of CEV infection. Specific primers were designed based on a highly conserved region within the CEV p4a gene. The assay exhibited a sensitivity that was 100‐fold greater than that of the conventional PCR technique, with high specificity, and no observed cross‐reactivity with infectious haematopoietic necrosis virus (IHNV), infectious pancreatic necrosis virus (IPNV), spring viremia of carp virus (SVCV), salmonid alphavirus (SAV), or KHV. Inter‐ and intra‐assay experiments also confirmed the method's high repeatability. In a clinical setting, it showed higher sensitivity compared to the diagnostic methods for CEVD developed by the Center for Environment, Fisheries and Aquaculture Science (CEFAS), while also significantly reducing detection costs. Consequently, the established assay could provide robust technical support for the clinical diagnosis and epidemiological investigation of CEVD.

Extent of threats to marine fish from the online aquarium trade in the United States - Bing Lin; Yiwen Zeng; Bryan To; Robert J. Holmberg; Andrew L. Rhyne; Michael Tlusty; David S. Wilcove (Conservation Biology, 2026)
The global marine aquarium hobby is a multibillion‐dollar industry, largely driven by demand from the United States. Much of this trade occurs online. We web scraped 4 major US‐based e‐commerce platforms selling marine aquarium fish to determine the retail price and source (wild capture, aquaculture, or both) of 13 families of ray‐finned marine fish ( Actinopterygii ). We supplemented this with ecological and economic trait data from FishBase and the International Union for Conservation of Nature (IUCN). Across all platforms and 13 popular fish taxonomic families, we found 734 unique species for sale, 89.2% (655 species) of which were sourced exclusively from the wild. A total of 45 species were of conservation concern (20 threatened species and 25 additional species with decreasing population trends), 38 of which were sourced solely from the wild. Retail price was significantly correlated with source, body length, minimum occupied depth, and schooling behavior. A further 100 species for sale were not listed as being in the aquarium trade in FishBase or by the IUCN, indicating incomplete information on this fishery in 2 important databases. For 58 species (encompassing 71 variants) with both wild‐caught and captive‐bred individuals for sale, aquaculture fish were a mean 28.1% (95% confidence interval 15.3) cheaper than their wild‐caught counterparts.

Sustainable production of high-purity crystalline FePO4 from sludge for battery electrodes - Xuan Wang; Yijiao Chang; Zhu Liang; Anjie Li; Yiru Wu; Bohua Wen; Bing Li; Feiyun Sun; Xiao-yan Li; Bruce E. Logan; Lin Lin (Water Research, 2026)

Hop bitter acids from the pistillate flower of Humulus lupulus L. and their anti-inflammatory and anti-dengue virus activities - Biao Sun; Yun-Lin Ao; Xia Cao; Jia-Bing Zhang; Xia Zhang; Dong-Hao Lu; Man Lin; Jun-Shan Liu; Xiao-Qi Zhang (Phytochemistry, 2026)

Numerical study on the influence of submerged breakwater slope on wave-current propagation behaviors - Hong-Fei Mao; Long Han; Kai-Lin Chen; Ying-Chao Ma; Jin-Bo Lin; Zheng-Lin Tian; Zhong-Bing Zhou; Ran Ji; Yan-Li He; Li-Min Wang (Ocean Engineering, 2026)

Tension characteristics of symmetrically inclined mooring lines for a submerged floating tunnel under wave action - Weidong Chen; Haobo Jiang; Bing Ren; Gancheng Zhu; Pengzhi Lin (Ocean Engineering, 2026)

Rice SINA E3 ligases dichotomously control ERECTA1 ubiquitination and stability to regulate panicle morphogenesis and grain yield - Zi-Qi Lu; Tao Guo; Ying-Jie Cao; Jun-Xiang Shan; Wang-Wei Ye; Nai-Qian Dong; Yi Kan; Yi-Bing Yang; Shuang-Qin Guo; Jie-Jie Lei; Xiao-Rui Mu; Ji-Fu Zhou; et al. (Molecular Plant, 2026)

Recent advances in formaldehyde adsorption by metal–organic frameworks for indoor air filtration - Andrea Hoe; Hanjie Lin; Bing Guo; Yeqing Wang; Weiwei Zheng; Jianshun Zhang (Journal of Hazardous Materials, 2026)

Stage-specific neurotoxicity of lead in zebrafish: Metabolic disruption in embryos and ferroptosis in larvae - Jian Liu; Guizhen Yan; Hengyu Gui; Kang Luo; Hongwei Liang; Ai Guan; Weizhen Liu; Hongyu Zhou; Zhang Lin; Bing Yan (Journal of Hazardous Materials, 2026)

Low-cholesterol egg yolk lipids alleviated the development of atherosclerosis in ApoE −/− mice by regulating bile acid metabolism and gut microbiota - Le Cheng; Ming Zhang; Fang Wu; Jianguo Dong; Yifei Wang; Lin Dong; Yumeng Ma; Chenyan Zheng; Zihan Wang; Yixuan Li; Ran Wang; Fazheng Ren; et al. (Food Research International, 2026)

Soil aggregates, carbon and nitrogen content, and water retention across land uses in the Reshui River Catchment - Jing Zheng; Jianxiong Zhang; Bing Ren; Hongyu Lin; Ziyang Li; Feng Gu; Bo Zhu; Barthelemy Harerimana; Minghua Zhou (Ecological Engineering, 2026)

Dual aggregation steering in bulk-heterojunction via solvent engineering toward efficient and stable binary organic solar cells - Yijing Lin; Bing Zheng; Xingting Liu; Huizhen Xu; Liyang Yu; Ruipeng Li; Xin Song; Weiguo Zhu (Chemical Engineering Journal, 2026)

Alternating current or direct current: Which is better for electrochemical membrane separation water purification system? - Zhen Qiu; Jiujing Xu; Cheng Chen; Wei Yu; Bisheng Li; Liguo Shen; Bing Yu; Huajun Feng; Hongjun Lin (Chemical Engineering Journal, 2026)

Enhanced fermentation for lactic acid production from food waste via hydrothermal pretreatment: performance evaluation and metagenomic analysis - Zuohong Chen; Jiayu Zhang; Lin Lin; Yingfei Sun; Xiao-yan Li; Bing Li (Bioresource Technology, 2026)

Statistical characteristics of storm cells and centroid-based probability nowcasts by tracking error - Kao-Shen Chung; Tsai-Jung Lee; Li-Pen Wang; Bing-Zhang Wang; Chieh-Ying Ke; Yi-Hao Tsou; Shin-Gan Chen; Ping-Yu Lin; Treng-Shi Huang (Atmospheric Research, 2026)

Spatial variation of rainfall for landslide early warning: an examination from Majiajing watershed in Yunnan, China - Jing-Kun Bao; Kun Wang; Chuan-Bing Zhu; Ze Li; Ze-Min Xu; Yun-Fei Zhang; Lin Tian; Yang Yang; Jun-Yao Luo; Tai-Qiang Yang (Natural Hazards, 2026)

Oral Administrations of Short-Chain Fatty Acids or Probiotics Extend the Survival Times and Mitigate the Neuropathological Damages in the Scrapie-Infected Hamsters - Yuan Wang; Dong-Lin Liang; Run-Dong Cao; Ruhan A.; Jia-Feng Zeng; Bing Xu; Ju-Zheng Li; Wei-Wei Zhang; Li-Ping Gao; Kang Xiao; Xiao-Ping Dong; Qi Shi (Molecular Neurobiology, 2026)

Tunable surface potential nanomaterials for enhanced environmental nucleic acid extraction and surveillance - Jiahui Lv; Tong Li; Ying Liu; Bing Li; Peng Jia; Chuwei Ma; Hongjun Xiao; Guanghui Wang; Li Cheng; Jingkai Yang; Ziyi Xu; Xuan Tan; et al. (Water Research, 2025)

Frequency-domain linear potential analysis on the near-trapping of water waves in the square cylinder array - Ying-Chao Ma; Hao Shen; Zhi-Wei Song; Hui Yang; Hong-Fei Mao; Zhong-Bing Zhou; Guang-Lin Wu (Ocean Engineering, 2025)

Corrigendum to “Rho GAPase protein 1 (RACGAP1) affects the proliferation and metastasis of esophageal squamous cell carcinoma cells by regulating signaling pathways: Thermal infrared medical image inspection” [J Therm Biol. 2025 131 104178 doi: 10.1016/j.jtherbio.2025.104178. PMID: 40561732] - Yu-Hao Zhu; Jia-Cheng Lin; Xiao-Bing Lin; Wei-Yuan Lai; Jin-Dong Yu; Lin Long (Journal of Thermal Biology, 2025)

Unraveling the mechanistic interplay of carbon cycle and nitrogen transport within deep reservoirs: A perspective of δ13CDIC analysis - Yufei Bao; Yuchun Wang; Qian Zhang; Xiaobo Liu; Peng Hu; Meng Sun; Xiaodong Qu; Jie Wen; Shanze Li; Bing Lin; Jialong Huang (Journal of Hydrology, 2025)

Whether the hybridization of polystyrene, polyethylene, and polypropylene microplastics impacts aquatic carbon leakage from water hyacinth: A case study considering per(poly)fluorocarboxylicacid cocontamination - Zi-wei Chen; Zu-lin Hua; Ye-bing Shi; Li Gu; Chun Wang (Journal of Environmental Chemical Engineering, 2025)

Functional differentiation of Sojae semen Praeparatum: A multi-omics analysis of the effects of Artemisia annua and Mori folium on composition, microorganisms, and functional characteristics - Yingying Cheng; Bing Wang; Qiaoling Ma; Min Sun; Xintong Wang; Ruolan Wang; Hongping Chen; Lin Chen; Youping Liu; Fu Wang; Chuan Zheng; Yuan Hu (Food Research International, 2025)

Identification of new coumarin-cinnamic acid hybrid FtsZ inhibitors as potential bactericides for enhancing the yield and quality of rice - Ling Zhang; Si-yue Ma; Wan Chen; Lin-li Yang; Yue Ding; Xiang Zhou; Li-wei Liu; Zhi-bing Wu; Song Yang (Food Chemistry, 2025)

Fabrication of Rubus chingii Hu ellagitannins-loaded W/O/W double emulsion gels stabilized by WPI/pectin complexes: Physicochemical properties, digestion characteristics, and transformation of ellagitannins - Dong-Jun Hou; Quan-yuan Xie; Ming-Shun Chen; Yu-Lin Cheng; Bing Zhang; Zong-cai Tu; Lu Zhang (Food Chemistry, 2025)

Exploring the feasibility of multi-element fingerprinting with chemometrics for discriminating the geographical origins of asparagus and its risk assessment - Qiuhong Zhang; Min Li; Chuanhao Dou; Xiangliang Yan; Bing Wang; Huimin Zhang; Yongqiang Lin; Dantong Zhao (Food Chemistry, 2025)

LPS disrupts erythroid-myeloid balance in zebrafish via Jak2/Stat3-Hif1a signaling - Hai-Chuan Yu; Meng-Yao Chen; Shuang-Ling Zhang; Fang-Chao Tong; Fan-Ping Wang; Lin Wang; Jia-Long Zhang; Jiao-Jie Guo; Bing-Yang Zhang; Jia-Qi Tian; Jiao Wu (Fish & Shellfish Immunology, 2025)

From chemisorption to physisorption: A synergistic computational screening approach to exploit N-rich covalent organic frameworks for methyl iodide capture - Tianyu Guo; Xiaoyu Wu; Chenrui Li; Liangdan Zhao; Mingrui Zuo; Lin Liu; Lin-Bing Sun; Lifeng Ding (Chemical Engineering Journal, 2025)

A sequential nanotherapy potentiate anti-angiogenic therapy by disrupting lipid metabolism under metabolic stress - Qiye Xi; Xiaojing Lin; Yixian Xie; Fengyong Cheng; Ben Hu; Fengling Zhang; Fushan Sun; Bing Han; Yufang Lai; Yongxia Wang; Jigang Wang; Meng Yu (Chemical Engineering Journal, 2025)

Charge-engineered 2D layered magnetic Cl-CaFe2O4/g-C3N4 catalyst for catalytic ozonation of norfloxacin: performance, mechanism and ecotoxicological assessment - Lanhe Zhang; Bing Shi; Hui Liu; Xu Lin; Fangfei Shi (Chemical Engineering Journal, 2025)

Covalent organic frameworks with synergistic linkages and functional groups boost electrochemiluminescence for sensitive detection of long non-coding RNA - Linlin Song; Lin Cui; Xiaoran Zou; Xueting Cao; Wenqi Chu; Wenjie Gao; Lin Cheng; Bing Sun; Chun-yang Zhang (Chemical Engineering Journal, 2025)

d-band center-guided high-fidelity generative model for inverse materials design - Jiahao Wu; Peijia Lin; Zheshuai Lin; Bing Zhang; Yanchuan Guo (Chemical Engineering Journal, 2025)

Structural characterization and immunomodulatory activity of a novel pectin polysaccharide extracted from Gardenia jasminoides fruit - Yue Guo; Yanan Cheng; Bing Zheng; Jianhua Xie; Yi Chen; Huasi Lin; Hui Liu; Xiaobo Hu; Qiang Yu (Carbohydrate Polymers, 2025)

Effects of gum incorporation on the properties of sodium alginate-based composite hydrogel beads for encapsulating lactic acid bacteria - Ying-Ying Jing; Yun-Cheng Li; Yong-Qi Luo; Long-Hua Zou; Yuan-Mou Tang; Yu-Xi Lin; Fan-Bing Meng (Carbohydrate Polymers, 2025)

Peripheral inflammation in spinocerebellar ataxia type 3: associations with genetic and clinical manifestations - Jia-Yi Zhang; Qiu-Ni Su; Han Lin; Wei Lin; Mao-Lin Cui; Zhuo-Ying Huang; Bei-Ning Ye; Ying-Xin Ye; Yi-Lin Jia; Qing-Ying Zhu; Zhi-Han Li; Min-Ting Lin; et al. (Inflammation Research, 2025)

Altered CD27-related T cell subsets reflect immune imbalance in systemic lupus erythematosus - Xiaoning Chen; Bing Shen; Weijie Lin; Ziqi Xiong; Bohao Yang; Hanxi Luo; Zhiwei Zong; Jie Chen; Ayibaota Bahabayi; Chen Liu (Immunologic Research, 2025)

Distribution, sources, and health risks of PM2.5 and PM1-bound polycyclic aromatic hydrocarbons in the Pearl River Delta - Guang-Hong Zhai; Yue Wen; Mo Yang; Qi-Zhen Wu; Wan-Ting He; Li-Xia Liang; Le-Bing Wang; Yun-Ting Zhang; Jing-Wen Huang; Jia-Xin Zhou; Min Li; Gao Meng; et al. (Environmental Monitoring and Assessment, 2025)

Investigating antidiabetic drug targets as potential therapeutic modulators for schizophrenia - Yu-Sheng Huang; Xu Lin; Ya-Juan Xu; Gui-Bing Chen (Psychopharmacology, 2025)
Rationale Certain types of antidiabetic drugs (ADs) have been proven to improve cognitive functions and symptom dimensions in schizophrenia (SCZ). Objectives Schizophrenia is a major contributor to social functional impairment, and antipsychotics (APs) remain the cornerstone of its treatment. Investigating the potential of antidiabetic drugs as APs could significantly advance therapeutic strategies for schizophrenia. Methods To assess this potential, we employed an integrated analytical framework that included two-sample Mendelian randomization (MR) using genetic proxies for antidiabetic drug targets, multivariable MR (MVMR), and colocalization analyses. Furthermore, gene and drug enrichment analyses alongside molecular docking studies were performed to elucidate underlying mechanisms and identify candidate drugs. The analysis utilized summary statistics from genome-wide association meta-analyses (GWAS) of schizophrenia, as well as gene expression data from the eQTLGen consortium. Results A total of fourteen drug targets were identified among eight major antidiabetic drugs. Notably, RXRB, a target of thiazolidinediones (TZDs), exhibited a strong inverse association with schizophrenia risk (OR: 0.28, 95% CI: 0.21–0.38, P < 0.001). Other significant targets included GPD1 (targeted by metformin), LRP2 (insulin), SLC5A2 (SGLT2 inhibitors), and ABCC8/KCNJ11 and INS (sulfonylureas). Primary and secondary MR analyses confirmed the associations of RXRB, INS, LRP2, and SLC5A2 with gene expression levels. Drug enrichment and molecular docking analyses identified bezafibrate as a promising candidate for repurposing as an AP. Conclusion Antidiabetic drugs may possess therapeutic potential in schizophrenia by modulating specific drug-related pathways.These findings provide new theoretical support for the selection of ADs in patients with schizophrenia comorbid with diabetes, and also offer new insights for the future development of APs.

HDAC3 Epigenetic Suppression by Electroacupuncture Restores AMPA Receptor Function and Synaptic Plasticity in Alzheimer’s Disease Models - Hongzhu Li; Bing Deng; Mucan Lin; Lanfeng Lai; Jiaying Zhao; Yuemei Li (NeuroMolecular Medicine, 2025)

Application of a deep learning model with physical model constraints and attention mechanism for state prediction in high-power power-shift tractors - Li-quan Lu; Ze-peng Zhang; Guang-lin Zhang; Bing Han; Hao-ran Yang; Zhong-xiang Zhu; Zheng-he Song; Zhi-qiang Zhai; Jian-hua Wang; Chuan-chuan Zhang (Computers and Electronics in Agriculture, 2025)

Competitive blockade of NKCC1 by potassium suppresses thallium bioaccumulation and neurotoxicity in zebrafish: Implications for aquatic toxicity - Jian Liu; Xin Li; Yiwen Zhu; Hengyu Gui; Kang Luo; Hongwei Liang; Ai Guan; Weizhen Liu; Hongyu Zhou; Zhang Lin; Bing Yan (Science of The Total Environment, 2025)

Facile synthesis of high loading and highly electron-delocalized Co single-atom catalyst for PMS activation: An in-depth study of molecular orbital and catalytic mechanisms - Mu Li; Dongsheng Xia; Wei Zhang; Feiyun Sun; Guan Zhang; Lin Lin; Zhengjun Gong; Bing Li; Xiao-yan Li (Journal of Hazardous Materials, 2025)

Surface-modified nanoplastics facilitate the dissemination and persistence of antibiotic resistance genes - Xiaojie Sun; Xue Chen; Jie Ming; Zhiquan Lin; Yue-Zhong Li; Bing-Jie Ni; Shou-Qing Ni (Journal of Hazardous Materials, 2025)

Interfacial freeze-thaw stability of Pickering emulsions stabilized by sodium Caseinate-modified solid lipid particles: Influence of lipid crystalline structure and polymorphic transitions - Qihong Jiang; Xin Luo; Lin Li; Bing Li; Xia Zhang (Food Chemistry, 2025)

Extended thermophilic phase promotes fungal-bacterial collaboration to facilitate humification in batch-fed composting - Haichao Wang; Xiaowei Zheng; Dong Guo; Dan Liu; Bing Bai; Yan Shao; Bing Yue; Huan Zhang; Shuye Lin (Environmental Research, 2025)

Microplastic accumulation in endometrial cancer tissues and its metabolic impact - Chunlin Dong; Hongwen Xu; Bing Zhang; Yaying Lin; Jing Song; Jinjin Yu; Ding Ma (Environmental Pollution, 2025)

Quantification of shear deformation in reinforced concrete beams: An approach integrating arch action and decoupling methodologies - Haoran Lin; Bing Li (Engineering Structures, 2025)

Food-grade Pickering emulsions for dual-targeted delivery of dietary bioactives to the colon and inflamed sites: A synergistic strategy for alleviating ulcerative colitis - Yi Yuan; Xia Zhang; Qiyong Guo; Bing Li; Lin Li; Shaoyun Wang; Qingrong Xue; Jintao Liu (Chemical Engineering Journal, 2025)

Single-stage reverse-structured solar evaporator from two to three dimensional by transparent hydrogel - Shen Du; Bing-Lin Bai; Ya-Ling He; Mingyun Dai; Jia-Cheng Wan (Chemical Engineering Journal, 2025)

A bifunctional fluorescent probe for simultaneous imaging of myelin integrity and β-amyloid plaques in Alzheimer's disease progression - Xueting Wang; Huan Liu; Xueao Wang; He Wang; Jie Lin; Xiangjie Luo; Jian-Jun Yang; Bing Zhang; Guiquan Chen; Hai-Liang Zhu; Tony D. James; Yong Qian (Chemical Engineering Journal, 2025)

Spectral-consistent cross-display standardization: A Calibration-adaptive framework for unifying visual and non-visual effects - Bing Zhang; Shenfei Chen; Jinghan Qiu; Xianxian Zeng; Zhichao Ma; Yi Lin (Building and Environment, 2025)

Energy-driven anthropogenic heat modulates China’s summer climate: CESM2 projections under SSP5-8.5 for the late 21st century - Mengyi Zhang; Xiaoyu Jiang; Ruilin Wang; Bing Chen; Guo Lin; Xue Wu; Chenglai Wu; Huiyi Yang; Xiaohong Liu (Climate Dynamics, 2025)

The effect of construction measures on the seismic performance of a frame-infilled wall with fabricated constructional column - Shucheng Yuan; Haifeng Lin; Haibo Luo; Zhanyuan Zhu; Zuyin Zou; Wei Liang; Zhuoying Wang; Bing Ma; Jinxin Yao; Qichao Zhang; Jiangfeng Dong; Hwa Kian Chai (Bulletin of Earthquake Engineering, 2025)

Elucidating the suppressive role of native bacterial traits against root-knot nematodes to control plant-parasitic effect in serpentine hostile rhizosphere soil - Aslia Asif; Liang-Yu Lin; Ping-Chi Hsu; Suprokash Koner; Zeng-Yei Hseu; Tsui-Kang Hsu; Shih-Wei Huang; Bing-Mu Hsu (Applied Soil Ecology, 2025)

Three new triterpenoids from the fruit of Eleutherococcus senticosus (Rupr.) Harms - Yan Liu; Yu-Xuan Lin; Xiao-Hui Rong; Meng-Meng Li; Juan Pan; Wei Guan; Hai-Xue Kuang; Bing-You Yang (Natural Product Research, 2025)

Root architectural diversity underpins soil stabilisation in alpine grasslands: Trait-mediated mechanisms across rhizomatic, densely tufted, and sparsely tufted herbs - Junmei Gao; Lingshan Ni; Kexin Li; Ni Zhu; Lin Liu; Suyuan Jia; Laiting Zhang; Shixiong Li; Bing Liu; Xiaoli Wang; Yu Liu (Plant and Soil, 2025)

Separation and recovery of iron from vanadium extraction tailing slag by P204-P507 mixture collector flotation process - Yi-bo Wang; Jing-wei Li; Xiao-long Liu; Xin-fei Jiang; Yin-he Lin; Zhi Tian; Jun-jie Yin; Bing-qing Huang; Jia-xin Yang; Chen-xuan Wang; Zi-wang Wu; Shi-xing Ma; et al. (Journal of Environmental Chemical Engineering, 2025)

UV/green rust/glucose oxidase-based Fenton-like Systems for algal removal: Mechanisms of sustained oxidative capacity in UV-enhanced systems - Siwei Li; Qian Zhang; Meng Li; Xiangyu Liu; Jie Peng; Bing Lin; Jialong Huang; Yong Huang (Journal of Environmental Chemical Engineering, 2025)

Deciphering surfactants modulation of PersiLipase1-p-NPL interaction via MD simulations - Yuhan Zhao; Lin Chen; Wei Chen; Bing Zhao; Ruige Wang (Journal of Environmental Chemical Engineering, 2025)

Exposure assessment of Staphylococcus aureus in fluid milk - Yingying Lin; Mingjie Pan; Yunfeng Yang; Xiao Ye; Huahu Xu; Yikan Lin; Bing Niu (International Dairy Journal, 2025)

Pueraria lobata-derived peptides hold promise as a novel antioxidant source by mitigating ethanol-induced oxidative stress in HepG2 cells through regulating the Keap1/Nrf2 pathway - Lin Liu; Jiehua Liang; Minjie He; Bingyan Jiang; Jie Liu; Junsong Wu; Pan Li; Bing Du (Food Chemistry, 2025)

Sensitive detection of phthalates in Chinese Baijiu by online in-tube SPME-HPLC-DAD based on carbonized COF-coated carbon fibers - Yaming Sun; Baoen Su; Ke Zhang; Yuhong Lin; Bing Wang; Min Sun (Food Chemistry, 2025)

Impact of long-term submerge-emerge alternation on the fate of per- and polyfluoroalkyl substances (PFASs) in sediment-water systems: Insight from dissolved organic matter - Ye-bing Shi; Zu-lin Hua; Zi-wei Chen (Environmental Pollution, 2025)

Habitat suitability assessment and prediction using a physiological species distribution model based on whole-genome genotyping and microclimate data - Bing-Xian Liu; Liang Zhang; Zhan-Wei Zhao; Lin-Xuan Ma; Xiao-Nie Lin; Ming-Ling Liao; Yun-Wei Dong (Estuarine, Coastal and Shelf Science, 2025)

Hyperlocal disaster damage assessment using bi-temporal street-view imagery and pre-trained vision models - Yifan Yang; Lei Zou; Bing Zhou; Daoyang Li; Binbin Lin; Joynal Abedin; Mingzheng Yang (Computers, Environment and Urban Systems, 2025)

Highly flexible Janus fabric based on TPU spraying and laser processing for personal thermal-wet management - Zixuan Xu; Yulun Wu; Shuqiang Min; Lin Hu; Tonghuan Zhan; Heng Wang; Yan Yuan; Haojun Luo; Yichen Tang; Bing Xu (Chemical Engineering Journal, 2025)

Self-reconstructed Cu2O/Co3O4@NC heterostructured catalyst for efficient tandem electrocatalytic conversion of nitrate to ammonia - Lin Zhu Dai; Guo Yu Yong; Wan Ni Gan; Ting Li; Zhi Cheng Chen; Lun Yao Pan; Hong Qun Luo; Nian Bing Li (Chemical Engineering Journal, 2025)

Recycling of sub-continental lithosphere during early ocean spreading revealed by Triassic trachytes in the central Tibetan Plateau - Zong-Yong Yang; Qiang Wang; Jun Wang; Lin Ma; Derek Wyman; Andrew C. Kerr; Xian-Wu Bi; Peng Sun; Xiu-Zheng Zhang; Lu-Lu Hao; Xiao Liu; Chuan-Bing Xu; et al. (Chemical Geology, 2025)

Recycling of continental crust into the deep mantle in orogens: Constraints from zircon U-Pb-Hf-O and whole-rock Mg-Fe isotopes of Baihua complex, North Qinling Orogen - Gang Yang; Juan Zhang; Hong-Fu Zhang; An-Ping Chen; A-Bing Lin (Chemical Geology, 2025)

A novel approach for wave-turbulence decomposition - Jianliang Lin; Chunyan Zhu; Jianwei Sun; Weiming Xie; Bram van Prooijen; Leicheng Guo; Qing He; Qingshu Yang; Zheng Bing Wang (Coastal Engineering, 2025)

Pest-YOLOv8: enhanced detection for small and complex agricultural pests using triple attention and wise-IoU - Bing Su; Yueyang Zhu; Yifeng Lin (Journal of Plant Diseases and Protection, 2025)

Both biotic and abiotic soil N₂O productions are lower under organic N than inorganic N deposition in a Moso bamboo forest - Wenting Jiang; Yan Wang; Yongxin Lin; Hiroko Akiyama; Yunying Fang; Tony Vancov; Shenglei Fu; Hojeong Kang; Xinli Chen; Zhengqin Xiong; Zhijie Li; Shuijin Hu; et al. (Biology and Fertility of Soils, 2025)

Novel L-type chiral metal(II) complexes inhibit breast cancer growth through synergistic effects of anti-angiogenesis, anti-inflammatory, apoptosis induction and cuproptosis - Nan Jin; Bing-Bing Xu; Hong-Yu Lin; Bing-Li Jiang; Qiao-Ying Yang; Xiu-Ying Qin (Apoptosis, 2025)

Altererythrobacter guangdongensis sp. nov. and Tsuneonella sediminis sp. nov., two novel carotenoid-producing species isolated from tidal flat sediment - Huan-Huan He; Ying Wang; Bing-Yu Li; Chun-Yan Lu; Shuai Li; Zhuo-Huan Zheng; Liang Zhang; Wen-Hui Lian; Xin-Tao Luo; Hai-Wei Lin; Lei Dong; Wen-Jun Li (Systematic and Applied Microbiology, 2025)

First experiment using post-accelerated unstable ion beams at BRIF: angular distribution of the 21 , 22 Na elastic scattering from doubly magic 40 Ca - Wei Nan; Bing Guo; Cheng-Jian Lin; Dan-Yang Pang; Lei Yang; Dong-Xi Wang; Guo Yang; Yang-Ping Shen; Bing Tang; Qi-Wen Fan; Yi-Wen Bao; Lei Cao; et al. (Science Bulletin, 2025)

Cadmium and rising tides: Amplified greenhouse gas emissions from mangrove sediment - Hengzhi Yin; Ruili Li; Xiaofeng Wu; Yuefei Huang; Guanghui Lin; Bing Li; Guanqian Wang (Regional Studies in Marine Science, 2025)

Novel three-dimensional interpenetrating network boron-doped diamond anodes for rapid degradation of refractory organic pollutant - Wanlin Yang; Xu Lin; Yuan Liao; Dongtao Lei; Menglin Zhang; Jian Wang; Weifeng Yang; Bing Wang; Ying Xiong (Process Safety and Environmental Protection, 2025)

Mineralogical insights into the release behaviors of potentially toxic elements from the indigenous Zn smelting slags dumping sites - Ze-Lin Xu; Mei-Chun Zhou; Jin-Hui Miao; Wen-Chu Zhao; Rong-Bing Fu; Da-Mao Xu (Process Safety and Environmental Protection, 2025)

The role of light intensity in an electrically enhanced algal activated sludge (E-AAS) system for the treatment of aniline wastewater: Effects on bacterial-algal synergies and electron transport - Xunhao Liu; Qian Zhang; Meng Li; Bing Lin; Qi He; Nanping Wu; Jiajing Chen; Xiaoqian Dong; Hongyu Wang (Journal of Water Process Engineering, 2025)

The emerging threat of hybrid microplastics: Impacts on per(poly)fluoroalkyl substance bioaccumulation and phytotoxicity in floating macrophytes - Zi-wei Chen; Zu-lin Hua; Ye-bing Shi; Li Gu; Fu-zhu Ye; Jia-yun Chen; Peng Guo (Journal of Hazardous Materials, 2025)

Particle size distribution (PSD) of mine waste dump via unmanned aerial vehicle (UAV) image recognition and sieving - Han Ke; Zi Han Lin; Xiao Fei Wei; Bing Zhou; Tian Shou Hu; Shuai Zhang; Jie Hu; Chen Sheng Zhang (Engineering Geology, 2025)

Synergistic enhancement of wetland purification performance by introducing intermittent aeration and zero-valent iron under chilling stress - Lin-Yuan Wu; Bing-Xu Guo; Ke-Jia Zhang; Jun-Yu Ai; Wei-Yi Shi; Qing-Yuan Tian; Wen-Huai Wang; Jun-Feng Li (Chemical Engineering Journal, 2025)

Single cobalt atoms anchored on in-situ-formed carbon layers within restricted microenvironment: an efficient catalyst for oxygen evolution reaction - Yang Wang; Ying Zhou; Xuan-Yi Liu; Xiao-Qin Zheng; Shui-Jing Wang; Kai Zhang; Xiang-Bin Shao; Jiahui Kou; Lin-Bing Sun (Chemical Engineering Journal, 2025)

Tremella fuciformis Polysaccharides Alleviate Early Brain Injury in Experimental Subarachnoid Hemorrhage by Inhibiting the KDR-Mediated P38 MAPK/NF-κB Pathway - Yu-hui Wan; Zeng-jing Cheng; Ling-xiang Fan; De-hong Yang; Bing-lin Chen; Xiang-xin Chen; Qing Zhu (Molecular Neurobiology, 2025)

Unprecedented triterpenes with anti-inflammatory activity from Limax maximus - Ya-feng Wang; Pei-de Tang; Rui-jie He; Zhang-bin Liu; Yong-qiong Wei; Jun Ruan; Bing-yuan Yang; Yong-lin Huang (Journal of Natural Medicines, 2025)

Anecic earthworm enhanced the soil multifunctionality by affecting soil bacterial abundant taxa - Yan Hu; Bing-Jie Jin; Xin-Yuan Li; Qing-Lin Chen; Cheng-Liang Sun; Gang Li; Xian-Yong Lin (Soil Ecology Letters, 2025)

Enhancing soil organic carbon fixation with modified bentonite composites - Bing Liu; Yuwen Shen; Deshui Tan; Bohan Cheng; Haitao Lin; Rui Xue; Zongxin Li; Qiang Yao; Shuying Jiao (Applied Clay Science, 2025)

Flash: Dual-gradient filtering membranes enable ultra-fast plasma separation - Xianchang Wu; Hui Niu; Tonghuan Zhan; Yulun Wu; Ping Qiao; Lin Hu; Bing Xu (Analytica Chimica Acta, 2025)

Analysis of temporal and spatial distribution of CG lightning activity and its relationship with terrain features around Jiuxianshan mountain - Biao Zhu; Binbin Lin; Bing Liu; Hengyi Liu (Journal of Atmospheric and Solar-Terrestrial Physics, 2025)

Insights into the balance of safety, flavor, and texture in fermented fish: A study based on full-length sequencing of fermented largemouth bass (Micropterus salmoides) - Xianhao Zhang; Bingrui Guo; Bing Dai; Shimiao Wang; Siqi Zhang; Sufang Zhang; Chaofan Ji; Beiwei Zhu; Xinping Lin (International Journal of Food Microbiology, 2025)

Spatiotemporal analysis of illegal Coilia nasus fishing linked to suitable habitats modeled with MaxEnt in China - Suhang Wei; Junjie Zhong; Songyin Qiu; Xiaodong Sun; Mingjie Pan; Yingying Lin; Qin Chen; Bing Niu (Journal for Nature Conservation, 2025)

Research progress on the biological characteristics and the synthesis pathway of cantharidin in the family meloidae (Insecta: Coleoptera) - Qian Sun; Bing Wang; Yingying Xie; Fei Xue; Shuangcheng Ma; Bonian Zhao; Yongqiang Lin (Insect Biochemistry and Molecular Biology, 2025)

Evaluating palm olein and palm stearin on hepatic lipids in C57BL/6 J mice under low and high fat intakes: A quantitative lipidomic approach - Liting Wan; Lin Li; Xia Zhang; Bing Li; Kristen J. Brao; Janette M. Harro; Mark E. Shirtliff (Food Chemistry, 2025)

Combining the life cycle model and corrosion model to analyze the impact of corrosion on carbon emissions of steel pipelines - An Yan; Ying Xiao; Hongyang Ren; Bing Lin; Hailong Zhang; Yingying Wang; Xi Li; Bing Wang; Junlei Tang (Environmental Impact Assessment Review, 2025)

Micropatterned piezoelectric films induced by modulated corona field for weak signal detection - Fu Lv; Chenghang Yu; Bing Liu; Jiamin Lin; Zijian Hong; Yongjun Wu; Zhaohui Ren; Qilong Zhang; Shurong Dong; Jikui Luo; Juan Li; Yuhui Huang (Chemical Engineering Journal, 2025)

Effects of Physical Exercise on High-Fat Diet–Induced Hypothalamic Inflammation: Systematic Review - Yu Xue Sun; Jia Bao Guo; Bing Lin Chen (Molecular Neurobiology, 2025)

The formation of a hybrid fish derived from Labeo rohita ♀ × Cyprinus carpio ♂ and exhibiting stronger low temperature tolerance - Jiali Lin; Haoran Zhang; Jietao Wang; Bing Fu; Zexun Zhou; Wuhui Li; Huirong Yang; Shaojun Liu (Aquaculture, 2025)

Juvenile macular degeneration in nonhuman primates generated by germline knockout of ABCA4 gene - Ya Ma; Qiang Lin; Hai-Long He; Yi-Xin Liu; Min Li; Xiao-Hui Zhang; Zi-Bing Jin (Science Bulletin, 2025)

Petrogenesis and tectonic implication of the Neoproterozoic Shuimo alkaline-carbonatite complex from Northwestern margin of the Yangtze Block (China) - Bin Lin; Lian-Xun Wang; Yu-Fang Zhong; Xiao-Bing Qi; Xue-Wei Fu; Chang-Qian Ma (Precambrian Research, 2025)

Rho GAPase protein 1 (RACGAP1) affects the proliferation and metastasis of esophageal squamous cell carcinoma cells by regulating signaling pathways: Thermal infrared medical image inspection - Yu-Hao Zhu; Jia-Cheng Lin; Xiao-Bing Lin; Wei-Yuan Lai; Jin-Dong Yu; Lin Long (Journal of Thermal Biology, 2025)

Distinct neurotoxic mechanisms of thallium and lead: Calcium-mediated apoptosis and iron-induced ferroptosis in zebrafish at environmental concentrations - Jian Liu; Ai Guan; Zihui Huo; Xin Li; Yiwen Zhu; Hongwei Liang; Weizhen Liu; Hongyu Zhou; Zhang Lin; Bing Yan (Journal of Hazardous Materials, 2025)

Response of the rhizosphere microenvironment to per(poly)fluoroalkyl substance partitioning induced by submerge-emerge alternation - Ye-bing Shi; Zu-lin Hua; Zi-wei Chen (Journal of Environmental Management, 2025)

Improved degradable, mechanical, and osteoimmunity-regulating performances of additively manufactured Zn-Mg alloy with heterogeneous microstructure for augmented bone regeneration - Zhengjun Lin; Luxin Liang; Yawei Li; Yanlin Wu; Jing Li; Bing Wang; Chao Chen; Tang Liu (Chemical Engineering Journal, 2025)

Electrocatalytic upcycling of polylactic acid hydrolysate and simultaneous hydrogen production - Ping He; Jiang-nan Xu; Jia-yang Dou; Bing Xu; She-ying Dong; Ting-lin Huang; Jun-Jie Zhu (Chemical Engineering Journal, 2025)

Investigating the Potential Therapeutic Targeting of the JAK-STAT Pathway in Cerebrovascular Diseases: Opportunities and Challenges - Jia-Wei Wu; Bing-Xin Wang; Li-Ping Shen; Yong-Lin Chen; Zhi-Yong Du; Shi-Qing Du; Xiao-Jie Lu; Xu-Dong Zhao (Molecular Neurobiology, 2025)

Safranal ameliorates atherosclerosis progression partly via repressing PI3K/Akt and NF-κB signaling pathways in ApoE (−/−) mice - Yining Geng; Manping Song; Bing Huang; Ru Lin; Shiwen Wu; An Lin (Journal of Natural Medicines, 2025)

A study of frictional instability induced by fluid injection for the granite fracture - Bing Bai; Hang Lin; Hengtao Yang; Yan Zou (Bulletin of Engineering Geology and the Environment, 2025)

Deepening and narrowing impacts on circulation, stratification, and sediment transport in the Changjiang Estuary - Jianliang Lin; Bram C. van Prooijen; Chunyan Zhu; Leicheng Guo; Qing He; Zheng Bing Wang; Qingshu Yang (Frontiers in Marine Science, 2025)
Channel deepening and narrowing are common anthropogenic modifications in estuaries, but their combined effects on estuarine circulation, stratification, and sediment transport remain insufficiently understood. This study investigates these combined impacts in the North Passage of the Changjiang Estuary, where large-scale deepening and narrowing have significantly altered hydrodynamic and sediment processes. Our analysis demonstrates that channel deepening intensifies estuarine circulation by strengthening the landward near-bed flow, thereby enhancing sediment import. Contrary to initial expectations that narrowing would promote sediment flushing, our results indicate that narrowing increases stratification, steepens along-estuary salinity gradients, and suppresses vertical mixing. Intensified stratification further reinforces estuarine circulation, promoting sediment trapping at the saltwater intrusion limit. Additionally, enhanced tidal pumping driven by increased velocity and suspended sediment concentration gradients extends the estuarine turbidity maximum both upstream and downstream, a process often overlooked in engineered estuaries. These findings challenge conventional assumptions regarding the sedimentary impacts of narrowing, emphasizing instead its critical role in amplifying estuarine circulation and sediment trapping. Our results provide new insights into sediment dynamics in river-dominated estuaries, with significant implications for estuarine management, dredging operations, water quality control, and long-term morphological stability.

Modeling and mechanistic understanding of vertical dissolved methane transport in integrated vertical flow constructed wetlands (IVCWs) - Ru Xue; Ke Zhang; Xiaoling Liu; Bing Jiang; Hongbing Luo; Mei Li; You Mo; Cheng Liu; Lin Li; Wei Chen; Lin Cheng; Jia Chen; et al. (Journal of Water Process Engineering, 2025)

A novel non-genetic strategy to increase lipid content in Phaeodactylum tricornutum - Kun-Tao Peng; Bing-Hong Xiong; Gao Cheng; Yuan-Hong Zhong; Lin Yu (Food Bioscience, 2025)

DSSAT modeling of oilseed flax (Linum usitatissimum L.): Sensitivity analysis of yield to weather variability and nitrogen application - Zechen Lin; Yue Li; Gerrit Hoogenboom; Yuhong Gao; Bing Wu; Ling Wu; Lili Wu; Hui Zhou; Bin Yan; Peina Lu; Jie Tang; Shunchang Su; et al. (Field Crops Research, 2025)

Enhancing cancer-killing activity of PMN transfusion therapy via apoptotic modulation function of selenium nanoparticles - Chenyu Lin; Jing Wang; Yuqian Zhu; Dachuan Zhang; Xixi Huang; Jiaming Wang; Jianlin Ren; Ming Hou; Mufan Wu; Bing Shen; Bingdi Chen (Chemical Engineering Journal, 2025)

Epigenetics in the modern era of crop improvements - Yan Xue; Xiaofeng Cao; Xiangsong Chen; Xian Deng; Xing Wang Deng; Yong Ding; Aiwu Dong; Cheng-Guo Duan; Xiaofeng Fang; Lei Gong; Zhizhong Gong; Xiaofeng Gu; et al. (Science China Life Sciences, 2025)
Epigenetic mechanisms are integral to plant growth, development, and adaptation to environmental stimuli. Over the past two decades, our comprehension of these complex regulatory processes has expanded remarkably, producing a substantial body of knowledge on both locus-specific mechanisms and genome-wide regulatory patterns. Studies initially grounded in the model plant Arabidopsis have been broadened to encompass a diverse array of crop species, revealing the multifaceted roles of epigenetics in physiological and agronomic traits. With recent technological advancements, epigenetic regulations at the single-cell level and at the large-scale population level are emerging as new focuses. This review offers an in-depth synthesis of the diverse epigenetic regulations, detailing the catalytic machinery and regulatory functions. It delves into the intricate interplay among various epigenetic elements and their collective influence on the modulation of crop traits. Furthermore, it examines recent breakthroughs in technologies for epigenetic modifications and their integration into strategies for crop improvement. The review underscores the transformative potential of epigenetic strategies in bolstering crop performance, advocating for the development of efficient tools to fully exploit the agricultural benefits of epigenetic insights.

Effects of plant litter diversity on soil enzyme activity and microbial community composition in a Mongolian pine plantation - Bing Mao; Guigang Lin; Biao Zhu; Lei Zhao; Qiong Zhao; Qun Gang; De-Hui Zeng (Plant and Soil, 2025)

Lifespan extension by rapamycin in Brachionus dorcas (Rotifera) is dose and developmental stage dependent - Ting Liu; Han-Bing Dong; Bao-Chun Shi; Hao-Yue Zhao; Zhao-Yun Wang; Lin Liu; Wei-Lu Li; Yi-Long Xi (Hydrobiologia, 2025)

Pixel array-based urine biosensor for detection of trimethylamine N-oxide and glucose for early detection of diabetic kidney disease - Mei-Ching Yu; Chi-Jen Lo; Wei-Cheng Lin; Wei-Lun Yen; Yun-Yu Hsieh; Bing-Hong Chen; Fu-Sung Lo (Analytica Chimica Acta, 2025)

Molecular docking and molecular dynamics simulations revealed interaction mechanism of acetylcholinesterase with organophosphorus pesticides and their alternatives - Jiawen Yang; Lin Chen; Shuo Wang; Bing Zhao; Ruige Wang (Archives of Toxicology, 2025)

An Integrated Safety Monitoring and Pre-Warning System for Fishing Vessels - Kun Yang; Jinglong Lin; Jianjun Ding; Bing Zheng; Li Qin (Journal of Marine Science and Engineering, 2025)
Fishing vessels are essential for the activities of catching, moving, and storing fish. However, fishing vessel accidents claim thousands of deaths every year. This study presents a novel integrated safety monitoring and early warning system designed for fishing vessels, offering significant advancements in maritime safety through real-time alerts based on vessel attitude motion and environmental conditions. The innovation of the system lies in its dual-subsystem architecture: a sensing terminal equipped with a nine-axis sensor, temperature and humidity sensors, a GPS module, and a surveillance camera collects critical data, while a decision support subsystem processes this information via a fuzzy logic-based algorithm to generate a “danger score”. This score quantifies the vessel’s safety status, enabling the system to trigger alerts through SMS and web notifications when predefined thresholds are exceeded. Field trials in the Zhoushan Sea area confirmed the system’s effectiveness in accurately predicting safety hazards and providing timely alerts. The results highlight its potential to enhance operational safety and contribute to the digitization of fisheries management by offering reliable real-time data on vessel conditions. The system’s modular and cost-efficient design ensures it is scalable and adaptable for widespread use across the fishing industry. Our study addresses the limitations of existing technologies by providing a balanced solution that combines comprehensive sensing capabilities with real-time responsiveness and cost-effectiveness, offering a practical and innovative approach to improve fishing vessel safety.

Calculation and analysis of wave loads and hydrodynamic coefficients on submerged floating tunnels with various cross-sections - Hong-Fei Mao; Wei-Jiang Zheng; Qin-Ru Yang; Zhong-Bing Zhou; Zheng-Lin Tian; Long Han; Guang-Lin Wu; Jin-Bo Lin (Ocean Engineering, 2025)

RAPID LEAF FALLING 1 facilitates chemical defoliation and mechanical harvesting in cotton - Bing Zhang; Dandan Yue; Bei Han; Danfan Bao; Xiao Zhang; Xuyang Hao; Xin Lin; Keith Lindsey; Longfu Zhu; Shuangxia Jin; Maojun Wang; Haijiang Xu; et al. (Molecular Plant, 2025)

Dynamic behavior of double-column FRP-concrete-steel tubular bridge piers subjected to vehicular impact: Experimental study and numerical analysis - Shuhong Lin; Bing Zhang; Sumei Zhang (Engineering Structures, 2025)

Comprehensive modification of cratonic lithospheric mantle beneath the central North China Craton: Insights from Li isotope systematics of olivine xenocrysts in Cenozoic basalts - Yao Xu; Hong-Fu Zhang; Yan-Jie Tang; A-Bing Lin; Juan Zhang; Ming-Jie Zhang (Chemical Geology, 2025)

MiR-518b Promotes the Tumorigenesis of Hepatocellular Carcinoma by Targeting EGR1 to Regulate PI3K/AKT/mTOR Signaling Pathway - Xinyuan Wang; Juan Li; Jiao Nong; Xin Deng; Yiping Chen; Bing Han; Lin Zeng; Xiabing Huang (Cell Biochemistry and Biophysics, 2025)

Identification of a novel strain of carp edema virus affecting Songpu mirror carp in Liaoning, China - Wen Shi; Bing Han; Huilin He; Ruixue Feng; Siyi Guo; Xuanyu Ren; Jinshan Huang; Xu Lin; Jiyuan Yin; Xiaonan Lv; Min Liu (Aquaculture, 2025)

Deciphering the N1-substituent effects on biodegradation of sulfonamides: Novel insights revealed from molecular biology and computational chemistry approaches - Jiahui Hu; Ruiyang Li; Jiayu Zhang; Lijia Cao; Huaxin Lei; Renxin Zhao; Lin Lin; Xiao-yan Li; Wen Zhang; Bing Li (Water Research, 2025)

Full realization of the RIBLL2 separator at the HIRFL-CSR facility - Xiao-Dong Xu; Yong Zheng; Zhi-Yu Sun; Yu-Nan Song; Bao-Hua Sun; Satoru Terashima; Chang-Jian Wang; Ge Guo; Guang-Shuai Li; Xiu-Lin Wei; Jun-Yao Xu; Ji-Chao Zhang; et al. (Science Bulletin, 2025)

Insight into selective removal of trace thallium (Tl(Ι)) by novel chitosan adsorbents encapsulating low-cost silicate mineral wastes - Yu Gong; Yujie Wang; Jing Yang; Yongxin Bing; Zifei Sun; Yongming Ju; Xiaochen Lin; Houhu Zhang; Zitao Lin; Weixin Li (Environmental Research, 2025)

A strategy for transplacental in utero therapy based on tetrahedral framework nucleic acid: Application to fetal alcohol spectrum disorders - Xinyue Pan; Zhiqiang Liu; Hao Sui; Songhang Li; Yao He; Bing Shi; Jingtao Li; Yunfeng Lin (Chemical Engineering Journal, 2025)

Pulsatilla saponin D inhibited the growth of osteosarcoma by regulating the JNK/ATF3 signaling pathway - Kaipeng Jin; Chengchun Shen; Wei Yu; Jinti Lin; Jian Zhu; Huimin Tao; Bing Liu (Chemico-Biological Interactions, 2025)

Assessment of the growth and quality of pepper seedlings under the combinations of daily light integral and nitrogen concentration - Zhengnan Yan; Xiuxiu Cao; Lixue Bing; Duo Lin; Fei Cheng; Kaiyan Wang; Ye Qi; Yanjie Yang (Horticulture, Environment, and Biotechnology, 2025)

Efficient conversion and highly sensitive detection of PAEs in milk based on hydrazinolysis reaction and hydrogen bonding using SERS technique - Lili Hua; Hongmei Li; Jing-Wen Zhou; Xiao-Feng Liu; Xian-Ming Guo; Zhao-Bing Zhang; Yichuan Kou; Tang-Tang Xie; Cuihong Sheng; Lin Zhang; Sheng-Hong Liu; Fan-Li Zhang; et al. (Analytica Chimica Acta, 2025)

Anemarrhenae rhizoma combined with Trichosanthis radix ameliorated type 2 diabetes in rats via the PI3K-Akt signalling pathway based on network pharmacology analysis - Yan Lin; Jinde Zheng; Xinyi Zhao; Bei Zheng; Ying Li; Wenjuan Yang; Bing Han; Hanxiao Tang; Meiling Zhang (Natural Product Research, 2025)

A mini review of Liparis species: an ornamental genus with considerable medicinal value - Xiao-Bing Chen; Li-Yun Huang; Min Zhou; Zhi-Jie Ling; Yan-Ping Liu; Xi-Lin Ouyang (Natural Product Research, 2025)

The bio-decolorization of methyl orange by S.putrefaciens CN32 and responding mechanism to salinity stress based on transcriptomic analysis - Bai-Hang Zhao; Bing-Lin Zhang; Bao-Yu Zhang; Rui-Xuan Liu; Xu-Ming Liu (Water Research, 2025)

Single- and combined-heavy metals/metalloids exposures are associated with infertility in US women aged 20–44: NHANES 2013–2020 analysis - He-Bin Chi; Jia-Jia Tang; Xiao-Yuan Fan; Han-Wen Zhang; Feng Tang; Xian-Shu Lin; Bing-Rui Yang; Na Li; Jun Guo; Li-An-Sheng Wu; Qiu-Qi Huang; Yin-Yin Xia (Reproductive Toxicology, 2025)

Adrenomedullin gene delivery rescues estrogen production in Leydig cells via the inhibition of TGF-β1/Smads signaling pathway - You-wen Luo; Xia-lian Zhu; Zhi-min Yang; Jian-hua Zhou; Tong Tao; Bing-hai Chen; Song-lin Qin; Bo-long Liu; Wei Hu (Reproductive Toxicology, 2025)

A UDP-glucuronosyltransferase gene UGT379A1 involved in detoxification of lufenuron in Diaphorina citri - Ze-Hao Huang; Qi Pan; Zhen Wu; Yu-Chao Shen; Si-Chen Li; Qi-Qi Yang; Shao-Hui Zhang; Shuang Lei; Yang-Yang Cui; Li-Li Ding; Shi-Jiang Yu; Liu Liu; et al. (Pesticide Biochemistry and Physiology, 2025)

Heterocyclic pseudoguaianolide oligomers and seco-pseudoguaianolide derivatives from the inflorescence of Ambrosia artemisiifolia - Zhi Zeng; Hua-liang He; Lin Qiu; Qiao Gao; Hong-shuai Gao; Jin Xue; Xiao-nian Li; You-zhi Li; Wen-bing Ding (Phytochemistry, 2025)

Modifying pea protein by cold plasma for the development of functional vegan cheese - Bing-Fan Chuang; Sheng-Yi Chen; Jer-An Lin; Gow-Chin Yen (Food Bioscience, 2025)

Terrestrial ecosystem response to Early Cretaceous global environmental change: A calibrated, high-resolution Aptian record from Northeast China - Ming-Dao Sun; Qin Lin; Jahandar Ramezani; Jiang-Si Liu; Zheng-An Lu; Han-Qing Yang; Jiang-Hao Bai; Shi-Xi Cai; Jun-Cai Chen; Xuan-Yu Chen; Hao Cui; Guang-Chao Deng; et al. (Earth and Planetary Science Letters, 2025)

MMCPT: A high-efficiency multiplexed metabolomics approach for rapid differential metabolite discovery using enzymatically cleavable chemoselective probe and TMT labeling - Lu Ye; Xue-Man Dong; Pei-Ran Miao; Yu-Xin Xu; Pu Wu; Ji-Lei Zhao; Hua-Min Zhang; Bing-Jun Zhou; Hui Zhang; Yuanyuan Lin; Jian-Liang Zhou (Chemical Engineering Journal, 2025)

Implant coating for promoted postoperative bone regeneration via cascade Reaction-Mediated microenvironment reprogramming - Bing Yan; Rurong Lin; Chongyin Qiu; Wei Sun; Xiaogang Ma; Jianxing Huang; Shuai Liu; Haifeng Liang; Chengzhong Xu; Chunyi Pu; Xiaojing Liu; Bo Yu; et al. (Chemical Engineering Journal, 2025)

Role of Exercise on Neuropathic Pain in Preclinical Models: Perspectives for Neuroglia - Chen-Chen Zhu; Yi-Li Zheng; Chan Gong; Bing-Lin Chen; Jia-Bao Guo (Molecular Neurobiology, 2025)

Effects of extreme precipitation on soil erosion affected by typhoons in central Shandong Province, China - Mingming Dong; Yousheng Wang; Jing Guo; Lin Meng; Zhen Xu; Zhikai Liu; Bing Liu; Lei Zhang; Bing Yin (Journal of Soils and Sediments, 2025)

New Lycopodium alkaloids with neuroprotective activities from Lycopodium japonicum Thunb - Zhen Xie; Yang Liu; Qiang Luo; Qiang Wang; Yue-Bing Min; Lin Liu; Dong-Kun Zheng (Natural Product Research, 2025)

Assessing the Impacts of the Israeli–Palestinian Conflict on Global Sea Transportation: From the View of Mass Tanker Trajectories - Bing Zhang; Xiaohui Chen; Haiyan Liu; Lin Ye; Ran Zhang; Yunpeng Zhao (Journal of Marine Science and Engineering, 2025)
Sea transportation plays a vital role in global trade, and studying the impact of emergencies on global sea transportation is essential to ensure the stability of trade. At present, the conflict between Palestine and Israel has attracted extensive attention worldwide. However, there is a lack of specific research on the impact of conflict on shipping, particularly on global shipping costs. By using the global vessel trajectory data of tankers from the Automatic Identification System (AIS) and taking the global sea transportation of large tankers as an example, this paper quantifies and visualizes the changes in global sea transportation before and after conflicts from a data-driven perspective. Firstly, the complete vessel trajectory, as well as the port of departure and the port of destination are extracted. Then, from the perspective of shipping cost and vessel traffic flow, we evaluate the vessel traffic flow changes caused by the conflict by using the route distance to replace the shipping costs and quantify the cost increase for the relevant countries caused by the vessel detour based on the shipping cost increment index. The research results show that after the outbreak of the conflict, the number of vessels passing through the Red Sea area has decreased significantly. About 3.1% of global vessels were affected, with global sea transportation costs of large tankers increasing by about 0.0825%. This study takes the Israeli–Palestinian conflict as an example and analyzes the impact of emergencies on the global sea transportation situation of tankers based on AIS data. The research results reveal the characteristics of international shipping to a certain extent and provide guidance for global sea transportation route planning.

Identification and characterization of Alternaria spp. causing leaf blotch on Salix matsudana: A study from Rudong city, China - Yi-Lin Chen; Bing-Yao Peng; Yu Wan; De-Wei Li; Li-Hua Zhu (Crop Protection, 2025)

Investigating wet-bulb globe temperature on heat-related illness in general population for alerting heat exposure: A time-stratified case-crossover study - Yi-Chun Lin; Chau-Ren Jung; Bing-Fang Hwang; Chen-Peng Chen (Urban Climate, 2025)

AIS data-driven analysis for identifying cargo handling events in international trade tankers - Ran Zhang; Daozhu Dong; Xiaohui Chen; Bing Zhang; Yixuan Zhang; Lin Ye; Bing Liu; Ying Zhao; Chunyan Peng (Ocean Engineering, 2025)

Moxifloxacin plus Cordyceps polysaccharide ameliorate intestinal barrier damage due to abdominal infection via anti-inflammation and immune regulation under simulated microgravity - Hong-Yun Nie; Jun Ge; Kai-Ge Liu; Yuan Yue; Hao Li; Hai-Guan Lin; Tao Zhang; Hong-Feng Yan; Bing-Xin Xu; Hong-Wei Sun; Jian-Wu Yang; Shao-Yan Si; et al. (Life Sciences in Space Research, 2025)

Bio-electroreduction of CO2 to acetate: Impact of the inorganic carbon feeding regime on microbial electrosynthesis - Jin Du; Hebin Liang; Bohua Wen; Bing Li; Xiao-yan Li; Lin Lin (Journal of Water Process Engineering, 2025)

Enhanced electron transport through hydrogen bonds and Ag nanoparticles in the PCN-222/Ag/COF core–shell photocatalyst for efficient oxytetracycline degradation - Bing-Bing Lu; Jia-Chang Lu; Qing-Yun Zhao; Rui Wang; Ze-Lin Chen; Ji-Qiang Guan; Hao Liu; Ying Fu; Fei Ye (Journal of Cleaner Production, 2025)

Surfactant-free W/O high internal phase emulsions co-stabilized by beeswax and phytosterol crystal scaffold: A promising fat mimetic with enhanced mechanical and mouthfeel properties - Ying Song; Xia Zhang; Jiarong Li; Rixin Zhang; Bing Li; Lin Li (Food Research International, 2025)

Cell-free hemoglobin released from hemolysis induces programmed cell death through iron overload and oxidative stress in grass carp (Ctenopharyngodon idella) - Jialing Song; Ningjing Li; Yan Yang; Bing Chen; Jiaxiang Hu; Ye Tian; Li Lin; Zhendong Qin (Fish & Shellfish Immunology, 2025)

Hemolysis-associated release of hemoglobin induces mitochondrial oxidative phosphorylation (OXPHOS) disturbance and aggravates cell oxidative damage in grass carp (Ctenopharyngodon idella) - Yan Yang; Ningjing Li; Jialing Song; Ye Tian; Bing Chen; Jiangtao Li; Li Lin; Zhendong Qin (Fish & Shellfish Immunology, 2025)

MEHP induced mitochondrial damage by promoting ROS production in CIK cells, leading to apoptosis, autophagy, cell cycle arrest - Lu Li; Wan Li; Yufeng Liu; Bing Han; Yanbo Yu; Hongjin Lin (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2025)

Hard-soft-acid-base engineering of Bi-MOFs for enhanced selective extraction of phosphate - Bing Lu; Yuan Yao; Gang Wang; Shuangshi Dong; Lin Zhao; Shiyong Wang (Chemical Engineering Journal, 2025)

Design and biomedical application of Cr3+-doped gallate near-infrared persistent luminescence nanoprobes - Jie Gao; Lin Yuan; Yu Min; Mengyu Cao; Hetong Zhu; Jiaqi Hong; Bing Yu; Hailin Cong (Chemical Engineering Journal, 2025)

Role of MFN2 in bovine embryonic development and the mitigation of ER stress - Shu-Ming Shi; Bing Hu; Zhi-Chao Chi; Lin-Yi Qu; Li-Ying Liu; Yu-Yan He; Guan-Lin Jia; Jing-Hang Li; Ilkeun Kong; Yong-Xun Jin; Xian-Feng Yu (Animal Reproduction Science, 2025)

Phosphomolybdic acid boosts polyunsaturated fatty acid and neutral lipid production in Phaeodactylum tricornutum - Kun-Tao Peng; Bing-Hong Xiong; Gao Cheng; Yuan-Hong Zhong; Lin Yu (Frontiers in Marine Science, 2025)
Phaeodactylum tricornutum is considered a potential lipid production platform due to its high growth rates and elevated natural neutral lipid and polyunsaturated fatty acid (PUFA) contents. Furthermore, microalgae are emerging as promising sources of docosahexaenoic acid (DHA) and eicosapentaenoic acid (EPA). In this study, phosphomolybdic acid (PMo 12 ), as a photocatalyst, can enhance the synthesis of neutral lipids and PUFAs by influencing the expression of lipid metabolism-related genes and photosynthesis in P. tricornutum. We also observed the contents of EPA and PUFA in engineered microalgae nearly doubled compared to the wild type, while neutral lipid content showed a significant increase of 69.7% in engineered microalgae. Notably, the growth rate of engineered microalgae remained comparable to that of the wild type. This work presents an effective approach to enhance the production of microalgal bioproducts, suggesting that photocatalysts such as PMo 12 could serve as viable alternatives to genetic engineering technology, facilitating the commercialization of microalgal biodiesel.

Foodborne iron overload induces oxidative stress and causes mitochondrial damage in the liver of grass carp (Ctenopharyngodon idellus) - Xiaoman Huang; Yan Yang; Yanhan Bai; Shiyi Yang; Bing Chen; Linpeng Zhang; Lihan Liu; Junjie Tao; Chengming Tu; Li Lin; Zhendong Qin (Aquaculture, 2025)

Efficient removal of levofloxacin by FeCo2O4@C-REC activated peroxymonosulfate: Performance and mechanism - Bai-Hang Zhao; Bao-Yu Zhang; Bing-Lin Zhang; Jing Zhang; Chun Wang; Ye Li (Journal of Water Process Engineering, 2025)

pH-dependent medium-chain fatty acid synthesis in waste activated sludge fermentation: Metabolic pathway regulation - Yun Wang; Shu-Lin Wu; Wei Wei; Lan Wu; Sansi Huang; Xiaohu Dai; Bing-Jie Ni (Journal of Environmental Management, 2025)

Effect of excitation voltage in a magnetically induced electric field on the physicochemical, structural and functional properties of citrus pectin - Ya-Hui Yu; Xiaozhen Liu; Luo-Bang Wu; Xiangying Yu; Ming-Yu Jin; Long-Qing Li; Fengyuan Liu; Yuting Li; Lin Li; Bing Li; Jing-Kun Yan (Food Chemistry, 2025)

3,5-Dicaffeoylquinic acid promotes intestinal urate excretion via the MAPK signaling pathway based on Caco-2 Cell model - Jiajing Liao; Jin Qian; Lijuan Rao; Suqin Lin; Chen Wang; Linqian Xu; Bing Yuan; Jiayi Yuan; Yin Wan; Guiming Fu (Food Bioscience, 2025)

An assessment of the levels of emerging and traditional organophosphate ester flame retardants in dairy products in China and their combined dietary risks - Ruize Zhou; Jianqiang Geng; Jie Jiang; Bing Shao; Li Lin; Baolong Wang; Yantao Wu; Wei Li (Food and Chemical Toxicology, 2025)

Bilayer oriented nanofiber membrane for enhancing response deformation and stability of humidity-responsive actuator - Zhongqiu Cheng; Yiyang Hua; Desuo Zhang; Mengxuan Wang; Xin Ge; Yaxinru Shen; Bing Zhao; Ning Qi; Hong Lin (Chemical Engineering Journal, 2025)

Harnessing metal-metal interactions for simultaneously boosting photocatalytic hydrogen and benzaldehyde production - Yajie Feng; Chi Lin; Yifei Huang; Bing Li; Yingxin He; Jiangping Ma; Chaogang Ban; Lujie Ruan; Hongxing Jia; Xiaoping Tao; Liyong Gan; Xiaoyuan Zhou (Chemical Engineering Journal, 2025)

Chronic polyaluminum chloride perturbation shaped community assembly patterns: An overlooked mechanism of nitrogen removal inhibition - Nan-ping Wu; Qian Zhang; Hong-yu Wang; Yun-jie Zhang; Meng Li; Bin Ji; Yufei Bao; Bing Lin; Yu-wei Ding; Qi He; Jia-jing Chen (Chemical Engineering Journal, 2025)

Harnessing diurnal dynamics: Understanding the influence of light–dark cycle on algal-bacterial symbiotic system under aniline stress - Qi He; Qian Zhang; Meng Li; Jing He; Bing Lin; Nan-Ping Wu; Jia-Jing Chen; Xun-Hao Liu; Xiao-Qian Dong (Bioresource Technology, 2025)

Developing filamentous fungal chassis for natural product production - Jie Fan; Peng-Lin Wei; Yuanyuan Li; Shengquan Zhang; Zedong Ren; Wei Li; Wen-Bing Yin (Bioresource Technology, 2025)

Two novel butyrolactone lignan dimers from leaves of Castanopsis chinensis and their anti-inflammatory activities - Ya-Feng Wang; Ping Lin; Nao Pang; Zhang-Bin Liu; Bing-Yuan Yang; Rui-Jie He; Yong-Lin Huang (Journal of Natural Medicines, 2025)

Vessel Type Recognition Using a Multi-Graph Fusion Method Integrating Vessel Trajectory Sequence and Dependency Relations - Lin Ye; Xiaohui Chen; Haiyan Liu; Ran Zhang; Bing Zhang; Yunpeng Zhao; Dewei Zhou (Journal of Marine Science and Engineering, 2024)
In the field of research into vessel type recognition utilizing trajectory data, researchers have primarily concentrated on developing models based on trajectory sequences to extract the relevant information. However, this approach often overlooks the crucial significance of the spatial dependency relationships among trajectory points, posing challenges for comprehensively capturing the intricate features of vessel travel patterns. To address this limitation, our study introduces a novel multi-graph fusion representation method that integrates both trajectory sequences and dependency relationships to optimize the task of vessel type recognition. The proposed method initially extracts the spatiotemporal features and behavioral semantic features from vessel trajectories. By utilizing these behavioral semantic features, the key nodes within the trajectory that exhibit dependencies are identified. Subsequently, graph structures are constructed to represent the intricate dependencies between these nodes and the sequences of trajectory points. These graph structures are then processed through graph convolutional networks (GCNs), which integrate various sources of information within the graphs to obtain behavioral representations of vessel trajectories. Finally, these representations are applied to the task of vessel type recognition for experimental validation. The experimental results indicate that this method significantly enhances vessel type recognition performance when compared to other baseline methods. Additionally, ablation experiments have been conducted to validate the effectiveness of each component of the method. This innovative approach not only delves deeply into the behavioral representations of vessel trajectories but also contributes to advancements in intelligent water traffic control.

Effects of hypoxia and reoxygenation on energy metabolism, immune response, and apoptosis in orange-spotted grouper (Epinephelus coioides) - Yuxin Wu; Yiran Lin; Bing Lin; Yukun Huang; Zhide Yu; Yonghao Ma; Yuwei Feng; Qiaoyi Chen; Along Gao; Hu Shu (Frontiers in Marine Science, 2024)
Hypoxia is an unfavorable environmental condition that produces diverse negative effects in fish. High-density cultures of Epinephelus coioides are more likely to experience hypoxic conditions than those in natural environments. To assess the effects of hypoxia on E. coioides , we examined the related enzyme activities and gene expression after 48 h of hypoxia and 24 h of dissolved oxygen (DO) recovery. Under hypoxic stress (DO: 1.2 ± 0.1 mg/L), the energy supply mode of fish changed from aerobic metabolism to anaerobic metabolism, and the serum glucose content and lactate dehydrogenase activity were significantly upregulated. Total protein, hepatic glycogen, and two key regulatory enzymes (i.e., hexokinase and pyruvate kinase) were differentially expressed in the liver, and mRNA expression of three genes (i.e., LDHA , GLUT1 , and MCT2 ) also showed a high expression trend. In serum, three immune-related enzymes (i.e., alanine aminotransferase, aspartate aminotransferase, and alkaline phosphatase) were found to be involved in regulation by hypoxia and showed different levels of changing patterns. Expression of inflammatory genes (i.e., IL-8 , IFNγ , MyD88 , and NF-kB ) were significantly regulated in liver. With prolongation of hypoxic stress, high expression of apoptotic genes (i.e., p53 , Bax , Bcl-2 , and Caspase-9 ) was closely related to the degree of apoptosis in the liver. Our investigation of the changes in energy metabolism, immune response, and apoptosis of E. coioides under hypoxia and reoxygenation (DO, 6.0 ± 0.1 mg/L) provides a theoretical bases for healthy aquaculture and selection of varieties with tolerance to hypoxia.

Experimental Study of Submarine Pipeline with Geotextile and Stone Cover Protection Under the Superposition of Waves and Currents - Wenqi Si; Mingqing Wang; Yaru Gao; Ke Sun; Bing Chen; Risheng Wang; Lin Cui; Dong-Sheng Jeng; Hongyi Zhao (Journal of Marine Science and Engineering, 2024)
Submarine pipelines are the main transport carriers of marine resources. In order to protect these pipelines, geotextile and stone covering measures are adopted in this paper and the protective effect is studied. A sequence of physical model tests was conducted to carry out the research. The hydrodynamic characteristics and seabed oscillation response of the seabed surrounding the pipeline were analyzed with or without geotextile and stone cover protection, and it was found that they were affected by waves (and currents). The experimental results show the following: (1) comparing the regular wave and current with the regular wave alone, it is found that forward current promotes wave propagation and reverse current inhibits wave propagation; (2) the protective effect of geotextile and stone covering measures on different positions of the pipeline (the front, the bottom, and the back of the pipe) is basically same; (3) in the case of waves with large wave heights and long wave periods superimposed with ocean currents, the protective effect of geotextile and stone coverings on the hydrodynamic and seabed pore pressure around the pipeline is more significant.

Submerge-emerge alternation promotes sediment per- and polyfluoroalkyl substance (PFAS) release and bioaccumulation - Ye-bing Shi; Zu-lin Hua; Xiao-qing Li; Song-he Zhang; Jian-long Liu (Science of The Total Environment, 2024)

New insights into the stages of cadmium remediation in ryegrass enhanced by kitchen compost-derived dissolved organic matter: Activation, absorption, and storage - Bing Kou; Lin Huo; Minyi Cao; Kunlong Hui; Wenbing Tan; Ying Yuan; Yu Jiang (Science of The Total Environment, 2024)

Outdoor light at night is a modifiable environmental factor for metabolic syndrome: The 33 Communities Chinese Health Study (33CCHS) - Li-Wen Hu; Yan-Chen Gong; Hong-Xing Zou; Le-Bing Wang; Yanan Sun; Alejandro Godinez; Han-Yu Yang; Si-Han Wu; Shuo Zhang; Wen-Zhong Huang; Zhao-Huan Gui; Li-Zi Lin; et al. (Science of The Total Environment, 2024)

Numerical examination of wave forces on partially submerged horizontal circular cylinders near free surface - Hong-Fei Mao; Yuan-Ting Yang; Jin-Bo Lin; Zhong-Bing Zhou; Ming He (Ocean Engineering, 2024)

A novel collaborative collision avoidance decision method for multi-ship encounters in complex waterways - Han Dong; Rong Zhen; Qiyong Gu; Zhong Lin; Jiuhu Chen; Kai Yan; Bing Chen (Ocean Engineering, 2024)

A TT1–SCE1 module integrates ubiquitination and SUMOylation to regulate heat tolerance in rice - Hong-Xiao Yu; Ying-Jie Cao; Yi-Bing Yang; Jun-Xiang Shan; Wang-Wei Ye; Nai-Qian Dong; Yi Kan; Huai-Yu Zhao; Zi-Qi Lu; Shuang-Qin Guo; Jie-Jie Lei; Ben Liao; et al. (Molecular Plant, 2024)

Exploring the impact of visible light intensity on algae-bacterial symbiotic system treating aniline wastewater: Performance, microbial community and metabolic pathways - Jiajing Chen; Qian Zhang; Meng Li; Jing He; Bing Lin; Nanping Wu; Xunhao Liu; Siwei Li; Jialong Huang; Xiaoqian Dong; Hongyu Wang (Journal of Water Process Engineering, 2024)

Phosphorus deficiency promotes root:shoot ratio and carbon accumulation via modulating sucrose utilization in maize - Zu-Dong Xiao; Zhen-Yuan Chen; Yi-Hsuan Lin; Xiao-Gui Liang; Xin Wang; Shou-Bing Huang; Sebastian Munz; Simone Graeff-Hönninger; Si Shen; Shun-Li Zhou (Journal of Plant Physiology, 2024)

m6A RNA methyltransferase METTL16 induces Cr(VI) carcinogenesis and lung cancer development through glutamine biosynthesis and GLUL expression - Yun-Xia Xie; Lin Wang; Zhi-Hao Zhou; Wen-Jing Liu; Wei Wang; Jing-Hua Yang; Ming-Liang He; Jian-Ge Qiu; Bing-Hua Jiang (Journal of Hazardous Materials, 2024)

Unveiling the release mechanism of potentially toxic elements from Pb/Zn smelter contaminated soils under the coupled effects of freeze–thaw and acidification: Insights from mineralogical analysis - Da–Mao Xu; Bai–Hong An; Shao–Jun Jiang; Dong–Sheng Dai; Ze–Lin Xu; Lai Zhou; Xue–Qiang Zhu; Hong Yang; Rong–Bing Fu (Journal of Hazardous Materials, 2024)

Hidden deposit exploration using the tectono-geochemistry method in the western Xicheng ore field, China - Zhizhong Cheng; Qiang Wang; Junchen Liu; Zhenshan Pang; Tingjie Yan; Zezhong Du; Mingming Bing; Huixiang Yuan; Chenggui Lin (Journal of Geochemical Exploration, 2024)

Efficient degradation of chloroquine via pyrite-modified electro-Fenton yielding •OH and O2•- - Yuehua Zhang; Yinghui Lin; Yuanji Shi; Linyan Yang; Bing-Jie Ni; Xueming Chen (Journal of Cleaner Production, 2024)

The key role of Sn in enhancing Rh recovery from spent automotive catalysts - Xiaoyun Jia; Duchao Zhang; Yongmi Wang; Tingying Li; Bing Fan; Lin Chen; Weifeng Liu (Journal of Environmental Chemical Engineering, 2024)

Parathyroid hormone mediates the adverse impact of air pollution exposure on serum 25-hydroxyvitamin D: A nationwide cross-sectional study in China - Haitao Zhang; Jing Wang; Xia Meng; Bing Shu; Chunchun Yuan; Xingwen Xie; Zhangyu Liao; Xiaobing Jiang; Bolai Chen; Xinchao Lin; Xu Wei; Xiangyang Leng; et al. (Environmental Research, 2024)

High-valent iron–oxo species in heterogeneous catalysis: Formation, mechanism, and reactivity for the degradation of various emerging organic contaminants - Yin Li; Jiahui Hu; Yutian Bao; Yanan Xiao; Lin Lin; Bing Li; Xiao-yan Li (Chemical Engineering Journal, 2024)

Exploring the link between metformin use and adhesive capsulitis of the shoulder: a retrospective cohort study in Taiwan - Bing-Sian Lin; Wu-Chien Chien; Chieh-Hua Lu; Chi-Hsiang Chung; Chang-Huei Tsao; Tzu-Hsuan Weng; Ching-Yueh Lin (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

Lymph nodes in oral squamous cell carcinoma: a comprehensive anatomical perspective - Guang-Rui Wang; Nian-Nian Zhong; Lei-Ming Cao; Xuan-Hao Liu; Zi-Zhan Li; Yao Xiao; Kan Zhou; Yi-Fu Yu; Bing Liu; Lin-Lin Bu (Clinical & Experimental Metastasis, 2024)

Set-pMAE: spatial-spEctral-temporal based parallel masked autoEncoder for EEG emotion recognition - Chenyu Pan; Huimin Lu; Chenglin Lin; Zeyi Zhong; Bing Liu (Cognitive Neurodynamics, 2024)

Analysis of deliquescent chloride salt by laser-induced breakdown spectroscopy with controlled uniform precipitation - Lizhu Kang; Ji Chen; Zhijie Huang; Zhanjian Lin; Rui Zhang; Bing Lu; Xiangyou Li (Analytica Chimica Acta, 2024)

Jeotgalibacillus haloalkalitolerans sp. nov., a novel alkalitolerant and halotolerant bacterium, isolated from the confluence of the Fenhe River and the Yellow River - Ya-Fei Zhang; Yun-Lin Peng; Yong-Hui Xiao; Bing Yu; Ming-Yue Cao; Zhi-Ling Zhang; Le-Qun Huang; Yi Li (Antonie van Leeuwenhoek, 2024)

Devosia lacusdianchii sp. nov., an attached bacterium inhibited by metabolites from its symbiotic Microcystis - Qing-Lin Deng; Yao Xiao; Ru Jia; Xin Xie; Le Wang; Xin Wang; Jian-Yuan Yang; Qi-Gen Guo; Bing-Huo Zhang (Antonie van Leeuwenhoek, 2024)

The Temperature-Dependent Monotonic Mechanical Characteristics of Marine Sand–Geomembrane Interfaces - Zhiming Chao; Hongyi Zhao; Hui Liu; Peng Cui; Danda Shi; Hai Lin; Yang Lu; Bing Han; Shuang Chen (Journal of Marine Science and Engineering, 2024)
The utilization of geomembrane reinforcement technology is pervasive in marine sand foundation reinforcement projects. However, the elevated temperatures and intricate stress conditions prevalent in marine environments exert a notable influence on the mechanical characteristics of geomembrane interfaces comprising marine sand, which impedes the efficacy of geomembrane reinforcement in marine sand foundations. Nevertheless, there is a lack of research investigating the temperature-dependent interfacial mechanical performance of geomembranes and marine sand under diverse stress states. In this study, a series of monotonic shear tests were carried out on the interface between geomembranes and marine sand within a temperature range of 5 °C to 80 °C. These experiments were carried out using a self-developed large-scale temperature-controlled interfacial dynamic and static shear device. The experimental results demonstrate that temperature has a pronounced effect on the monotonic mechanical characteristics of the geomembrane–marine sand interface, which displays clear temperature dependence. The findings of this study may help in the design and optimization of offshore projects where a marine sand–polymer layer interface exists.

DGT and kinetic analyses differentiate Se and Cd bioavailability in naturally enriched paddy soils - Chao Zhang; Dong-Xing Guan; Paul N. Williams; Guo-Bing Lin; Xiao-Lei Chen; Lena Q. Ma (Chemosphere, 2024)

On the FT-ICR mass spectrometry analysis of dissolved organic matter released by adsorbent during coal chemical wastewater treatment - Qi Wei; Cai Chen; Hong-Peng Ma; Tao Liu; Bing Liu; Tian-Xiang Wang; Sen Zhang; Dan-Hui Yang; Wen-Jie Lv; Hua-Lin Wang (Science of The Total Environment, 2024)

Predicting rice phenology across China by integrating crop phenology model and machine learning - Jinhan Zhang; Xiaomao Lin; Chongya Jiang; Xuntao Hu; Bing Liu; Leilei Liu; Liujun Xiao; Yan Zhu; Weixing Cao; Liang Tang (Science of The Total Environment, 2024)

Burden of biliary tract carcinoma in China (1990–2021): Findings from the 2021 Global Burden of Disease Study - Wei Zhang; Yi-Jun Wang; Jiang-Mei Liu; Xu-Heng Sun; Yan Jiang; Fang Shen; Li-Juan Shen; Jing Xiang; Jun-Feng Zhang; Lin-Hua Yang; Wen-Guang Wu; Tao Chen; et al. (Science Bulletin, 2024)

An adaptive trajectory segmentation and simplification algorithm based on vessel behavioral features - Lin Ye; Xiaohui Chen; Ran Zhang; Bing Zhang; Haiyan Liu (Ocean Engineering, 2024)

Synthesis of hydrothermal carbonation carbon with tunable photocatalytic performance for trimethoprim degradation using an ethanol-water co-solvent strategy: Influence of ethanol concentration - Jiashuai Hu; Jie Chen; Xiaoling Liu; Jie Liang; Ke Zhang; Bing Jiang; Hongbing Luo; Lin Li; Xiaochan An; Xiaobing Chen; Xiaojun Chen; Wei Chen; et al. (Journal of Cleaner Production, 2024)

Insights into the critical roles of water-soluble organic matter and humic acid within kitchen compost in influencing cadmium bioavailability - Bing Kou; Lin Huo; Minyi Cao; Yuxin Ke; Lei Wang; Wenbing Tan; Ying Yuan; Xiaoli Zhu (Journal of Environmental Management, 2024)

Applying kitchen compost promoted soil chrysene degradation by optimizing microbial community structure - Bing Kou; Lin Huo; Minyi Cao; Tingqiao Yu; Yuman Wu; Kunlong Hui; Wenbing Tan; Ying Yuan; Xiaoli Zhu (Journal of Environmental Management, 2024)

Tailoring stability in oil-in-water high internal phase Pickering emulsions (HIPPEs) through surface modification of beeswax-based solid lipid particles (SLPs) with various surfactants - Rixin Zhang; Bing Li; Ying Song; Lin Li; Xia Zhang (Food Hydrocolloids, 2024)

Perfluorooctane sulfonate (PFOS) and benzo[a]pyrene (BaP) synergistically induce neurotoxicity in C6 rat glioma cells via the activation of neurotransmitter and Cyp1a1-mediated steroid hormone synthesis pathways - Yu-Shun Lu; Ju Chen; Xiao-Rong He; Shang-Lin Yang; Bing-Jie Ma; Jiang Yu; Jing Qiu; Yong-Zhong Qian; Yan-Yang Xu (Food and Chemical Toxicology, 2024)

Ultra-Low-Dose UV-C Photo-stimulation Promotes Neural Stem Cells Differentiation via Presenilin 1 Mediated Notch and β-Catenin Activation - Lin Zhou; Zihan Wang; Qiuling Zhong; Bing Song; Yan Wang; Teng Guan; Qian Liu (Molecular Neurobiology, 2024)

A preliminary study of T-2 toxin that cause liver injury in rats via the NF-kB and NLRP3-mediated pyroptosis pathway - Shicong Zheng; Haonan Li; Hexuan Dong; Fang Qi; Bing Zhang; Qian Yu; Buyi Lin; Hong Jiang; Haoyu Du; Ying Liu; Jun Yu (Toxicon, 2024)

Early Cretaceous fayalite-, ferrosilite-, and biotite-bearing rhyolitic porphyries in the Baishuizhai area, South China: Formation by fractional crystallization in the shallow crust - Xiao Liu; Qiang Wang; Xi-Jun Liu; Lin Ma; Derek A. Wyman; Gong-Jian Tang; Wei Dan; Zi-Qi Jiang; Hao Wu; Wan-Long Hu; Jin-Heng Liu; Chuan-Bing Xu; et al. (Lithos, 2024)

Efficient degradation and mineralization of polyethylene terephthalate microplastics by the synergy of sulfate and hydroxyl radicals in a heterogeneous electro-Fenton-activated persulfate oxidation system - Yinghui Lin; Yuehua Zhang; Yonghao Wang; Yuancai Lv; Linyan Yang; Zhijie Chen; Bing-Jie Ni; Xueming Chen (Journal of Hazardous Materials, 2024)

Malachite green and related substances in environmental samples: Updates on pretreatment and analysis methods - Zu-Yi Chen; Bing-lin He; Yu Bian; Yuan Zhang; Xue-song Feng (Journal of Environmental Chemical Engineering, 2024)

κ-Carrageenan masking bitterness perception in surimi gels containing potassium chloride-based salt substitutes: Gel properties, oral processing, and sensory evaluation - Ni He; Xinran Chen; Lin Li; Shaoyun Wang; Meijuan Lan; Yi Yuan; Zhenhui Zhang; Tongshuai Li; Xia Zhang; Xing He; Bing Li (Food Chemistry, 2024)

Reducing target reliability index of concrete bridge beams through compression yielding - Lin Feng; Yu-Fei Wu; Bing-Cheng Guo; Xiao-Xu Huang (Engineering Structures, 2024)

Achieving over 42 % indoor efficiency in wide-bandgap perovskite solar cells through optimized interfacial passivation and carrier transport - Zhong-En Shi; Ta-Hung Cheng; Chien-Yu Lung; Chi-Wei Lin; Chih-Lin Wang; Bing-Huang Jiang; Yu-Sheng Hsiao; Chih-Ping Chen (Chemical Engineering Journal, 2024)

Construction of negative electrostatic sugared gourd pore within nickel-based metal-organic framework for one-step purification acetylene from ethylene and carbon dioxide mixture - Xing-Zhe Guo; Bing Lin; Guang-Zu Xiong; Rajamani Krishna; Zhao-Rong Zhang; Qing-Zan Liu; Zhi-Xiong Zhang; Liming Fan; Jie Zhang; Bingwen Li (Chemical Engineering Journal, 2024)

Benzo-12-crown-4 and β-diketone bi-functionalized ionic liquids for highly selective lithium extraction from alkaline solution - Shen Wang; Meng Rong; Lin-Bing Sun; Yunze Zhao; Huifang Xing; Liangrong Yang (Chemical Engineering Journal, 2024)

Post-Conflict Behaviors of Wild Gelada Monkeys (Theropithecus gelada) at Guassa, Ethiopia - Triana I. Hohn; Bing Lin; Carrie M. Miller; Iris R. Foxfoot; Vivek V. Venkataraman; Kathreen E. Ruckstuhl; Nga Nguyen; Peter J. Fashing (International Journal of Primatology, 2024)

Experimental Study of the Random Wave-Induced Hydrodynamics and Soil Response in a Porous Seabed Around Double Piles - Mingqing Wang; Wenqi Si; Yaru Gao; Lin Cui; Dong-Sheng Jeng; Ke Sun; Bing Chen; Hongyi Zhao (Journal of Marine Science and Engineering, 2024)
The evaluation of the wave-induced pore pressures around the offshore piles has attracted great attentions among coastal engineers, because they have been commonly used as foundations of numerous marine infrastructures. This paper presents comparative studies of the random wave-induced transient seabed response around single and double piles in a sandy seabed through a series of wave flume experiments. The influences of relative spacing ratios, wave incidence angles, and front pile diameters under different random wave parameters on oscillatory pore pressures in the vicinity of double piles are examined. In addition, variations in wave profiles and dynamic wave pressures surrounding single and double piles are quantitatively analyzed. Based on the experimental results, the following conclusions can be drawn: (1) under the influence of random waves, the wave profiles around the double piles exhibit obvious irregularity and nonlinearity; (2) the shielding effect existing in the tandem piles results in lower dynamic wave pressures around the rear pile compared to the front pile; (3) the pore pressures on the front surface of the double piles decrease with increasing soil depth, with a decreasing attenuation rate at each layer; (4) when the relative spacing ratio G/D2=3, the group-pile effect weakens, leading to an increase in the pore pressures around the rear pile, approaching the results of a single pile under conditions of lower significant wave heights or periods; (5) the intense disturbance effect caused by large wave incidence angles exacerbates the pore pressure response around the double piles; (6) when the diameter of the front pile in the tandem piles increases, it enhances the shielding effect, thus suppressing the seabed response around the rear pile. In contrast, it causes an increase in the wave surface around the double piles, exacerbating the pore pressure response in the seabed. The latter effect becomes more pronounced when the significant wave height is larger.

Urban mangroves at risk: Understanding organophosphate flame retardant pollution at different urban function zones in shenzhen - Wenjun Zhao; Bing Li; Ruili Li; Xiaofeng Wu; Guanghui Lin; Yuefei Huang (Ocean & Coastal Management, 2024)

First identification of Carboniferous mafic dikes during a period of arc magmatic quiescence in the Northern Qiangtang terrane, central Tibet: Back-arc extension and implications for opening of the Xijir Ulan Ocean - Zhi-Wei Yu; Wei Dan; Qiang Wang; Xiu-Zheng Zhang; Jun Wang; Bing Chen; Lin Gong (Lithos, 2024)

Integrated membrane process of tubular ultrafiltration-nanofiltration-electrodialysis-reverse osmosis for treating fracturing flowback fluid - Bing Xu; Qian Zhang; Huanhuan Wu; Qianqian Tian; Wenming Chai; Ming Zhang; Guangyi Shao; Shuwen Tian; Yakai Lin; Hong Yao (Journal of Cleaner Production, 2024)

Zirconium isotope tracing of the magmatic-hydrothermal transition - Er-Lin Zhu; Qiong-Xia Xia; Shao-Bing Zhang; James Van Orman; Ren-Xu Chen; Zhao-Ya Li; Peng Gao (Geochimica et Cosmochimica Acta, 2024)

Investigating the impact of ultrasound on the structural, physicochemical, and emulsifying characteristics of Dioscorin: Insights from experimental data and molecular dynamics simulation - Qi Gao; Yu-qi Yang; Hao-nan Nie; Bing-qing Wang; Xue Peng; Ning Wang; Jiang-kuo Li; Jia-jia Rao; You-lin Xue (Food Chemistry, 2024)

Association between outdoor light at night exposure and executive function in Chinese children - Han-Yu Yang; Si-Han Wu; Shuo Zhang; Hong-Xing Zou; Le-Bing Wang; Li-Zi Lin; Zhao-Huan Gui; Xiao-Wen Zeng; Bo-Yi Yang; Ru-Qing Liu; Guang-Hui Dong; Li-Wen Hu (Environmental Research, 2024)

Experimental study of high-mode buckling behavior of flat steel core in a buckling-restrained brace - Pao-Chun Lin; Chih-Wei Chang; Bing-Cheng Wu (Engineering Structures, 2024)

Insight into response mechanism of aerobic granular sludge to combined nanoparticle stress: Nitrogen removal, microbial community and heavy metal resistance genes - Yu-Qi Li; Bai-Hang Zhao; Yu-Qing Zhang; Hai-Shan Yang; Bing-Lin Zhang (Chemical Engineering Journal, 2024)

Engineering Au-Pt atomic alloy cocatalysts for enhanced H2 production from photo-reforming of lignocellulosic biomass wastes - Fangjie Ding; Hongbo Yu; Renyong Tu; Sha Li; Lin Chen; Bing Li; Jianzhong Guo; Chunzheng Wu (Chemical Engineering Journal, 2024)

CO2-to-HCOOH electrolysis on intercalation-engineered bismuth-oxybromide with self-renewing hydroxyls - Bing Yang; Donglin Shi; Yulu Zhang; Lin Meng; Jintao Guo; Shilun Wang; Yao Shen; Liang Chen; Youju Huang (Chemical Engineering Journal, 2024)

A Bi-MOF-based composite sponge equipped with antibacterial heterogeneous membranes for effective phosphate removal from wastewater - Bing Lu; Gang Wang; Lin Zhao; Shiyong Wang; Shuangshi Dong (Chemical Engineering Journal, 2024)

Boosting photoelectron transfer by Fermi and doping levels regulation in carbon nitride towards efficient solar-driven hydrogen production - Shangcong Sun; Bo Peng; Ye Song; Bing Liu; Haitao Song; Wei Lin (Chemical Engineering Journal, 2024)

Corrigendum to “Ionic-confining-assisted multiple-mode tunable light emitting of carbon nanodots” [Chem. Eng. J. 486 (2024) 150196] - Jing-Nan Hao; Zhong-Zheng Ding; Cheng-Long Shen; Guang-Song Zheng; Jia-Lu Liu; Ruo-Bing Li; Run-Wei Song; Kai-Kai Liu; Jin-Hao Zang; Lin Dong; Qing Lou; Chong-Xin Shan (Chemical Engineering Journal, 2024)

Convergent Neuroimaging and Molecular Signatures in Mild Cognitive Impairment and Alzheimer’s Disease: A Data-Driven Meta-Analysis with N = 3,118 - Xiaopeng Kang; Dawei Wang; Jiaji Lin; Hongxiang Yao; Kun Zhao; Chengyuan Song; Pindong Chen; Yida Qu; Hongwei Yang; Zengqiang Zhang; Bo Zhou; Tong Han; et al. (Neuroscience Bulletin, 2024)
The current study aimed to evaluate the susceptibility to regional brain atrophy and its biological mechanism in Alzheimer’s disease (AD). We conducted data-driven meta-analyses to combine 3,118 structural magnetic resonance images from three datasets to obtain robust atrophy patterns. Then we introduced a set of radiogenomic analyses to investigate the biological basis of the atrophy patterns in AD. Our results showed that the hippocampus and amygdala exhibit the most severe atrophy, followed by the temporal, frontal, and occipital lobes in mild cognitive impairment (MCI) and AD. The extent of atrophy in MCI was less severe than that in AD. A series of biological processes related to the glutamate signaling pathway, cellular stress response, and synapse structure and function were investigated through gene set enrichment analysis. Our study contributes to understanding the manifestations of atrophy and a deeper understanding of the pathophysiological processes that contribute to atrophy, providing new insight for further clinical research on AD.

Age-related alterations in vortex veins on indocyanine green angiography - Chen-Xi Cai; Shan-Shan Yu; Xiao-Mei Xiong; Bing-Qian Liu; Zhen-Qiang Lin; Qiang Wang; Jin-Li Cui; Ze-Hao Liu; Tao Li; Lin Lu; Ying Lin (GeroScience, 2024)
To determine age-related alterations in vortex veins in healthy subjects. A total of 228 healthy subjects (aged 4 to 86 years) were recruited and divided into four groups (G1, <21 years; G2, 21–40 years; G3, 41–60 years; and G4, 61–86 years). The clinical characteristics of the participants were recorded, and parameters including the number of vortex vein roots (NVVR), the central vortex vein diameter (CVVD), the mean root area of the vortex vein (MRAVV), and the weighted mean of the thickest branch diameter (WMTBD) were obtained by marking the vortex veins on indocyanine green angiography (ICGA). The NVVR in the age group over 60 years old was significantly lower than that in other age groups ( P < 0.05). The CVVD, MRAVV, and WMTBD of all age groups increased with increasing age ( P < 0.05). The NVVR was unevenly distributed among the quadrants ( P < 0.001). The proportions of type four vortex veins (complete systems including ampulla) and anastomotic branches of the vortex veins were significantly increased in elderly participants over 50 years of age ( P < 0.05). Subfoveal choroidal thickness was significantly correlated with age, NVVR, CVVD and MRAVV ( P < 0.05). This is the first study to reveal age-related alterations in vortex veins on ICGA in a healthy population. Aging may lead to partial vortex occlusion and residual vortex dilation. As age increases, anastomotic branches increasingly appear between the originally independent vortex veins. Translational relevance: Aging may lead to partial vortex occlusion and residual vortex dilation.

Unraveling the mechanisms and responses of aniline-degrading biosystem to salinity stress in high temperature condition: Pollutants removal performance and microbial community - Qi He; Qian Zhang; Junhao Su; Meng Li; Bing Lin; Nanping Wu; Haonan Shen; Jiajing Chen (Chemosphere, 2024)

Deciphering spatial-temporal dynamics of flood exposure in the United States, - Joynal Abedin; Lei Zou; Mingzheng Yang; Robert Rohli; Debayan Mandal; Yi Qiang; Humaira Akter; Bing Zhou; Binbin Lin; Heng Cai (Sustainable Cities and Society, 2024)

High-molecular-weight dissolved organic matter enhanced phosphorus availability in paddy soils: Evidence from field and microcosm experiments - Hai-Bo Wang; Xi-Peng Liu; Bing-Jie Jin; Yu-Chen Shu; Cheng-Liang Sun; Yong-Guan Zhu; Xian-Yong Lin (Soil and Tillage Research, 2024)

Emamectin benzoate exposure induced carp kidney injury by triggering mitochondrial oxidative stress to accelerate ferroptosis and autophagy - Lu Li; Wan Li; Yufeng Liu; Bing Han; Yanbo Yu; Hongjin Lin (Pesticide Biochemistry and Physiology, 2024)

First identification of Mid-Miocene north–south trending dikes in the eastern Qiangtang terrane, eastern Tibet: Mantle melting and implications for plateau uplift - Chuan-Bing Xu; Jun Wang; Qiang Wang; Andrew C. Kerr; Wu-Fu Li; Jin-Heng Liu; Bing-Zhang Wang; Shan-Ping Li; Chun-Tao Wang; Zi-Long Wang; Lin Gong (Lithos, 2024)

Clean water harvesting and power generation by solar-absorbing Germanium@k-carrageenan evaporator demonstrating superior energy conversion - Yingying Chen; Lifang Chen; Zhi Yang; Wenhao Wang; Pengcheng Lin; Bing Yao (Journal of Cleaner Production, 2024)

Unveiling community adaptations to extreme heat events using mobile phone location data - Hao Tian; Heng Cai; Leiqiu Hu; Yi Qiang; Bing Zhou; Mingzheng Yang; Binbin Lin (Journal of Environmental Management, 2024)

Contamination of dairy products with tris(2,4-di-tert-butylphenyl) phosphite and implications for human exposure - Ruize Zhou; Jianqiang Geng; Jie Jiang; Bing Shao; Li Lin; Tongna Mu; Baolong Wang; Ting Liu (Food Chemistry, 2024)

Deciphering the formation of granules by n-DAMO and Anammox microorganisms - Zhi-Cheng Zhao; Ruo-Lin Li; Sheng-Qiang Fan; Yang Lu; Bing-Feng Liu; De-Feng Xing; Nan-Qi Ren; Guo-Jun Xie (Environmental Research, 2024)

Deciphering the influence of salinity stress on the biological aniline degradation system: Pollutants degradation performance and microbial response - Qi He; Bin Tan; Meng Li; Junhao Su; Bing Lin; Nan-ping Wu; Hao-nan Shen; Jia-jing Chen; Qian Zhang (Environmental Research, 2024)

Challenges and enhancement technologies of medium chain carboxylates production in open culture anaerobic fermentation - Shu-Lin Wu; Lan Wu; Wei Wei; Jiali Shentu; Yuyang Long; Dongsheng Shen; Bing-Jie Ni (Chemical Engineering Journal, 2024)

Enhancing open-circuit voltage and suppression of energy loss in ternary organic photovoltaics utilizing carbazole/bicarbazole-based guest donors - Chun-Yu Lin; Bing-Huang Jiang; Pei-Jui Weng; Yu Hsuan Lin; Yu-Wei Su; Hui-Shan Shih; Zhong-En Shi; Yan-Ru Lin; Jijitha Vailassery; Shih-Sheng Sun; Chih-Ping Chen; Yuan Jay Chang (Chemical Engineering Journal, 2024)

Mutual-benefit modification of the coagulant solution and fly ash for enhanced sludge dewatering - Yingfei Sun; Yuexing Wang; Jianjun Zhang; Chengzhi Zhu; Zuohong Chen; Zehui Yu; Bing Li; Ruo-hong Li; Xiao-yan Li; Lin Lin (Chemical Engineering Journal, 2024)

TRIM38 suppresses migration, invasion, metastasis, and proliferation in non-small cell lung cancer (NSCLC) via regulating the AMPK/NF-κB/NLRP3 pathway - Kaihua Zhang; Guihu Lin; Zhenkai Nie; Shan Jin; Xiaohan Bing; Zhantao Li; Mingru Li (Molecular and Cellular Biochemistry, 2024)

HDAC inhibitors as a potential therapy for chemotherapy-induced neuropathic pain - Chalton Manengu; Chun-Hao Zhu; Guo-Dong Zhang; Miao-Miao Tian; Xiao-Bing Lan; Li-Jun Tao; Lin Ma; Yue Liu; Jian-Qiang Yu; Ning Liu (Inflammopharmacology, 2024)

The urgent need to reduce phosphorus discharges for sustainable mangrove wetland management - Lixia Qiu; Enhao Wang; Ruili Li; Xiaofeng Wu; Yuefei Huang; Guanghui Lin; Bing Li (Water Research, 2024)

Spatial distribution and assembly processes of bacterial communities in riverine and coastal ecosystems of a rapidly urbanizing megacity in China - Hebin Liang; Jin Huang; Yu Xia; Ying Yang; Yang Yu; Kai Zhou; Lin Lin; Xiaoyan Li; Bing Li (Science of The Total Environment, 2024)

A novel inherent safety index for reactive hazard evaluation integrating thermal and pressure effects - Zixuan Liu; Jiaxing Zhu; Feng Sun; Bing Sun; Lin Hao; Hongyuan Wei (Process Safety and Environmental Protection, 2024)

Bacterial assembly and succession patterns in conventional and advanced drinking water systems: From source to tap - Jie Liu; Renxin Zhao; Jie Feng; Wenjie Fu; Lijia Cao; Jiayu Zhang; Yusha Lei; Jiajin Liang; Lin Lin; Xiaoyan Li; Bing Li (Journal of Hazardous Materials, 2024)

Effect of vegetable oils on the thermal gel properties of PSE-like chicken breast meat protein isolate-based emulsion gels - Ke Li; Lin-Meng Wang; Bing-Bing Cui; Bo Chen; Dian-Bo Zhao; Yan-Hong Bai (Food Chemistry, 2024)

A systematic study on the chemical model of polycyclic aromatic hydrocarbons formation from nutrients (glucose, amino acids, fatty acids) in food - Qiuyi Lin; Haolin Zhang; Xiaomei Lv; Ruiwei Xie; Bing-Huei Chen; Yu-Wen Lai; Lei Chen; Hui Teng; Hui Cao (Food Chemistry, 2024)

CRISPR/Cas12a integrated electrochemiluminescence biosensor for pufferfish authenticity detection based on NiCo2O4 NCs@Au as a coreaction accelerator - Xiaobo Zhang; Zhiru Li; Xiuwen Wang; Lin Hong; Xinying Yin; Yan Zhang; Bing Hu; Qiuyue Zheng; Jijuan Cao (Food Chemistry, 2024)

Exploring the roles of excess amino acids, creatine, creatinine, and glucose in the formation of heterocyclic aromatic amines by UPLC-MS/MS - Haolin Zhang; Xiaomei Lv; Weiming Su; Bing-Huei Chen; Yu-Wen Lai; Ruiwei Xie; Qiuyi Lin; Lei Chen; Hui Cao (Food Chemistry, 2024)

Enhancing stand establishment and yield formation of cotton with multiple drip irrigation during emergence in saline fields of Southern Xinjiang - Jianlong Dai; Zhengpeng Cui; Yanjun Zhang; Lijie Zhan; JunJun Nie; Jianqiang Cui; Dongmei Zhang; Shizhen Xu; Lin Sun; Bing Chen; Hezhong Dong (Field Crops Research, 2024)

In-situ interfacial polymerization of polyamide TFN membranes by adding a diamino-silane coupling agent: Toward enhanced desalination performance - Huanhuan Wu; Qian Zhang; Bing Xu; Xin Liu; Yakai Lin; Nan Jiang; Hong Yao; Yuanhui Tang; Lin Wang; Lixin Yu; Zhenzhong Yang; Xiaolin Wang (Desalination, 2024)

Associations of toxic metals and their mixture with hyperuricemia in Chinese rural older adults - Hongli Wang; Yan Zhang; Liang Sun; Xianwei Guo; Qiang Liu; Junzhe Li; Ziwei Tian; Xuqiu Cheng; Yuan Wang; Huaibiao Li; Bing Hu; Jie Sheng; et al. (Environmental Geochemistry and Health, 2024)

Moderate oxidation of algae-laden water: Principals and challenges - Xin Mao; Qingnan Wang; Haiqing Chang; Bin Liu; Shiqing Zhou; Lin Deng; Bing Zhang; Fangshu Qu (Water Research, 2024)

Different microbial functional traits drive bulk and rhizosphere soil phosphorus mobilization in an alpine meadow after nitrogen input - Bing Han; Yicheng He; Ji Chen; Yufei Wang; Lina Shi; Zhenrong Lin; Lu Yu; Xiaoting Wei; Wantong Zhang; Yiyi Geng; Xinqing Shao; Shangang Jia (Science of The Total Environment, 2024)

Differential effects of oxytetracycline on detoxification and antioxidant defense in the hepatopancreas and intestine of Chinese mitten crab under cadmium stress - Lin Zeng; Yong-Hong Wang; Chun-Xiang Ai; Bin Zhang; Hui Zhang; Zi-Ming Liu; Min-Hui Yu; Bing Hu (Science of The Total Environment, 2024)

Nitrogen fertilization modulates rice phyllosphere functional genes and pathogens through fungal communities - Wei-Feng Wu; Xin-Yuan Li; Song-Can Chen; Bing-Jie Jin; Chun-Yan Wu; Gang Li; Cheng-liang Sun; Yong-Guan Zhu; Xian-Yong Lin (Science of The Total Environment, 2024)

Long-term developments in seasonal hypoxia and response to climate change: A three-decade modeling study in the Ariake Sea, Japan - Lin Hao; Ai Sanada; Baixin Chi; Bing Xiong; Yasuyuki Maruya; Shinichiro Yano (Science of The Total Environment, 2024)

Environmental and human history in the hyper-arid eastern Tarim Basin (Lop Nur), northwest China: A critical review for sustaining the natural and cultural landscapes - Kangkang Li; Xiaoguang Qin; Bing Xu; Lei Zhang; Guijin Mu; Yong Wu; Xiaohong Tian; Dong Wei; Chunxue Wang; Huiqiu Shao; Hongjuan Jia; Zhiqiang Yin; et al. (Quaternary International, 2024)

Three new quinic acid derivatives and a new shikimic acid derivative from the leaves of Castanopsis orthacantha - Xue-Xue Cheng; Ya-Feng Wang; Rui-Jie He; Bing-Yuan Yang; Zhang-Bin Liu; Yong-Lin Huang (Phytochemistry Letters, 2024)

Source-sink relationships of anthropogenic metal(loid)s from urban catchment to waterway in relation to spatial pattern of urban green infrastructures - Juan Li; Linlin Zhang; Shen Yu; Bing Hong; Ruihan Lin; Qi Li; Haifeng Jia; Dawen Yang; Chengwei Gu; Qimeng Jia (Journal of Hazardous Materials, 2024)

Mxenes as inorganic fillers for the construction of poly(aryl piperidinium) anion exchange membranes with microphase separation structures to enhance ionic conductivity - Xiuzhu Zhang; Zongxue Yu; Junlei Tang; Jiaqiang Huang; Xunwang Tang; Bing Lin; Shuangshuang Xia (Fuel, 2024)

Sulfation, characterization, antibacterial activity, and action mechanism of rice bran polysaccharides - Bing-Jie Chen; Yong-Jin Qiao; Gang Yu; Xiao Wang; Yi Zhang; Ling-Lin Fu (Food Bioscience, 2024)

Exploration of the immune response of grass carp (Ctenopharyngodon idellus) erythrocytes during bacterial infection - Shiyi Yang; Yanhan Bai; Junjie Tao; Chengming Tu; Bing Chen; Xiaoman Huang; Linpeng Zhang; Lihan Liu; Lin Li; Zhendong Qin (Fish & Shellfish Immunology, 2024)

Therapeutic effects and mechanisms of isoxanthohumol on DSS-induced colitis: regulating T cell development, restoring gut microbiota, and improving metabolic disorders - Ya-Na Yang; Bing Han; Mao-Qing Zhang; Na-Nan Chai; Feng-Lin Yu; Wen-Hui Qi; Meng-Yuan Tian; Dong-Zhi Sun; Ying Huang; Qing-Xin Song; Yan Li; Mao-Cui Zhu; et al. (Inflammopharmacology, 2024)

Mathematical derivation and mechanism analysis of beta oscillations in a cortex-pallidum model - Minbo Xu; Bing Hu; Zhizhi Wang; Luyao Zhu; Jiahui Lin; Dingjiang Wang (Cognitive Neurodynamics, 2024)

Dictyosphaerium sp.-treated aerobic digestate of perishable waste as substitution for vegetable hydroponic nutrient solution - Mengjie Zhang; Xiaoyan Zhang; Qilu Cheng; Feifan Shi; Yuan Fu; Jianlin Xu; Bing Gu; Junwei Ma; Li Yang; Qifa Zhou; Hui Lin (Algal Research, 2024)

Determinants of microbiome composition: Insights from free‐ranging hybrid zebras ( Equus quagga × grevyi ) - Joel O. Abraham; Bing Lin; Audrey E. Miller; Lucas P. Henry; Margaret Y. Demmel; Rosemary Warungu; Margaret Mwangi; Patrick M. Lobura; Luisa F. Pallares; Julien F. Ayroles; Robert M. Pringle; Daniel I. Rubenstein (Molecular Ecology, 2024)
The composition of mammalian gut microbiomes is highly conserved within species, yet the mechanisms by which microbiome composition is transmitted and maintained within lineages of wild animals remain unclear. Mutually compatible hypotheses exist, including that microbiome fidelity results from inherited dietary habits, shared environmental exposure, morphophysiological filtering and/or maternal effects. Interspecific hybrids are a promising system in which to interrogate the determinants of microbiome composition because hybrids can decouple traits and processes that are otherwise co‐inherited in their parent species. We used a population of free‐living hybrid zebras ( Equus quagga × grevyi ) in Kenya to evaluate the roles of these four mechanisms in regulating microbiome composition. We analysed faecal DNA for both the trn L‐P6 and the 16S rRNA V4 region to characterize the diets and microbiomes of the hybrid zebra and of their parent species, plains zebra ( E. quagga ) and Grevy's zebra ( E. grevyi ). We found that both diet and microbiome composition clustered by species, and that hybrid diets and microbiomes were largely nested within those of the maternal species, plains zebra. Hybrid microbiomes were less variable than those of either parent species where they co‐occurred. Diet and microbiome composition were strongly correlated, although the strength of this correlation varied between species. These patterns are most consistent with the maternal‐effects hypothesis, somewhat consistent with the diet hypothesis, and largely inconsistent with the environmental‐sourcing and morphophysiological‐filtering hypotheses. Maternal transmittance likely operates in conjunction with inherited feeding habits to conserve microbiome composition within species.

Abnormal brain functional network dynamics in amyotrophic lateral sclerosis patients with depression - Sujuan Sun; Yujing Chen; Bing Zhao; Jun Zhu; Tianrui Wen; Bingnan Peng; Qingguo Ren; Xiaohan Sun; Pengfei Lin; Dong Zhang; Shuangwu Liu (Brain Imaging and Behavior, 2024)

Environmental DNA metabarcoding reveals fish diversity, community assembly and one invasive species prevalence in a National Park of Liaohe in September - Ni Xin; Zhao Li; Yong-Wei Jiang; Hui Wang; Juan Tan; Yang Li; Bing-Jiao Sun; Xiao-Long Lin (Frontiers in Marine Science, 2024)
The escalating environmental changes are imposing multiple pressures on biodiversity conservation, thereby, more attention has been paid to fish diversity and community assembly patterns. Fish diversity in Liaohe River has deteriorated significantly due to overfishing, environmental pollution and other reasons, in addition, no fish survey related research has been published in Liaohe National Park in recent years. In order to study the diversity of fish species in the area and to investigate the presence of any invasive species. This study used eDNA metabarcoding to explore the distribution and diversity of fish communities in the Liaohe National Park. The study showed that a total of 54 species of fish from six orders, 14 families, and 39 genera were detected, meantime, the invasive species Lepomis cyanellus was found at two sampling sites. The α-diversity results showed that estuarine sites had the highest species diversity. The spatial structure of fish communities in the upstream and downstream reaches were similar as indicated by non-metric multidimensional scaling. In our study, the fish community is influenced by both deterministic and stochastic processes, with the stochastic processes being the main factor. The potential existence of L. cyanellus in Liaohe National Park might be resulted from aquaculture, ornamental pet trade, other economic fish farming, artificial release. The relatively low number of fish species in this study may be attributed to the limited number of sampling events and sampling sites. In addition to these factors, over exploitation of resources, water pollution, and the invasion of alien species have directly impacted the biodiversity of aquatic life. The results of this study lay a foundation for the future biodiversity investigation in National Parks of China, meantime, the use of eDNA monitoring is crucial to prevent, to control and limit the spreading of invasive species in advance.

Alkaloids isolated from the endophytic fungus Fusarium concentricum - Xi-Lin Zhang; Bing-Guo Lu; Jian Bai; Ning Li (Natural Product Research, 2024)

Atmospheric CO2 in the megacity Hangzhou, China: Urban-suburban differences, sources and impact factors - Yuanyuan Chen; Yanran Lu; Bing Qi; Qianli Ma; Kunpeng Zang; Yi Lin; Shuo Liu; Fengmei Pan; Shan Li; Peng Guo; Lihan Chen; Wengang Lan; et al. (Science of The Total Environment, 2024)

Effects of exercise on muscle fiber conversion, muscle development and meat quality of Sunit sheep - Lin Su; Congying Zhao; Bing Sun; Lu Dou; Chenlei Wang; Zhihao Yang; Tianle Li; Ye Jin (Meat Science, 2024)

Green synthesis of Fe3O4@ceramsite from sludge improving anaerobic digestion performance of waste activated sludge - Pengqu Zhang; Dongsheng Shen; Jinyang Shao; Xiaoyu He; Jianjun Zeng; Shu-Lin Wu; Yuyang Long; Wei Wei; Bing-Jie Ni (Journal of Environmental Management, 2024)

Spartina alterniflora invasion altered phosphorus retention and microbial phosphate solubilization of the Minjiang estuary wetland in southeastern China - Yan-Zhen Lin; Qi-Qi Chen; Yi-Fan Qiu; Rong-Rong Xie; Hong Zhang; Yong Zhang; Jia-Bing Li; Yong-He Han (Journal of Environmental Management, 2024)

Enhanced foamability and stability of aqueous foams through novel pickering fat globules formulated with solid lipid particles - Yuyan Zeng; Tangyu Yang; Yuan Liu; Bing Li; Lin Li; Xia Zhang (Food Hydrocolloids, 2024)

Analysis of the impact of indoor thermal comfort data characteristics on dataset quality - Chang Chang; Xiangli Li; Lin Duanmu; Bing Sun; Hengjin Ju (Energy and Buildings, 2024)

Selective capture of uranium by p-block bismuth-based metal–organic framework - Lin Zhao; Zhihao Pan; Lirong Cai; Shiyong Wang; Bing Lu; Sihao Lv; Yongfu Qiu; Gang Wang (Desalination, 2024)

Electrochemical oxidation processes based on renewable energy towards carbon neutrality: Oxidation fundamentals, catalysts, challenges and prospects - Yan Yan; Bing Lin; Liehui Zhang; Yingying Wang; Hailong Zhang; Hongpeng Zheng; Taigang Zhou; Yingqing Zhan; Zongxue Yu; Yun Kuang; Junlei Tang (Chemical Engineering Journal, 2024)

An antibacterial membrane based on Janus bacterial cellulose with nano-sized copper oxide through polydopamine conjugation for infectious wound healing - Bing Han; Fan Liu; Shuhang Hu; Xinyu Chen; Chenming Lin; In-Seop Lee; Cen Chen (Carbohydrate Polymers, 2024)

Clinicopathological characteristics and prognosis of Epstein-Barr virus–associated gastric cancer - Lin-lin Li; Ao-yang Yu; Mei Zhu; Lu-yao Ma; Meng-han Cao; Wen-lou Liu; Xiao-bing Qin; Chao Gao; Zheng-xiang Han; Hong-mei Wang (Archives of Virology, 2024)

Triterpene hexahydroxydiphenoyl ester and phenol glucosides from the leaves of Castanopsis eyrie (Champ. ex Benth.) Hutch - Bing-Yuan Yang; Nao Pang; Rui-Jie He; Ya-Feng Wang; Yong-Lin Huang (Natural Product Research, 2024)

Mechanism of peroxymonosulfate activation by nanoparticle Co@N–C: Experimental investigation and theoretical calculation - Mu Li; Lin Lin; Wei Zhang; Yubin Zou; Jiahui Hu; Yin Li; Bing Li; Feiyun Sun; Xiao-yan Li (Chemosphere, 2024)

Immune response mechanisms underlying bacterial infection in Aquarana catesbeiana erythrocytes - Yanhan Bai; Lingqin Lu; Junjie Tao; Chengming Tu; Bing Chen; Shiyi Yang; Xiaoman Huang; Linpeng Zhang; Lihan Liu; Li Lin; Zhendong Qin (Aquaculture, 2024)

Humic substances mediated superior photochemical pollutant conversion on defective TiO2 in environmentally relevant matrices: The key roles of oxygen vacancy in surface interactions, oxidant activation and radical generation - Song Hu; Lyumeng Ye; Bing-Jie Tian; Jia-Ying Li; Ai-Yong Zhang; Lu Zhao; Chi Zhang; Chu Jiang; Zhi-Xian Lin; Wei Da; Qi-Xin Wei (Science of The Total Environment, 2024)

Degradation of prometryn during UV/persulfate process: Kinetics and disinfection by-product formation - Chen-Yan Hu; Hao Liu; Ling Xu; Yi-Li Lin; Qiang-Bing Wang; Dan-Dan Huang; Yi-Hui Wu; Zi-Yi Dong; Sheng-Jie Ji (Journal of Water Process Engineering, 2024)

Trace Co(II) triggers peracetic acid activation in phosphate buffer: New insights into the oxidative species responsible for ciprofloxacin removal - Feifei Liu; Yubin Zou; Hebin Liang; Jiahui Hu; Yin Li; Lin Lin; Xiaoyan Li; Bing Li (Journal of Hazardous Materials, 2024)

Improved Pb(II) removal by D001 resin with a facile nanoscale α-FeOOH modification - Bing Li; Zhiyi Deng; Xueying Lin; Weiting Chen; Ping Li; Jinhua Wu (Journal of Environmental Chemical Engineering, 2024)

Effects of ultrasonic pretreatment on fibrillation kinetics, morphologies, and functional properties of bovine serum albumin fibrils - Yipeng Yang; Ziran Pan; Tangyu Yang; Huaijie Yang; Lin Li; Bing Li (Food Hydrocolloids, 2024)

Fenton-like system of UV/Glucose-oxidase@Kaolin coupled with organic green rust: UV-enhanced enzyme activity and the mechanism of UV synergistic degradation of photosensitive pollutants - Xiangyu Liu; Lei Zhang; Qian Zhang; Meng Li; Ziqi Zhao; Bing Lin; Jie Peng; Haonan Shen; Qi He (Environmental Research, 2024)

Humoral immunosuppression of exposure to polycyclic aromatic hydrocarbons and the roles of oxidative stress and inflammation - Yingyi Dai; Qianyun Deng; Qiaojuan Liu; Lin Zhang; Huiquan Gan; Xinhong Pan; Bing Gu; Lei Tan (Environmental Pollution, 2024)

Visible light-mediated supramolecular framework for tunable CO2 adsorption - Tao Yang; Chunyi Yu; Chen Gu; Yang Liu; Hui Wen; Xiao-Qin Liu; Guoliang Liu; Lifeng Ding; Lin-Bing Sun (Chemical Engineering Journal, 2024)

Ionic-confining-assisted multiple-mode tunable light emitting of carbon nanodots - Jing-Nan Hao; Zhong-Zheng Ding; Cheng-Long Shen; Guang-Song Zheng; Jia-Lu Liu; Ruo-Bing Li; Run-Wei Song; Kai-Kai Liu; Jin-Hao Zang; Lin Dong; Qing Lou; Chong-Xin Shan (Chemical Engineering Journal, 2024)

The Characteristics of Degradation of Enrofloxacin by Vis / BC-BiOI / PMS Photocatalytic System Based on BiOI-Modified Biochar - Yutong Xiang; Bin Tan; Meng Li; Yuning Liu; Xiangyu Liu; Yuwei Ding; Bing Lin; Qian Zhang (Water, Air, & Soil Pollution, 2024)

Chromosomal mapping of a major genetic locus from Agropyron cristatum chromosome 6P that influences grain number and spikelet number in wheat - Yida Lin; Shenghui Zhou; Wenjing Yang; Bing Han; Xuezhong Liang; Yuxin Zhang; Jinpeng Zhang; Haiming Han; Baojin Guo; Weihua Liu; Xinming Yang; Xiuquan Li; et al. (Theoretical and Applied Genetics, 2024)

A human-specific insertion promotes cell proliferation and migration by enhancing TBC1D8B expression - Hui Zhao; Lin-Lin Liu; Jian Sun; Lian Jin; Hai-Bing Xie; Jian-Bo Li; Hui Xu; Dong-Dong Wu; Xiao-Lin Zhuang; Min-Sheng Peng; Ya-Jun Guo; Wei-Zhu Qian; et al. (Science China Life Sciences, 2024)

Characterization of the MIKCC-type MADS-box gene family in blueberry and its possible mechanism for regulating flowering in response to the chilling requirement - Sui-Lin Zhang; Yan Wu; Xiao-Han Zhang; Xin Feng; Hui-Ling Wu; Bing-Jie Zhou; Ya-Qian Zhang; Man Cao; Zhi-Xia Hou (Planta, 2024)

PCSK9 regulates myocardial ischemia–reperfusion injury through parkin/pink1-mediated autophagy pathway - Guangwei Huang; Hailong Bao; Peng Zhan; Xiyang Lu; Zonggang Duan; Xinlin Xiong; Muzhi Lin; Bing Wang; Hongxin An; Luanda Xiahou; Haiyan Zhou; Zhenhua Luo; et al. (Molecular & Cellular Toxicology, 2024)

New insights into the treatment of polycystic ovary syndrome: HKDC1 promotes the growth of ovarian granulocyte cells by regulating mitochondrial function and glycolysis - Peiwei Cong; Bing Shang; Lina Zhang; Zhaoli Wu; Yanan Wang; Jia Li; Lin Zhang (Journal of Molecular Histology, 2024)

Biochemical and Transcriptome Analysis Reveals Pigment Biosynthesis Influenced Chlorina Leaf Formation in Anoectochilus roxburghii (Wall.) Lindl - Xiu-Xian Ye; Yi-Quan Chen; Jian-She Wu; Huai-Qin Zhong; Bing Lin; Min-Ling Huang; Rong-Hui Fan (Biochemical Genetics, 2024)

The longevity evaluation of multi-metal stabilization by MgO in Pb/Zn smelter–contaminated soils - Ze-Lin Xu; Da-Mao Xu; Hai-Xuan Li; Hao-Kai Li; Rong-Bing Fu (Environmental Science and Pollution Research, 2024)

Transcriptome analysis reveals the relationship between Spring viremia of carp N protein-induced endoplasmic reticulum stress in Epithelioma papulosum cyprinid (EPC) cells and apoptosis and autophagy - Xue Jiao; Yu-Ting Lu; Hong Shu; Lin-Hai Yu; Bing-Li Liu; Ai-Dong Qian; Yue-Hong Li (Aquaculture, 2024)

Competitive enrichment of comammox Nitrospira in floccular sludge - Jiaying Hou; Ying Zhu; Jinzhong Liu; Limin Lin; Min Zheng; Linyan Yang; Wei Wei; Bing-Jie Ni; Xueming Chen (Water Research, 2024)

Lacticaseibacillus chiayiensis mediate intestinal microbiome and microbiota-derived metabolites regulating the growth and immunity of chicks - Xin-Dong Li; Yao Lu; Cheng-Ying Luo; Wei-Gang Xin; Xin Kang; Yi-Cen Lin; Lian-Bing Lin (Veterinary Microbiology, 2024)

Artificial humic acid coated ferrihydrite strengthens the adsorption of phosphate and increases soil phosphate retention - Shuang Gai; Bing Liu; Yibo Lan; Lin Han; Yixiong Hu; Guanghao Dongye; Kui Cheng; Zhuqing Liu; Fan Yang (Science of The Total Environment, 2024)

Visible light-driven Cl-g-C3N4 activated peroxydisulfate process for TMP efficient degradation in a wide pH range - Jie Chen; Jiashuai Hu; Yuanmao Lin; Xiaoling Liu; Jie Liang; Ke Zhang; Bing Jiang; Hongbing Luo; Lin Li; Xiaochan An; Xiaobing Chen; Xiaojun Chen; et al. (Journal of Water Process Engineering, 2024)

Investigating the antibiotic resistance genes and their potential risks in the megacity water environment: A case study of Shenzhen Bay Basin, China - Hebin Liang; Jin Huang; Yi Tao; Uli Klümper; Thomas U. Berendonk; Kai Zhou; Yu Xia; Ying Yang; Yang Yu; Ke Yu; Lin Lin; Xiaoyan Li; et al. (Journal of Hazardous Materials, 2024)

Horizontal transfer potential of antibiotic resistance genes in wastewater treatment plants unraveled by microfluidic-based mini-metagenomics - Jiachen Ma; Haohao Sun; Bing Li; Bing Wu; Xuxiang Zhang; Lin Ye (Journal of Hazardous Materials, 2024)

Ultrasonic treatment treated sea bass myofibrillar proteins in low-salt solution: Emphasizing the changes on conformation structure, oxidation sites, and emulsifying properties - Meijuan Lan; Tongshuai Li; Lin Li; Shaoyun Wang; Juncheng Chen; Tangyu Yang; Zhiru Li; Yipeng Yang; Xia Zhang; Bing Li (Food Chemistry, 2024)

Interfacial adsorption dynamics of solid lipid particles at oil/water interfaces through QCM-D technique - Tangyu Yang; Shengjie Zan; Bing Li; Lin Li; Xia Zhang (Food Hydrocolloids, 2024)

Soil properties and fungal community jointly explain N2O emissions following N and P enrichment in an alpine meadow - Zhenrong Lin; Lina Shi; Xiaoting Wei; Bing Han; Cuoji Peng; Zeying Yao; Yicheng He; Qing Xiao; Xinmin Lu; Yanfang Deng; Huakun Zhou; Kesi Liu; et al. (Environmental Pollution, 2024)

Seismic behaviour of FRP-concrete-steel double-tube columns with shear studs: Experimental study and numerical modelling - Bing Zhang; Shuhong Lin; Sumei Zhang; Xingbao Lu; Tao Yu (Engineering Structures, 2024)

Constructing light-insensitive Ag(I) sites by in situ integration of nanoheaters for efficient adsorptive desulfurization - Jun Liu; Zhen Fu; Peng Tan; Min Li; Xiao-Qin Liu; Lin-Bing Sun (Chemical Engineering Journal, 2024)

Unraveling metabolic fate of a veterinary antibiotic thiamphenicol via the multi-omic approach - Jiayu Zhang; Fangliang Guo; Hebin Liang; Ke Yu; Wan Cai; Lin Lin; Xiaoyan Li; Bing Li (Chemical Engineering Journal, 2024)

Self-growing micro/nano hexagonal cyclodextrins based on dual enzyme synergism and low-temperature induction - Ruikang Lin; Xufeng Zang; Chao Yuan; Bing Yu; Pengfei Liu; Yishan Fang; Bo Cui (Chemical Engineering Journal, 2024)

Rosette-like (Ni,Co)Se2@Nb2CTx MXene heterostructure with abundant Se vacancies for high-performance flexible supercapacitor electrodes - Baolei Shen; Xianjin Hu; Hai-Tao Ren; Hao-Kai Peng; Bing-Chiuan Shiu; Jia-Horng Lin; Ching-Wen Lou; Ting-Ting Li (Chemical Engineering Journal, 2024)

Rapid anaerobic culture and reaction kinetic study of anammox bacteria on microfluidic chip - Bing Li; Siyuan Mao; Chi Zhang; Tiansi Xu; Xueyan Ma; Hai Lin; Huabing Yin; Yong Qiu (Bioresource Technology, 2024)

Enhancing Flooding Depth Forecasting Accuracy in an Urban Area Using a Novel Trend Forecasting Method - Song-Yue Yang; You-Da Jhong; Bing-Chen Jhong; Yun-Yang Lin (Water Resources Management, 2024)

An Intriguing Structural Modification in Neutrophil Migration Across Blood Vessels to Inflammatory Sites: Progress in the Core Mechanisms - Zexu Wang; Yufang Guo; Yulei Zhang; Liangquan Wu; Li Wang; Qiuqi Lin; Bing Wan (Cell Biochemistry and Biophysics, 2024)

An Improved VO Method for Collision Avoidance of Ships in Open Sea - Mao Zheng; Kehao Zhang; Bing Han; Bowen Lin; Haiming Zhou; Shigan Ding; Tianyue Zou; Yougui Yang (Journal of Marine Science and Engineering, 2024)
In order to effectively deal with collisions in various encounter situations in open water environments, a ship collision avoidance model was established, and multiple constraints were introduced into the velocity obstacle method, a method to determine the ship domain by calculating the safe distance of approach was proposed. At the same time, the ship collision avoidance model based on the ship domain is analyzed, and the relative velocity set of the collision cone is obtained by solving the common tangent line within the ellipse. The timing of starting collision avoidance is determined by calculating the ship collision risk, and a method for ending collision avoidance is proposed. Finally, by comparing the simulation experiments of the improved algorithm with those of the traditional algorithm and the actual ship experiment results of manual ship maneuvering, it is shown that the method can effectively avoid collisions based on safe encounter distances that comply with navigation experience in different encounter situations. At the same time, it has better performance in collision avoidance behavior. It has certain feasibility and practical applicability.

Pivotal Role of GSTO2 in Ferroptotic Neuronal Injury After Intracerebral Hemorrhage - Li Lin; Xiao-Na Li; Zhen-Yan Xie; Yong-Zhen Hu; Qing-Shan Long; Yi-Qi Wen; Xiao-Bing Wei; Li-Yang Zhang; Xue-Song Li (Journal of Molecular Neuroscience, 2024)
Previous research has found that an adaptive response to ferroptosis involving glutathione peroxidase 4 (GPX4) is triggered after intracerebral hemorrhage. However, little is known about the mechanisms underlying adaptive responses to ferroptosis. To explore the mechanisms underlying adaptive responses to ferroptosis after intracerebral hemorrhage, we used hemin-treated HT22 cells to mimic brain injury after hemorrhagic stroke in vitro to evaluate the antioxidant enzymes and performed bioinformatics analysis based on the mRNA sequencing data. Further, we determined the expression of GSTO2 in hemin-treated hippocampal neurons and in a mouse model of hippocampus-intracerebral hemorrhage (h-ICH) by using Western blot. After hemin treatment, the antioxidant enzymes GPX4, Nrf2, and glutathione (GSH) were upregulated, suggesting that an adaptive response to ferroptosis was triggered. Furthermore, we performed mRNA sequencing to explore the underlying mechanism, and the results showed that 2234 genes were differentially expressed. Among these, ten genes related to ferroptosis (Acsl1, Ftl1, Gclc, Gclm, Hmox1, Map1lc3b, Slc7a11, Slc40a1, Tfrc, and Slc39a14) were altered after hemin treatment. In addition, analysis of the data retrieved from the GO database for the ten targeted genes showed that 20 items on biological processes, 17 items on cellular components, and 19 items on molecular functions were significantly enriched. Based on the GO data, we performed GSEA and found that the glutathione metabolic process was significantly enriched in the hemin phenotype. Notably, the expression of glutathione S-transferase omega (GSTO2), which is involved in glutathione metabolism, was decreased after hemin treatment, and overexpression of Gsto2 decreased lipid reactive oxygen species level in hemin-exposed HT22 cells. In addition, the expression of GSTO2 was also decreased in a mouse model of hippocampus-intracerebral hemorrhage (h-ICH). The decreased expression of GSTO2 in the glutathione metabolic process may be involved in ferroptotic neuronal injury following hemorrhagic stroke.

Genome-wide identification and functional analysis of the cellulose synthase-like gene superfamily in common oat (Avena sativa L.) - Shanshan Zhang; Haibin Hu; Shumin Cui; Lin Yan; Bing Wu; Shanjun Wei (Phytochemistry, 2024)

Enhanced biomethane production from waste activated sludge anaerobic digestion by ceramsite and amended Fe2O3 ceramsite - Dongsheng Shen; Pengqu Zhang; Shu-Lin Wu; Yuyang Long; Wei Wei; Bing-Jie Ni (Journal of Environmental Management, 2024)

Photothermal-driven pH-responsive fiber composite membrane for oil-wastewater purification - Shuxia Li; Jia-Horng Lin; Hai-Tao Ren; Bing-Chiuan Shiu; Fei Sun; Ching-Wen Lou; Ting-Ting Li (Journal of Environmental Chemical Engineering, 2024)

Experimental study on the effect of unloading rate on the damage of coal with boreholes - Sibo Liu; Haifei Lin; Shugang Li; Haiqing Shuang; Bo Zhao; Peiyun Xu; Bing Zhou; Yu Tian (Fuel, 2024)

Effects of static magnetic field (SMF) and alternating magnetic field (AMF) assisted freezing on the microstructure and protein properties of channel catfish (Ictalurus punctatus) fillet - Bing Yang; Li Yang; Ruihong Xu; Shaotong Jiang; Lin Lin; Jianfeng Lu (Food Chemistry, 2024)

The infection of Aeromonas hydrophila activated Multiple programmed cell death pathways in red blood cells of Clarias fuscus - Junjie Tao; Chengming Tu; Zizheng Xu; Yanhan Bai; Bing Chen; Shiyi Yang; Xiaoman Huang; Linpeng Zhang; Lihan Liu; Li Lin; Zhendong Qin (Fish & Shellfish Immunology, 2024)

Ecological and functional differences of abundant and rare sub-communities in wastewater treatment plants across China - Kuo Yang; Wei Liu; Hui-min Lin; Tan Chen; Ting Yang; Bing Zhang; Xianghua Wen (Environmental Research, 2024)

Triclocarban exhibits higher adipogenic activity than triclosan through peroxisome proliferator-activated receptors pathways - Jia-Da Zhang; Sen He; Ting-Ting He; Chuan-Hai Li; Bing-Hua Yan; Yuan Yang; Jian Yang; Lin Luo; Yu-Long Yin; Lin-Ying Cao (Environmental Pollution, 2024)

Rational construction Ag/LiF/sulfide rich protective layer for remarkably enhancing the stability of Li metal anodes - Caili Xu; Shu Zhang; Cheng Chen; Yunhui Lin; Bing Qu; Haiping Zhou; Mengqiang Wu (Chemical Engineering Journal, 2024)

Deciphering the role of hydraulic retention time (HRT) in integrated fixed-film activated sludge (IFAS) system under aniline stress: Effects on microbial succession and communication - Nan-ping Wu; Bin Tan; Meng Li; Naif Abdullah Al-Dhabi; Bing Lin; Qi He; Hao-nan Shen; Jia-jing Cheng; Wangwang Tang; Qian Zhang (Chemical Engineering Journal, 2024)

Low-temperature fabrication of potassium single-atom solid base catalysts with high activity in transesterification - Xiang-Bin Shao; Xing-Ru Song; Song-Song Peng; Xiao-Qin Zheng; Shi-Chao Qi; Peng Tan; Xiao-Qin Liu; Lin-Bing Sun (Chemical Engineering Journal, 2024)

Peroxisome Proliferator-Activated Receptor-γ Coactivator-1α in the Spotlight with Multiple Sclerosis - Ya-Na Yang; Mao-Qing Zhang; Feng-Lin Yu; Bing Han; Ming-Yue Bao; Yan He; Xing Li; Yuan Zhang (Neuroscience Bulletin, 2024)

PSO-Based Predictive PID-Backstepping Controller Design for the Course-Keeping of Ships - Bowen Lin; Mao Zheng; Bing Han; Xiumin Chu; Mingyang Zhang; Haiming Zhou; Shigan Ding; Hao Wu; Kehao Zhang (Journal of Marine Science and Engineering, 2024)
Ship course-keeping control is of great significance to both navigation efficiency and safety. Nevertheless, the complex navigational conditions, unknown time-varying environmental disturbances, and complex dynamic characteristics of ships pose great difficulties for ship course-keeping. Thus, a PSO-based predictive PID-backstepping (P-PB) controller is proposed in this paper to realize the efficient and rapid course-keeping of ships. The proposed controller takes the ship’s target course, current course, yawing speed, as well as predictive motion parameters into consideration. In the design of the proposed controller, the PID controller is improved by introducing predictive control. Then, the improved controller is combined with a backstepping controller to balance the efficiency and stability of the control. Subsequently, the parameters in the proposed course-keeping controller are optimized by utilizing Particle Swarm Optimization (PSO), which can adaptively adjust the value of parameters in various scenarios, and thus further increase its efficiency. Finally, the improved controller is validated by carrying out simulation tests in various scenarios. The results show that it improves the course-keeping error and time-response specification by 4.19% and 9.71% on average, respectively, which can efficiently achieve the course-keeping of ships under various scenarios.

How do the occurrence patterns of potentially toxic elements (PTEs) control their release behaviours from Pb/Zn smelter contaminated soils? - Da-Mao Xu; Hao-Kai Li; Ze-Lin Xu; Rong-Bing Fu (Journal of Cleaner Production, 2024)

Adapting to seasonal temperature variations: A dynamic multi-subunit strategy for sulfur autotrophic denitrification bioreactors - Yi-Lu Sun; Han-Lin Wang; Huu Hao Ngo; Wenshan Guo; Bing-Jie Ni; Xue-Ning Zhang; Wei Wei (Environmental Research, 2024)

Deciphering microbial communities and their unique metabolic repertoire across rock-soil–plant continuum in the Dayoukeng fumarolic geothermal field of the Tatun Volcano Group - Jung-Sheng Chen; Bashir Hussain; Hsin-Chi Tsai; Viji Nagarajan; Rajendran Senthil Kumar; I-Ching Lin; Bing-Mu Hsu (Environmental Science and Pollution Research, 2023)

Reservoir horizontal principle stress prediction using intelligent fusion model based on physical model constraints: a case study of Daji Block, Eastern Ordos Basin, North China - Haiyu Lin; Xiangjun Liu; Jian Xiong; Lixi Liang; Jianjun Wu; Bing Li (Acta Geophysica, 2023)

Electrochemical oxidation of tetrahydrofurfuryl acohol on boron-doped diamond anode: Influence of current density and electrolyte solution - Huiqiang Liu; Xiaofan Hong; Jingshuang Chen; Xu Lin; Bing Wang; Ying Xiong (Chemosphere, 2023)

Bimetallic capture sites on porous La/Bi hydroxyl double salts for efficient phosphate adsorption: Multiple active centers and excellent selective properties - Bing Lu; Gang Wang; Lin Zhao; Shiyong Wang; Zhihao Pan; Shuangshi Dong (Chemosphere, 2023)

Depth profiles of microplastics in sediments from inland water to coast and their influential factors - Bing Yuan; Wenhui Gan; Jian Sun; Binliang Lin; Zhihe Chen (Science of The Total Environment, 2023)

Study on the impact of the perforated floating breakwater on coastal bridge with box-girder superstructure under two-dimensional focused waves - Lin Li; Bo Huang; Shuhang Qian; Zhiying Yang; Jianting Zhou; Qingyang Ren; Bing Zhu (Ocean Engineering, 2023)

Structural characterization of a low-molecular-weight polysaccharide from Plumula Nelumbinis and evaluation of its antioxidant and anti-inflammatory activity - Qingsong Zheng; Juncheng Chen; Yi Yuan; Xia Zhang; Yongzhen Zhai; Yuan Zhang; Lin Li; Bing Li (Food Bioscience, 2023)

Effect of hydraulic regime on sulfur-packed bed performance: Denitrification and disproportionation - Yi-Lu Sun; Wei Wei; Huu Hao Ngo; Wen Shan Guo; Xue-Ning Zhang; Bing-Jie Ni; Wei-Qin Zhuang; Han-Lin Wang (Environmental Research, 2023)

Numerical modeling on nuclide transport around a nuclear waste repository under coupled thermo-hydro-mechanical condition - Jintong Zhang; Junyu Chen; Zhihong Zhao; Sicong Chen; Guihong Liu; Xingguang Zhao; Ju Wang; Tao Lin; Bing Liu (Computers and Geotechnics, 2023)

Face-to-face conducting mechanism enabled by Si-C bonds for binder free Si@CNTs electrode - Zhi Yong Zhang; Zhe Fei Sun; Yan Liu; Bing Sheng Liu; Lin Shan Luo; Peng Fei Su; Chao Fei Lan; Shi Sheng Guo; Zi Qi Zhang; Xiang Han; Wei Huang; Zi Ping Wu; et al. (Chemical Engineering Journal, 2023)

Clinical comprehensive evaluation of direct oral anticoagulants for patients with atrial fibrillation in China - Chi Zhang; Zhi-Chun Gu; Er-Li Ma; Bing-Long Liu; Mang-Mang Pan; Jia Wang; Xin Wang; Bin Wu; Hou-Wen Lin (European Journal of Clinical Pharmacology, 2023)

Ecosystem responses dominate the trends of annual gross primary productivity over terrestrial ecosystems of China during 2000–2020 - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Hua Qi; Meng Yang; Zhao-Gang Liu; Xiao-Jun Dou; Le-Xin Ma; Shi-Ping Chen; et al. (Agricultural and Forest Meteorology, 2023)

Two truxinate derivatives and a phenyldilactone from the leaves of Castanopsis eyrei - Ya-feng Wang; Nao Pang; Zhen-hua Liang; Yong-lin Huang; Rui-jie He; Bing-yuan Yang; Zhang-bin Liu (Natural Product Research, 2023)

Overcoming the fluorescent interference during Raman spectroscopy detection of microplastics - Yu Liu; Jiale Hu; Liqian Lin; Bing Yang; Minhua Huang; Min Chang; Xiaoxin Huang; Zhenqing Dai; Shengli Sun; Lei Ren; Chengyong Li (Science of The Total Environment, 2023)

Phenolic glycosides and indole alkaloids isolated from the roots and rhizomes of Clematis chinensis and their anti-inflammatory activity - Hai-Bing Jiang; Si-Yuan Shao; Ya-Zi Wei; Ming-Bao Lin; Shuai Li (Phytochemistry, 2023)

Experimental study of the motion characteristics of a twin-circular submerged floating tunnel under wave actions - Weidong Chen; Chao Wang; Bing Ren; Pengzhi Lin (Ocean Engineering, 2023)

Characterization of anglerfish gelatin/polyvinyl alcohol film and its application in preservation of small yellow croaker (Larimichthys polyactis) - Bing Lin; Xiaojun Zhang; Duipeng Ou; Yu Chen; Yunyun Chen; Xuechang Chen (Journal of Food Engineering, 2023)

Efficient iron single-atom materials for environmental pollutants removal from aqueous solutions: A review - Hairui Hou; Lin Fang; Lijie Liu; Bing Zhao; Dedong Wu; Zixuan Ma; Baowei Hu; Xiangxue Wang; Shujun Yu (Journal of Cleaner Production, 2023)

In-situ production of lactate driving the biotransformation of waste activated sludge to medium-chain fatty acid - Shu-Lin Wu; Wei Wei; Huu Hao Ngo; Wenshan Guo; Chen Wang; Yun Wang; Bing-Jie Ni (Journal of Environmental Management, 2023)

Prenatal and postnatal exposure to heavy metals in PM2.5 and autism spectrum disorder - Hao-Hsuan Lin; Chau-Ren Jung; Chuan-Yao Lin; Ya-Chu Chang; Chia-Yun Hsieh; Pei-Chuan Hsu; Bao-Ru Chuang; Bing-Fang Hwang (Environmental Research, 2023)

Elucidating the roles of Cr(VI)-Cu(II) Co-pollution in the stress of aniline degradation stress: Insights into metabolic pathways and functional genes - Bing Lin; Bin Tan; Xiangyu Liu; Meng Li; Haojin Peng; Qian Zhang; Jiajing Chen; Haonan Shen; Qi He (Bioresource Technology, 2023)

Tropospheric ozone is a catastrophe, and ethylenediurea (EDU) is a phytoprotectant, recent reports on climate change scenario: A review - Sunil K. Gupta; Yang Da; Yun-Bing Zhang; Vivek Pandey; Jiao-Lin Zhang (Atmospheric Pollution Research, 2023)

Synthesis of novel naphthalene-chimonanthine scaffolds hybrids with potent antibacterial or antifungal activity - Shaojun Zheng; Wenbin Wu; Qiaoju Jiang; Chuansong Lin; Yue Fang; Huihui Dai; Bing Tang; Yi Tan (Natural Product Research, 2023)

Co-electron donors driven medium-chain fatty acids production: Roles of electron donors, reaction kinetics and metabolic pathways - Shu-Lin Wu; Yuyang Long; Wei Wei; Xingdong Shi; Dongsheng Shen; Bing-Jie Ni (Chemosphere, 2023)

Enhanced simultaneous removal of sulfamethoxazole and zinc (II) in the biochar-immobilized bioreactor: Performance, microbial structures and gene functions - Xi Chen; Hai Lin; Yingbo Dong; Bing Li; Chenjing Liu; Liping Zhang; Yanrong Lu; Qi Jin (Chemosphere, 2023)

Endophyte inoculation enhanced microbial metabolic function in the rhizosphere benefiting cadmium phytoremediation by Phytolacca acinosa - Bing Li; Beibei Wu; Yingbo Dong; Hai Lin; Chenjing Liu (Chemosphere, 2023)

The growth inhibitory effects and non-targeted metabolomic profiling of Microcystis aeruginosa treated by Scenedesmus sp - Xiao-lin Zhang; Qian-qian Zhu; Chuan-yue Chen; Bing Xie; Bin-guo Tang; Mei-hua Fan; Qun-ju Hu; Zhi Liao; Xiao-jun Yan (Chemosphere, 2023)

Selected rhizobacteria facilitated phytoremediation of barren and heavy metal contaminated gold mine tailings by Festuca arundinacea - Xu Chen; Chaoyu Sun; Qian Zhang; Xinyi Jiang; Chenjing Liu; Hai Lin; Bing Li (Chemosphere, 2023)

Genome-centric metagenomics provides new insights into metabolic pathways of polyhydroxyalkanoates biosynthesis and functional microorganisms subsisting on municipal organic wastes - Ruo-hong Li; Jin Huang; Cheng-xi Liu; Ke Yu; Feng Guo; You Li; Zuo-hong Chen; Xuan Wang; Ren-xin Zhao; Jia-yu Zhang; Jia-jin Liang; Yun Li; et al. (Water Research, 2023)

Targeted isolation of ursane-type triterpenoids from Tragopogon porrifolius based on Feature-Based Molecular Networking - Hong-bing Sun; Hai-fei Zou; Bing Xia; Yu-cheng Gu; Wen-lin Wu; Yan Zhou (Phytochemistry Letters, 2023)

Numerical study on the behaviors of coastal bridges with box girder under the action of extreme waves - Zhiying Yang; Bing Zhu; Bo Huang; Jie Hou; Yuezhi Zhang; Lin Li (Ocean Engineering, 2023)

Fertile mantle domains with different metasomatic features beneath the eastern North China Craton: Transformation from variably auto-metasomatized asthenospheric upwelling - Lei-Tao Cao; Jian-Ping Zheng; Hong-Kun Dai; Qing Xiong; A-Bing Lin; Shao-Kui Pan (Lithos, 2023)

Multiple tectonic switches in the Eastern Tianshan, Central Asian Orogenic Belt: Implications for crustal growth and metallogenesis - Lin Gong; Huayong Chen; Qiang Wang; Bing Xiao; Shuanliang Zhang; Gongjian Tang (Lithos, 2023)

Highly-oxidizing Au@MnO2−X nanozymes mediated homogeneous electrochemical detection of organophosphorus independent of dissolved oxygen - Huiling Zeng; Hailan Chen; Bing Yang; Junyi Zeng; Lin Meng; Donglin Shi; Liang Chen; Youju Huang (Journal of Hazardous Materials, 2023)

Advances in high performance anion exchange membranes: Molecular design, preparation methods, and ion transport dynamics - Ximin Chen; Yingqing Zhan; Junlei Tang; Xulin Yang; Ao Sun; Bing Lin; Fei Zhu; Hongshan Jia; Xianzhang Lei (Journal of Environmental Chemical Engineering, 2023)

Inactivation of Alicyclobacillus acidoterrestris vegetative cells and spores induced by atmospheric cold plasma - Si-Qi Zhao; Lin Chen; Bing Yan; Lang-Hong Wang; Xin-An Zeng; Rana Muhammad Aadil (Innovative Food Science & Emerging Technologies, 2023)

The role of the core microorganisms in the microbial interactions in activated sludge - Huimin Lin; Yichen Zheng; Yuankai Yang; Fengyi Liu; Kuo Yang; Bing Zhang; Xianghua Wen (Environmental Research, 2023)

Acetylcholine (ACh) enhances Cd tolerance through transporting ACh in vesicles and modifying Cd absorption in duckweed (Lemna turionifera 5511) - Lin Yang; Xu Ma; Yuhan Guo; Yuman He; Yunwen Yang; Wenqiao Wang; Ziyi Xu; Zhaojiang Zuo; Ying Xue; Rui Yang; Bing Han; Jinsheng Sun (Environmental Pollution, 2023)

Evolution of aniline degradation and nitrogen removal performance in electro-enhanced sequence batch reactor under salinity stress: Sludge characteristics and microbial diversity - Bing Lin; Bin Tan; Qian Zhang; Meng Li; Jiapeng Feng; Junhao Su; Jing He; Yunjie Zhang; Xiangyu Liu; Nanping Wu; Jiajing Chen (Environmental Pollution, 2023)

Constructing zinc single-atom catalysts for the direct electron-transfer mechanism in peroxymonosulfate activation to degrade sulfamethoxazole efficiently - Yanan Xiao; Jiahui Hu; Xiao-yan Li; Yubin Zou; Yin Li; Lin Lin; Bing Li (Chemical Engineering Journal, 2023)

Combining HUMSC secretome and a conductive hydrogel enhances angiogenesis and electrical transmission at myocardial infarct sites to support cardiac repair - Shu-yi He; Lin-yu Long; Zhi-cun Wang; Wen-qi Liu; Wen Zhang; Cheng Hu; Xiao-feng Wu; Ruiqi Dong; Hong-song Fan; Qing-Jiang; Ying-ying Tong; Guang-hua Yang; et al. (Chemical Engineering Journal, 2023)

In-situ investigation into the dynamic evolution of electrode surface H* and H* mediated pH-independent and residue-free electro-Fenton process - Jun Zhang; Songying Qu; Bing Li; Xiaoyan Li; Lin Lin (Chemical Engineering Journal, 2023)

Cheese-like Ti3C2 for enhanced hydrogen storage - Chen Gu; Hai-Guang Gao; Peng Tan; Ya-Na Liu; Xiao-Qin Liu; Xiao-Hui Hu; Yun-Feng Zhu; Lin-Bing Sun (Chemical Engineering Journal, 2023)

SAPHO syndrome after COVID-19 vaccination complicated with thyroid function abnormalities: a case report and literature review - Jia-Ying Lin; Bing-Xue Bai (Immunologic Research, 2023)

Earthworms enhance the inhibition efficiency of 3,4-dimethylpyrazole phosphate on soil nitrification by altering soil AOB communities and gut denitrifier communities - Bing-Jie Jin; Xi-Peng Liu; Miao Zhang; Yan Hu; Cheng-Liang Sun; Gang Li; Yong-Guan Zhu; Xian-Yong Lin (Biology and Fertility of Soils, 2023)

Study on leaching characteristics and biotoxicity of porous asphalt with biochar fillers - Jiawen Liu; Hui Li; John Harvey; Gordon Airey; Sijie Lin; Stephanie Ling Jie Lee; Yitan Zhou; Bing Yang (Transportation Research Part D: Transport and Environment, 2023)

Optical properties and molecular composition of wintertime atmospheric water-soluble organic carbon in different coastal cities of eastern China - Haibiao Chen; Caiqing Yan; Qinglong Fu; Xinfeng Wang; Jiao Tang; Bin Jiang; Honglei Sun; Tiancheng Luan; Qiaoyun Yang; Qianbiao Zhao; Jun Li; Gan Zhang; et al. (Science of The Total Environment, 2023)

Early Paleozoic subduction imprints of the Proto-Tethys Ocean: Evidence from the Appinite–Diorite–Granodiorite complex in East Kunlun, Northern Tibet - Yang-Ming Hu; Xiao-Wei Li; Xuan-Xue Mo; Lin Li; Kai Wang; Bing-Zhang Wang; Xiao-Ping Gong; Guo-Chen Dong; Yan-Bin Liu (Lithos, 2023)

The occurrence of "yellowing" phenomenon and its main driving factors after the remediation of chromium (Cr)-contaminated soils: A literature review - Hao-Kai Li; Da-Mao Xu; Jun-Xian Wang; Ze-Lin Xu; Rong-Bing Fu (Journal of Hazardous Materials, 2023)

Genome-wide transcriptomics and microRNAomics analyses uncover multi-faceted mechanisms to cope with copper stress in ancient macrobenthos amphioxus - Lin-Yu Yang; Qian-Hua Zhu; Jun-Yuan Chen; Lian-Bing Lin; Ming-Zhong Liang; Qi-Lin Zhang (Journal of Hazardous Materials, 2023)

Periodate activation by atomically dispersed Mn on carbon nanotubes for the production of iodate radicals and rapid degradation of sulfadiazine - Jiahui Hu; Yubin Zou; Yin Li; Zehui Yu; Yutian Bao; Lin Lin; Bing Li; Xiao-yan Li (Chemical Engineering Journal, 2023)

Chitosan-based antibacterial microspheres loaded multifunctional Janus composite membranes with unidirectional biofluid transport, antioxidant and pH-responsive monitoring - Ting-Ting Li; Li Sun; Ying Zhang; Bing-Chiuan Shiu; Hai-Tao Ren; Hao-Kai Peng; Jia-Horng Lin; Ching-Wen Lou (Chemical Engineering Journal, 2023)

Meningeal lymphatics restoration and neurovascular protection synergistically improve traumatic brain injury treatment - Jingquan Lin; Hangxiang Sun; Hongjie Jiang; Rui Xue; Bing Qin; Jianan Lu; Zhoule Zhu; Chengwei Cai; Jiawei Han; Jianmin Zhang; Xiaohua Yu; Junming Zhu (Chemical Engineering Journal, 2023)

Electricity facilitates the lithium sorption from salt-lake brine by H3LiTi5O12 nanoparticles: Kinetics, selectivity and mechanism - Qiuyue Wang; Mu Li; Bing Zhao; Boyang Meng; Wutong Chen; Zekai Jiang; Xin He; Bing Li; Xiao-yan Li; Lin Lin (Chemical Engineering Journal, 2023)

Exploring a variable-resolution approach for simulating the regional climate in Southwest China using VR-CESM - Xiaoyu Jiang; Chenglai Wu; Bing Chen; Weiyi Wang; Xiaohong Liu; Zhaohui Lin; Zhenyu Han (Atmospheric Research, 2023)

The associations of non-essential metal mixture with fasting plasma glucose among Chinese older adults without diabetes - Jing-Yuan Lei; Pan-Pan Wang; Hong-Li Wang; Yuan Wang; Liang Sun; Bing Hu; Su-Fang Wang; Dong-Mei Zhang; Gui-Mei Chen; Chun-Mei Liang; Fang-Biao Tao; Lin-Sheng Yang; et al. (Environmental Science and Pollution Research, 2023)

Schizophrenia in the genetic era: a review from development history, clinical features and genomic research approaches to insights of susceptibility genes - Ye Lv; Lin Wen; Wen-Juan Hu; Chong Deng; Hui-Wen Ren; Ya-Nan Bao; Bo-Wei Su; Ping Gao; Zi-Yue Man; Yi-Yang Luo; Cheng-Jie Li; Zhi-Xin Xiang; et al. (Metabolic Brain Disease, 2023)

Tissue residue distribution and withdrawal time estimation of trimethoprim and sulfachloropyridazine in Yugan black-bone fowl ( Gallus gallus domesticus Brisson) - Lin Zhao; Dawen Zhang; Jing Lan; Xiangdong Sun; Yun Zhang; Bing Wang; Bei Ni; Shuang Wu; Ruiying Zhang; Hui Liao (Food Additives & Contaminants: Part A, 2023)

Study on the fatigue properties and constitutive model of siltstone under the coupled action of dry‒wet cycles and cyclic loads - Zhen Huang; Wei Zhang; Hai Zhang; Jia-Bing Zhang; Xi-lin Lu (Soil Dynamics and Earthquake Engineering, 2023)

Drip fertigation sustains crop productivity while mitigating reactive nitrogen losses in Chinese agricultural systems: Evidence from a meta-analysis - Jing Zheng; Minghua Zhou; Bo Zhu; Junliang Fan; Hongyu Lin; Bing Ren; Fucang Zhang (Science of The Total Environment, 2023)

Association of long-term exposure to ambient PM2.5 and its constituents with gut microbiota: Evidence from a China cohort - Sicheng Li; Bing Guo; Ke Dong; Shourui Huang; Jialong Wu; Hanwen Zhou; Kunpeng Wu; Xinyu Han; Xian Liang; Xiaofang Pei; Haojiang Zuo; Hualiang Lin; et al. (Science of The Total Environment, 2023)

Anti-apoptotic effect of adrenomedullin gene delivery on Leydig cells by suppressing TGF-β1 via the Hippo signaling pathway - You-wen Luo; Xia-lian Zhu; Ming-yong Li; Jian-hua Zhou; Zhi-min Yang; Tao Tong; Bing-hai Chen; Song-lin Qin; Bo-long Liu; Wei Hu (Reproductive Toxicology, 2023)

A promising approach for simultaneous removal of ammonia and multiple heavy metals from landfill leachate by carbonate precipitating bacterium - Lili Zheng; Hai Lin; Yingbo Dong; Bing Li; Yanrong Lu (Journal of Hazardous Materials, 2023)

Variations of methane fluxes and methane microbial community composition with soil depth in the riparian buffer zone of a sponge city park - Ru Xue; Ke Zhang; Xiaoling Liu; Bing Jiang; Hongbing Luo; Mei Li; You Mo; Cheng Liu; Lin Li; Liangqian Fan; Wei Chen; Lin Cheng; et al. (Journal of Environmental Management, 2023)

The association between chemical constituents of ambient fine particulate matter and obesity in adults: A large population-based cohort study - Shaokun Yang; Feng Hong; Sicheng Li; Xinyu Han; Jiawei Li; Xing Wang; Lin Chen; Xuehui Zhang; Xi Tan; Jingru Xu; Zhuoma Duoji; Zhuoga Ciren; et al. (Environmental Research, 2023)

Maternal exposure to fine particulate matter and congenital heart defects during preconception and pregnancy period: A cohort-based case-control study in the Taiwan maternal and child health database - Ya-Chu Chang; Yu-Ting Lin; Chau-Ren Jung; Ke-Wei Chen; Bing-Fang Hwang (Environmental Research, 2023)

Occurrence and migration of organophosphite and organophosphate esters into food simulants from single-use food packaging in China - Ruize Zhou; Jianqiang Geng; Jie Jiang; Li Lin; Jing Zhang; Yunjia Yang; Xiaojun Wang; Yumin Niu; Bing Shao (Environmental Pollution, 2023)

A visible and near-infrared light dual-responsive PEC immunosensor for archaeological silk microtrace detection based on in situ growth of Ag2S on ZnO-MXene nanocomposites - Qingqing Zhou; Yong Liu; Lin Wang; Kun Wang; Haodong Chen; Hailing Zheng; Yang Zhou; Zhiwen Hu; Zhiqin Peng; Junmin Wan; Bing Wang (Chemical Engineering Journal, 2023)

Unraveling the nexus of Cr (VI), aniline, and microbial ecology on aniline-degrading biosystem: Removal efficiency, sludge type, microbial ecology - Bing Lin; Bin Tan; Qian Zhang; Meng Li; Haojin Peng; Junhao Su; Jing He; Yunjie Zhang; Xiangyu Liu; Nanping Wu (Bioresource Technology, 2023)

MiR-590-5p promotes cisplatin resistance via targeting hMSH2 in ovarian cancer - Bing Li; Xuejie Xu; Linlin Zheng; Xiaojie Jiang; Jing Lin; Guoliang Zhang (Molecular Biology Reports, 2023)

Enhanced removal of Cr(VI) by polyethyleneimine-modified bamboo hydrochar - Zi-Le Chen; Yu-Nan Zhang; Jian-Zhong Guo; Lin Chen; Bing Li (Environmental Science and Pollution Research, 2023)

Two new isoflavones from the barks of Dalbergia hancei Benth - Xiao-Mei Li; Nao Pang; Ya-Feng Wang; Rui-Jie He; Li Ge; Bing-Yuan Yang; Ke-Di Yang; Yong-Lin Huang (Natural Product Research, 2023)

Synthesis and antifungal activity of novel chiral indole analogues - Yi Tan; Qiaoju Jiang; Chuansong Lin; Yue Fang; Huihui Dai; Bing Tang; Wenbin Wu; Shaojun Zheng (Natural Product Research, 2023)

Insight into mixed chlorine/chloramines conversion and associated water quality variability in drinking water distribution systems - Renjie Pan; Tian-Yang Zhang; Zheng-Xiong Zheng; Jian Ai; Tao Ye; Heng-Xuan Zhao; Chen-Yan Hu; Yu-Lin Tang; Jing-Jing Fan; Bing Geng; Bin Xu (Science of The Total Environment, 2023)

Assessing impacts of objective features and subjective perceptions of street environment on running amount: A case study of Boston - Lin Dong; Hongchao Jiang; Wenjing Li; Bing Qiu; Hao Wang; Waishan Qiu (Landscape and Urban Planning, 2023)

Applicability of carbonate clumped isotope thermometry in the Tuchang-Jentse geothermal field - Yi-Chia Lu; Sheng-Rong Song; Ling-Wen Liu; Tsung-Ren Peng; Bill Bing-Cheng Chen; Remy Kai-Cheng Tu; Li-Hung Lin; Pei-Ling Wang (Geothermics, 2023)

Development of a multifunctional food packaging for meat products by incorporating carboxylated cellulose nanocrystal and beetroot extract into sodium alginate films - Qiyong Guo; Yi Yuan; Min He; Xia Zhang; Lin Li; Yuan Zhang; Bing Li (Food Chemistry, 2023)

Structural and functional properties of self-assembled peanut protein nanoparticles prepared by ultrasonic treatment: Effects of ultrasound intensity and protein concentration - Lin Chen; Shao-Bing Zhang (Food Chemistry, 2023)

Horseradish peroxidase (HRP) and glucose oxidase (GOX) based dual-enzyme system: Sustainable release of H2O2 and its effect on the desirable ping pong bibi degradation mechanism - Xiangyu Liu; Qian Zhang; Meng Li; Song Qin; Ziqi Zhao; Bing Lin; Yuwei Ding; Yutong Xiang; Chengwei Li (Environmental Research, 2023)

Effect of using construction and demolition waste as substrate on methane and carbon dioxide emissions from green roofs - Xinping Li; Yuanmao Lin; Xiaoling Liu; Jie Liang; Xin Yang; Ke Zhang; Bing Jiang; Hongbing Luo; Lin Li; Zhaolan Wei; Xiaochan An; Wei Chen; et al. (Ecological Engineering, 2023)

Nitrogen coordination modulation of single-atom CoN4 enables dual-active-sites catalyst featuring synergistic organics adsorption and peroxymonosulfate activation - Jun Zhang; Songying Qu; Bing Li; Xiaoyan Li; Lin Lin (Chemical Engineering Journal, 2023)

Modulating the interfacial built-in electric field in oxygen vacancies-enriched Ru/MxOy@C (M = V, Nb, Ta) ordered macroporous heterojunctions for electrocatalytic hydrogen production - Xiao Hui Chen; Hong Chuan Fu; Xiao Lin Li; Ting Li; Qing Zhang; Zi Qing Li; Yuan Hao Luo; Jing Lei Lei; Nian Bing Li; Hong Qun Luo (Chemical Engineering Journal, 2023)

Integrated fixed-film activated sludge systems in continuous-flow and batch mode acclimated from low to high aniline concentrations: Performance, mechanism and metabolic pathways - Nan-ping Wu; Qian Zhang; Bin Tan; Meng Li; Bing Lin; Jing He; Jun-hao Su; Hao-nan Shen (Bioresource Technology, 2023)

Mechanistic insights into the migration behavior of cadmium (Cd) in the soil and groundwater systems at a construction site: Experimental and numerical analysis - Da–Mao Xu; Ze–Lin Xu; Zi–Qi Mu; Bai–Hong An; Xiao–Wen Fang; Rong–Bing Fu (Journal of Environmental Chemical Engineering, 2023)

Improving sludge settling performance of secondary settling tank and simultaneously adsorbing nitrate and phosphate with surfactant modified zeolite (SMZ) ballasted flocculation - Hai Lin; Xijie Huang; Jiang Chang; Bing Li; Yongsheng Bai; Bojun Su; Luyuan Shi; Yingbo Dong (Journal of Environmental Chemical Engineering, 2023)

Monitoring ambient air pollution and pulmonary function in asthmatic children by mobile applications in COVID-19 pandemic - Pei-Yu Lin; Jiu-Yao Wang; Bing-Fang Hwang; Ruby Pawankar; I-Jen Wang (International Journal of Hygiene and Environmental Health, 2023)

Stable single iron atom within two-dimensional porphyrin sheet catalysis for CO oxidation: A computational investigation - Kefeng Xie; Shengyuan Xu; Kai Xu; Jie Wang; Longjun Ma; Jun-Bing Lin (Fuel, 2023)

Recent advances in luminescence and aptamer sensors based analytical determination, adsorptive removal, degradation of the tetracycline antibiotics, an overview and outlook - Ma-Lin Cui; Zi-Xuan Lin; Qing-Fan Xie; Xiao-Yan Zhang; Bing-Qing Wang; Miao-Ling Huang; Da-Peng Yang (Food Chemistry, 2023)

An effective tool for tracking steroids and their metabolites at the watershed level: Combining fugacity modeling and a chemical indicator - Ru Xu; Shan Liu; Hui Chen; Qin-Wei Hao; Yong-Xia Hu; Heng-Xiang Li; Lang Lin; Rui Hou; Bing Hong; Shen Yu; Xiang-Rong Xu (Environmental Pollution, 2023)

Facile solvent-free radical polymerization to prepare itaconate-functionalized hydrochar for efficient sorption of methylene blue and Pb(II) - Hua-Jing Teng; Tao Xia; Cheng Li; Jian-Zhong Guo; Lin Chen; Chunzheng Wu; Bing Li (Bioresource Technology, 2023)

Late Carboniferous extension-related magmatism in the southwestern Alxa block of NW China: geochronology, geochemistry, and tectonic implications - Zeng-Zhen Wang; Xuan-Hua Chen; Wei-Cui Ding; Bing Li; Yi-Ping Zhang; Zhao-Gang Shao; Sheng-Lin Xu (International Geology Review, 2023)

Effects on the migration and speciation of heavy metals by combined capping and biochemical oxidation during sediment remediation - Juan Lin; Mengling Liu; Sunling Zhuang; Bing Geng; Xiaodi Wang; Jiasheng Ma; Musong Chen (Science of The Total Environment, 2023)

Vulnerability of farmers and herdsmen households in Inner Mongolian plateau to arid climate disasters and their development model - Wenlong Li; Suocheng Dong; Haiying Lin; Fujia Li; Hao Cheng; Zhuang Jin; Shan Wang; Hasbaggen Zhang; Pengshen Hou; Bing Xia (Journal of Cleaner Production, 2023)

Improving the biodegradation of chicken feathers by a Bacillus licheniformis ZSZ6 mutant and application of hydrolysate - Chunhong Cui; Liqiong Sun; Xuelian Chen; Yu Zhu; Zhi Zheng; Dongmei Mao; Mingxu Li; Yuxin Li; Yajun Cao; Bing Feng; Hui Wang; Lin Wang; et al. (International Biodeterioration & Biodegradation, 2023)

Mechanisms of acidic electrolyzed water killing bacteria - Fan Wang; Yan-Ning Lin; Yu Xu; Yong-Bing Ba; Zhao-Huan Zhang; Li Zhao; Wing Lam; Fu-Lan Guan; Yong Zhao; Chang-Hua Xu (Food Control, 2023)

Ultralight, robust, and high Prussian blue-loading polyacrylonitrile aerogel: Preparation, characterization and efficient adsorption/removal of Cs+ - Xiao-Bo Yang; Wei Li; Ze-Zhong Lin; Jing-Qi Liu; Hong-Xin Jiang; Hao Jia; Wei-Liang Jin; Xin-Long Hou; Bing-Xuan Du; Li-Na Zhu; De-Ming Kong (Chemical Engineering Journal, 2023)

Variable response of particles and inorganic carbon of two different soils during splash erosion - Chenjia Yuan; Junqiu Lin; Bing Wang; Daming Yang; Nufang Fang; Lingshan Ni; Zhihua Shi (CATENA, 2023)

Response characteristics of an insertion tensiometer investigated via the vacuum saturation method - Yi Guo; Hung-Chou Lin; Jian-Bing Peng (CATENA, 2023)

The mobility of Cr(VI) on the ferrihydrite-Cr(VI) co-precipitates: The effect of co-existing tartaric acid and Cu(II) - Lin Zhang; Fenglian Fu; Jinlong Peng; Bing Tang (Applied Geochemistry, 2023)

Dietary chitosan alleviates intestinal and liver injury of hybrid sturgeon (Acipenser baerii♀ × A. schrenckii♂) induced by Aeromonas hydrophila infection - Ruiran Li; Xiaoni Wang; Denghang Yu; Qianrong Liang; Fuguo Liu; Lin Zhang; Bing Hu; Jin Wei; Lihe Liu; Jun Liu; Hongsen Xu (Animal Feed Science and Technology, 2023)

Physicochemical characteristics and microbial communities of rhizosphere in complex amendment-assisted soilless revegetation of gold mine tailings - Ling Qian; Hai Lin; Bing Li; Yingbo Dong (Chemosphere, 2023)

Coupled thermal-hydro-mechanical modeling on characteristics of excavation damage zone around deep tunnels crossing a major fault - Bing Liu; Wen Meng; Zhihong Zhao; Tao Lin; Jintong Zhang (Tunnelling and Underground Space Technology, 2023)

Physiological response and photosynthetic recovery to an extreme drought: Evidence from plants in a dry-hot valley savanna of Southwest China - Da Yang; Yang-Si-Ding Wang; Qin Wang; Yan Ke; Yun-Bing Zhang; Shi-Bao Zhang; Yong-Jiang Zhang; Nate G. McDowell; Jiao-Lin Zhang (Science of The Total Environment, 2023)

Understanding the 0 + + and 2 + + charmonium(-like) states near 3.9 GeV - Teng Ji; Xiang-Kun Dong; Miguel Albaladejo; Meng-Lin Du; Feng-Kun Guo; Juan Nieves; Bing-Song Zou (Science Bulletin, 2023)

Prevalence and Subtype Distribution of Blastocystis in Tibetan Sheep in Qinghai Province, Northwestern China - Fan Yang; Jing-min Gou; Bing-ke Yang; Jia-yue Du; Hui-zhong Yao; Mei Ren; Qing Lin (Protist, 2023)

Water transport in continental subduction zones: Constraints from eclogite from the Dabie orogen, east-central China - Zhi-Min Wang; Ren-Xu Chen; Yong-Fei Zheng; Shuning Li; Lin Zhu; Bing Gong; Xiang-Ping Zha; Wan-Cai Li (Journal of Asian Earth Sciences, 2023)

Recent advances in photochemical transformations using water as an oxygen source - Yan Liu; Lin Zuo; Qiyan Lv; Bing Yu (Current Opinion in Green and Sustainable Chemistry, 2023)

Mechanism study on gliding arc (GA) plasma reforming: Reaction and energy pathways for H2 production from methanol steam reforming - Zhuo-Wen Xue; Jing-Lin Liu; Zhi-Yuan Zhang; Hemedi Kitila; Hao-Yu Lian; Bing Sun; Ai-Min Zhu (Chemical Engineering Journal, 2023)

Unraveling Photothermal-Enhanced bulk charge transport and surface oxygen reactions in TiO2 photoanodes for highly efficient photoelectrochemical water oxidation - Jing Huang; Xiaoqin Hu; Jingnan Wang; Kaijie Lin; Bing He; Yingkui Yang; Yang Wang; Zhen Li; Xueqin Liu (Chemical Engineering Journal, 2023)

Visible-light-driven selective cleavage of C C bonds in lignin model substrates using carbon nitride-supported ruthenium single-atom catalyst - Jun Deng; Chi Zhou; Yue Yang; Bing Nan; Lin Dong; Lingchao Cai; Lina Li; Zhu-Jun Wang; Xiaofei Yang; Zupeng Chen (Chemical Engineering Journal, 2023)

Quantitative characterization of filamentous fungal promoters on a single-cell resolution to discover cryptic natural products - Peng-Lin Wei; Jie Fan; Jingwen Yu; Zihui Ma; Xian Guo; Nancy P. Keller; Erwei Li; Chunbo Lou; Wen-Bing Yin (Science China Life Sciences, 2023)

Human umbilical cord mesenchymal stem cell-derived exosomes carrying miR-1827 downregulate SUCNR1 to inhibit macrophage M2 polarization and prevent colorectal liver metastasis - Jierong Chen; Ziyue Li; Caifeng Yue; Jianhong Ma; Lixue Cao; Jiaxin Lin; Dandan Zhu; Ran An; Jinxin Lai; Yunmiao Guo; Bing Gu (Apoptosis, 2023)

Biosensors for detection of paralytic shellfish toxins: Recognition elements and transduction technologies - Liu-Na Wei; Lin Luo; Bing-Zhi Wang; Hong-Tao Lei; Tian Guan; Yu-Dong Shen; Hong Wang; Zhen-Lin Xu (Trends in Food Science & Technology, 2023)

Loss of tidal creek ecosystem vitality caused by tidal flat narrowing on the central Jiangsu coast, China - Xuezhong Fan; Liquan Zhang; Lin Yuan; Bing Guo; Qinglong Zhang; Yangang Wang; Qian Wu (Science of The Total Environment, 2023)

Improved dynamic event-triggered anti-unwinding control for autonomous underwater vehicles - Ziyi Su; Xiaogong Lin; Bing Huang; Dawei Zhao; Han Sun (Ocean Engineering, 2023)

Mechanisms, application advances and future perspectives of microbial-induced heavy metal precipitation: A review - Hai Lin; Mengying Zhou; Bing Li; Yingbo Dong (International Biodeterioration & Biodegradation, 2023)

Potential of kerosene-diesel blends as alternative fuels for diesel engines: Perspectives from spray combustion characteristics - Zhaowen Wang; Xiaojie Li; Lin Xiang; Yuhan Huang; Bing Lang; Xiaobei Cheng; Jie Zhang (Fuel, 2023)

Effects of palm olein and palm stearin on cecal and fecal microbiota of C57BL/6J mice under low and high fat intakes - Liting Wan; Lin Li; Xia Zhang; Bing Li; Janette M. Harro; Mark E. Shirtliff (Food Chemistry, 2023)

Performance and application of a novel drainage anti-slide pile on accumulation landslide with a chair-like deposit-bedrock interface in the Three Gorges Reservoir area, China - Shi-lin Luo; Da Huang; Jian-bing Peng; Ailifeila Aierken; Zhao Li; Xi-bin Kuang; Roberto Tomás (Computers and Geotechnics, 2023)

Development and application of DETECTR-based rapid detection for pathogenic Bacillus anthracis - Jianhao Xu; Xinru Bai; Xianglilan Zhang; Bing Yuan; Lei lin; Yan Guo; Yujun Cui; Jinxiong Liu; Hongyu Cui; Xiangang Ren; Jinglin Wang; Yuan Yuan (Analytica Chimica Acta, 2023)

Corrigendum to “Screening and evaluation of heavy metals facilitating antibiotic resistance gene transfer in a sludge bacterial community” [Sci. Total Environ. 695 (2019) 133862] - Hai Lin; Lintian Jiang; Bing Li; Yingbo Dong; Yinhai He; Yong Qiu (Science of The Total Environment, 2023)

Triclocarban and triclosan exacerbate high-fat diet-induced hepatic lipid accumulation at environmental related levels: The potential roles of estrogen-related receptors pathways - Xin Li; Jia-Da Zhang; Han Xiao; Sen He; Ting-Ting He; Xiao-Min Ren; Bing-Hua Yan; Lin Luo; Yu-Long Yin; Lin-Ying Cao (Science of The Total Environment, 2023)

Spatial effects of urban green infrastructure on instream water quality assessed by chemical and sensory indicators - Juan Li; Shen Yu; Bing Hong; Ruihan Lin; Qi Li; Linlin Zhang; Tao Lin; Haifeng Jia; Dawen Yang; Chengwei Gu; Qimeng Jia (Science of The Total Environment, 2023)

Biotransformation of sulfamethoxazole (SMX) by aerobic granular sludge: Removal performance, degradation mechanism and microbial response - Bing Zhang; Yuankai He; Wenxin Shi; Lanjin Liu; Lin Li; Chong Liu; Piet N.L. Lens (Science of The Total Environment, 2023)

Polyketides with antimicrobial activities from Penicillium canescens DJJ-1 - Jia-Peng Wang; Yan Shu; Sheng-Qi Zhang; Lin-Lin Yao; Bing-Xian Li; Li Zhu; Xiao Zhang; Huai Xiao; Le Cai; Zhong-Tao Ding (Phytochemistry, 2023)

Insight into modified biochars and their immobilizing effects on heavy metal(loid)s in contaminated soils: Mechanisms and influencing factors - Ehma Rose GUERET YADIBERET MENZEMBERE; Yinhai HE; Yingbo DONG; Bing LI; Chenjing LIU; Hai LIN; Lengue SAMBIANI (Pedosphere, 2023)

Antibacterial activity and mechanism of action of bacteriocin LFX01 against Staphylococcus aureus and Escherichia coli and its application on pork model - Wei-Gang Xin; Gang Wu; Jian-Ping Ying; Yi-Zhou Xiang; Yu-Hang Jiang; Xian-Yu Deng; Lian-Bing Lin; Qi-Lin Zhang (Meat Science, 2023)

Relationship between sediment load and climate extremes in the major Chinese rivers - Yatong Zhang; Peng Tian; Lin Yang; Guangju Zhao; Xingmin Mu; Bing Wang; Pengfei Du; Peng Gao; Wenyi Sun (Journal of Hydrology, 2023)

Structural and energetic basis of interaction between human estrogen-related receptor γ and environmental endocrine disruptors from multiple molecular dynamics simulations and free energy predictions - Lin Chen; Xu Huang; Yufei Li; Bing Zhao; Min Liang; Ruige Wang (Journal of Hazardous Materials, 2023)

Rapid reduction of Cr(VI) with plant leaves: Implications for ex-situ phytoremediation of chromium-polluted waters in cold region - Yu Fu; Lingli Wang; Yunjiao Liu; Meiru Hou; Qingchao Li; Xiaodie Li; Dagang Lin; Jialin Chen; Zhaohui Wang; Bing Xie (Journal of Cleaner Production, 2023)

Solvent-free oxidation of toluene to benzaldehyde using electron-rich Au clusters confined in Silicalite-1 - He Huang; Huahua Fan; Yuzhen Ge; Wanyue Ye; Yingcen Liu; Caicheng Song; Hua Lin; Xiaotong Zhang; Bing Li; Xiaowa Nie; Shufen Zhang; Rongwen Lu (Chemical Engineering Journal, 2023)

In-situ construction and repair of high catalytic activity interface on corrosion-resistant high-entropy amorphous alloy electrode for hydrogen production in high-temperature dilute sulfuric acid electrolysis - Yangzheng Li; Junlei Tang; Hailong Zhang; Yingying Wang; Bing Lin; Jichao Qiao; Hongpeng Zheng; Zongxue Yu; Yiding Liu; Taigang Zhou; Xianzhang Lei (Chemical Engineering Journal, 2023)

Catalytic activity enhancement by P and S co-doping of a single-atom Fe catalyst for peroxymonosulfate-based oxidation - Yin Li; Jiahui Hu; Yubin Zou; Lin Lin; Hebin Liang; Huaxin Lei; Bing Li; Xiao-yan Li (Chemical Engineering Journal, 2023)

Discovery of inhibitors against SARS-CoV-2 main protease using fragment-based drug design - Hai Ping Shao; Tian Hua Wang; Hong Lin Zhai; Ke Xin Bi; Bing Qiang Zhao (Chemico-Biological Interactions, 2023)

Establishment of an efficient method for kiwifruit in vitro micrografting - Wantian Yao; Lingling Kong; Diya Lei; Bing Zhao; Honglan Tang; Xuan Zhou; Yuanxiu Lin; Yunting Zhang; Yan Wang; Wen He; Mengyao Li; Qing Chen; et al. (Plant Cell, Tissue and Organ Culture (PCTOC), 2023)

Expression of Concern: Folic acid rivals methylenetetrahydrofolate reductase (MTHFR) gene-silencing effect on MEPM cell proliferation and apoptosis - Wen-lin Xiao; Min Wu; Bing Shi (Molecular and Cellular Biochemistry, 2023)

Enhanced immobility of Pb(II) during ferrihydrite-Pb(II) coprecipitates aging impacted by malic acid or phosphate - Jinlong Peng; Fenglian Fu; Lin Zhang; Bing Tang; Xiangdan Zhang (Environmental Science and Pollution Research, 2023)

Mapping Chinese annual gross primary productivity with eddy covariance measurements and machine learning - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Shi-Ping Chen; Shao-Min Liu; Hui-Min Wang; Jun-Hua Yan; Jun-Lei Tan; Fa-Wei Zhang; et al. (Science of The Total Environment, 2023)

Evaluation of eight psychoactive drugs used in Chinese cities by wastewater-based epidemiology - Xue-Ting Shao; Si-Yu Liu; Yue-Tong Zhao; Bing Jiang; Jian-Guo Lin; De-Gao Wang (Science of The Total Environment, 2023)

Corrigendum to “Comparative efficacy of omega-3 polyunsaturated fatty acids on major cardiovascular events: A network meta-analysis of randomized controlled trials” [Progress in Lipid Research. 2022 Oct 28;88:101196. doi: 10.1016/j.plipres.2022.101196] - Bo Yang; Ping-Tao Tseng; Xiang Hu; Bing-Yan Zeng; Jane Pei-Chen Chang; Yang Liu; Wei-Jie Chu; Shuang-Shuang Zhang; Zhi-Liang Zhou; Chih-Sheng Chu; Cheng-Ho Chang; Yu-Kang Tu; et al. (Progress in Lipid Research, 2023)

Experimental study on the distribution law of the blade foot resistance of a large deep-water open caisson in sand - Bing-nan Jiang; Ting Yu; Wen-ming Peng; Ying-bin Zhang; Shun-bin He; Jian-lin Ma (Ocean Engineering, 2023)

Petrogenesis of high heat production granite in eastern Hebei Province, China: Constraints from geochronology, geochemistry and Sr-Nd-Hf-O isotopes - Tao Zhang; De-Hui Zhang; Xiang-Chong Liu; Hua-Ning Qiu; Ji-Lin Zhang; Yan-Bing Liu (Lithos, 2023)

Hemin protects UVB-induced skin damage through inhibiting keratinocytes apoptosis and reducing neutrophil infiltration - Fang Bai; Chen Fan; Xi Lin; Hao-Yu Wang; Bing Wu; Chun-Lan Feng; Rong Zhou; Yan-Wei Wu; Wei Tang (Journal of Photochemistry and Photobiology B: Biology, 2023)

New insights into lincomycin biodegradation by Conexibacter sp. LD01: Genomics characterization, biodegradation kinetics and pathways - Huaxin Lei; Jiayu Zhang; Jin Huang; Dengjin Shen; Yin Li; Rui Jiao; Renxin Zhao; Xiaoyan Li; Lin Lin; Bing Li (Journal of Hazardous Materials, 2023)

Novel multifunctional natural selenium supplement development, in vitro and in vivo analysis, and risk-benefit assessment: Selenium-enriched chicory as a case study - Yaolei Li; Shanshan Ju; Jinjian Huang; Hao Wu; Zhijian Lin; Yu Wang; Hongyu Jin; Shuangcheng Ma; Bing Zhang (Journal of Cleaner Production, 2023)

A capacitive deionization and electro-oxidation hybrid system for simultaneous removal of heavy metals and organics from wastewater - Wutong Chen; Xin He; Zekai Jiang; Bing Li; Xiao-yan Li; Lin Lin (Chemical Engineering Journal, 2023)

Rapid Determination in the Quality Control of Chinese Patent Medicine - Shao Hua Lu; Ming Cai Zhang; Hong Lin Zhai; Ke Xin Bi; Bing Qiang Zhao (Journal of Pharmaceutical Innovation, 2022)

Release of Endogenous Brain-derived Neurotrophic Factor into the Lateral Entorhinal Cortex from the Paraventricular Thalamus Ameliorates Social Memory Deficits in a Mouse Model of Alzheimer’s Disease - Yun-Long Xu; Lin Zhu; Zi-Jun Chen; Xiao-Fei Deng; Pei-Dong Liu; Shan Li; Bing-Chun Lin; Chuan-Zhong Yang; Wei Xu; Kui-Kui Zhou; Ying-Jie Zhu (Neuroscience Bulletin, 2022)

Novel and sustainable carboxylation of terminal alkynes and CO2 to alkynyl carboxylic acids using triazolium ionic liquid-modified PMO-supported transition metal acetylacetonate as effective cooperative catalysts - Jing-Rui Li; Chen Chen; Xiao-Bing Liu; Yu-Lin Hu (Environmental Science and Pollution Research, 2022)

Interaction between seawater carbon dioxide dynamics and stratification in shallow coastal waters: A preliminary study based on a weekly validated three-dimensional ecological model - Bing Xiong; Shinichiro Yano; Katsuaki Komai; Naoki Saito; Hiroto Komori; Baixin Chi; Lin Hao; Keisuke Nakayama (Frontiers in Marine Science, 2022)
Shallow coastal waters (SCWs) have attracted wide attention in recent years due to their strong carbon sequestration capacity. However, the complex carbon dioxide (CO 2 ) dynamics in the water column makes it difficult to estimate the air–water CO 2 fluxes (F CO2 ) accurately. We developed a numerical model of CO 2 dynamics in water based on field measurements for a typical stratified semi-enclosed shallow bay: the Yatsushiro Sea, Japan. The developed model showed an excellent ability to reproduce the stratification and CO 2 dynamics of the Yatsushiro Sea. Through numerical model simulations, we analyzed the annual CO 2 dynamics in the Yatsushiro Sea in 2018. The results show that the effect of stratification on the CO 2 dynamics in seawater varies greatly depending on the distance from the estuary and the period. In the estuarine region, stratification manifests itself throughout the year by promoting the maintenance of a high partial pressure of CO 2 (pCO 2 ) in surface waters, resulting in surface pCO 2 being higher than atmospheric pCO 2 for up to 40 days during the flood period (average surface pCO 2 of 539.94 µatm). In contrast, in areas farther from the estuary, stratification mainly acts to promote the maintenance of high pCO 2 in surface waters during periods of high freshwater influence. Then changes to a lower surface pCO 2 before the freshwater influence leads towards complete dissipation. Finally, we estimated the F CO2 of the Yatsushiro Sea in 2018, and the results showed that the Yatsushiro Sea was a sink area for atmospheric CO 2 in 2018 (−1.70 mmol/m 2 /day).

New loci for refractive errors and ocular biometric parameters in young Chinese Han adults - Yunyun Sun; Zi-Bing Jin; Shifei Wei; Hongyan Jia; Kai Cao; Jianping Hu; Caixia Lin; Wenzai An; Jiyuan Guo; He Li; Jing Fu; Shi-Ming Li; et al. (Science China Life Sciences, 2022)

Measuring the phase response of a seismometer using superimposed sine signals - Zhan Lin; Yuntian Teng; Bing Xue; Xinxin Ma (Journal of Seismology, 2022)

How to improve the problem of hotel manpower shortage in the COVID-19 epidemic environment? Exploring the effectiveness of the hotel practice training system - Bing-Wang Xue; Hsiao-Hsien Lin; Chao-Chien Chen; Peng-Yeh Lee; Chin-Hsien Hsu (Environmental Science and Pollution Research, 2022)

Maintenance of Epstein-Barr virus latency through interaction of LMP2A with CXCR4 - Ni Qin; Yan Zhang; Lin Xu; Wen Liu; Bing Luo (Archives of Virology, 2022)

Functional analysis of HADH c.99C>G shows that the variant causes the proliferation of pancreatic islets and leu-sensitive hyperinsulinaemia - Wu Long; Yue-Bing Wang; Peng-Fei Qu; Lin Ma; Si-Jie Wei; Yan-Mei Xi; Jin-Liang Du; Xue Tang; Kai Liu; Yu-Hua Li; Pu-Ping Lei (Journal of Genetics, 2022)

L-Selenocysteine induced HepG-2 cells apoptosis through reactive oxygen species-mediated signaling pathway - Kaiying Zhang; Jingyao Su; Danyang Chen; Binger Lin; Yucan Wu; Yibing Wang; Jiapei Lei; Ruilin Zheng; Bing Zhu; Yinghua Li (Molecular Biology Reports, 2022)

Chromosomal mapping of a locus associated with adult-stage resistance to powdery mildew from Agropyron cristatum chromosome 6PL in wheat - Yida Lin; Shenghui Zhou; Xuezhong Liang; Baojin Guo; Bing Han; Haiming Han; Jingpeng Zhang; Yuqing Lu; Zhi Zhang; Xinming Yang; Xiuquan Li; Weihua Liu; et al. (Theoretical and Applied Genetics, 2022)

REGγ drives Lgr5+ stem cells to potentiate radiation induced intestinal regeneration - Xiangzhan Zhu; Minglei Yang; Zaijun Lin; Solomon Kibreab Mael; Ya Li; Lili Zhang; Yaqi Kong; Yaodong Zhang; Yuping Ren; Jianhui Li; Zimeng Wang; Ying Zhang; et al. (Science China Life Sciences, 2022)

A strategy for establishing an efficient somatic embryo regeneration system in Castanea mollissima Blume - Xiao-wei Li; Zhi-lin Sun; Yue-rong Gao; Jing-yi Ge; Yu-zhen Tian; Bing Liu; Shi-kan Sun; Ke-feng Fang; Ling Qin; Qing-qin Cao (Plant Cell, Tissue and Organ Culture (PCTOC), 2022)

Copper ore material footprints and transfers embodied in domestic and international trade of provinces in China - Lin Liu; Heinz Schandl; James West; Meng Jiang; Zijian Ren; Dingjiang Chen; Bing Zhu (Journal of Industrial Ecology, 2022)
Copper is a critical material for development and plays a profound role in transitioning to a low‐carbon future. China is the main copper consumer in recent decades that has a fast‐growing domestic market accompanied by active international trade. Given the large regional differences within China, it is relevant to understand the domestic driving forces of copper demands and the cascading effects on international regions. Here we combine the newly developed copper ore extraction datasets and the Chinese interprovincial nested global multi‐regional input–output models to explore the copper ore material footprints (CuMF), the interprovincial CuMF transfers, and the international CuMF transfers of provinces. Results show that at the initial stage of clean energy development (2007–2012), most provinces in China are, to a great degree (∼50%), relatively reliant on international copper inputs. The manufacturing sector is the main driving force of international CuMF transfers while the construction sector drives most interprovincial CuMF transfers, with the total volume of international CuMF transfers recently tripling. The central provinces in the industrial transition period and the northwestern provinces in the initial development stage saw the fastest growth in international and interprovincial CuMF transfers, respectively. The economic growth and low‐carbon transition will further advance copper‐related manufacturing and construction activities while other evidences indicate that the degree of foreign inputs to meet copper demand may peak and the interprovincial supply may rise continuously. Targeted governance of these sectors may effectively reduce high dependence on the international copper supply and ensure an efficient interprovincial CuMF transfer pattern.

Assessing the effective spatial characteristics of input features through physics-informed machine learning models in inundation forecasting during typhoons - Bing-Chen Jhong; Chung-Yi Lin; You-Da Jhong; Hsiang-Kuan Chang; Jung-Lien Chu; Hsi-Ting Fang (Hydrological Sciences Journal, 2022)

Registered clinical trials investigating treatment of long COVID: a scoping review and recommendations for research - Felicia Ceban; Alexia Leber; Muhammad Youshay Jawad; Mathew Yu; Leanna M. W. Lui; Mehala Subramaniapillai; Joshua D. Di Vincenzo; Hartej Gill; Nelson B. Rodrigues; Bing Cao; Yena Lee; Kangguang Lin; et al. (Infectious Diseases, 2022)

Real-time Neural-network-based Ensemble Typhoon Flood Forecasting Model with Self-organizing Map Cluster Analysis: A Case Study on the Wu River Basin in Taiwan - You-Da Jhong; Hsin-Ping Lin; Chang-Shian Chen; Bing-Chen Jhong (Water Resources Management, 2022)

Fine particulate matter measured by satellites predicts the risk of age-related macular degeneration in a longitudinal cohort study - Chung-Ling Liang; Chi-Min Wang; Chau-Ren Jung; Ya-Chu Chang; Chun-Ju Lin; Yu-Ting Lin; Bing-Fang Hwang (Environmental Science and Pollution Research, 2022)

Synthesis of polyaminophosphonated-functionalized hydrochar for efficient sorption of Pb(II) - Bing Li; Jia-Lin Liu; Huan Xu (Environmental Science and Pollution Research, 2022)

Widespread refertilization of cratonic lithospheric mantle related to circum-craton plate subduction: evidence from peridotite xenoliths from the central North China Craton - Yao Xu; Hong-Fu Zhang; A-Bing Lin (Contributions to Mineralogy and Petrology, 2022)

Cerebellar Oscillations in Familial and Sporadic Essential Tremor - Shi-Bing Wong; Yi-Mei Wang; Chih-Chun Lin; Scott Kun Geng; Nora Vanegas-Arroyave; Seth L. Pullman; Sheng-Han Kuo; Ming-Kai Pan (The Cerebellum, 2022)

Knockout of GGPPS1 restrains rab37-mediated autophagy in response to ventilator-induced lung injury - Zexu Wang; Meizi Chen; Xia Pan; Li Wang; Cheng Yin; Qiuqi Lin; Jingjing Jiang; Yunlei Zhang; Bing Wan (Human Cell, 2022)

The effect of preoperative statin treatment on acute kidney injury in elderly patients undergoing valve replacement surgery - Bing-qi Fu; Xue-biao Wei; Zedazhong Su; Ying-wen Lin; Zu-hui Ke; Tong Tan; Ji-yan Chen; Shou-hong Wang; Dan-qing Yu (European Journal of Clinical Pharmacology, 2022)

Socioeconomic Patterns for Global Mangrove Cover Changes with Multi-Database Analyses - Ruihan Lin; Shen Yu; Bing Hong (Wetlands, 2022)

Transcriptome Analysis Reveals Molecular Mechanisms Underlying Methyl Jasmonate-mediated Biosynthesis of Protopanaxadiol-type Saponins in Panax notoginseng Leaves - Ying Li; Yuan Lin; Bing Jia; Geng Chen; Huineng Shi; Rui Xu; Xuejiao Li; Junrong Tang; Qingyan Tang; Guanghui Zhang; Jianli Yang; Wei Fan; et al. (Journal of Plant Biology, 2022)

Simultaneous high-efficiency removal of sulfamethoxazole and zinc (II) from livestock and poultry breeding wastewater by a novel dual-functional bacterium, Bacillus sp. SDB4 - Xi Chen; Hai Lin; Yingbo Dong; Bing Li; Tingting Yin; Chenjing Liu (Environmental Science and Pollution Research, 2022)

Halomonas populi sp. nov. isolated from Populus euphratica - Lin Xu; Jun-Jie Ying; Yuan-Chun Fang; Ran Zhang; Jia Hua; Min Wu; Bing-Nan Han; Cong Sun (Archives of Microbiology, 2022)

Association between exposure to road traffic noise and hearing impairment: a case-control study - Tang-Chuan Wang; Ta-Yuan Chang; Richard S. Tyler; Bing-Fang Hwang; Yi-Hung Chen; Che-Ming Wu; Chiu-Shong Liu; Kuang-Chao Chen; Chia-Der Lin; Ming-Hsui Tsai (Journal of Environmental Health Science and Engineering, 2021)

Microplastics in Mollusks: Research Progress, Current Contamination Status, Analysis Approaches, and Future Perspectives - Ruixuan Wang; Hongli Mou; Xiaozhi Lin; Hui Zhu; Bing Li; Jiangyong Wang; Muhammad Junaid; Jun Wang (Frontiers in Marine Science, 2021)
Plastic fragments < 5 mm, known as microplastics (MPs), are ubiquitously present in the marine environment. Research on MPs pollution has gradually shifted from field investigations to laboratory studies. With the rapid growth of plastic consumption and the prevalence of aquaculture products, studies on marine MPs have focused on key marine species, such as mollusks. This review summarizes the recent knowledge including 77 important relevant literatures (from 2010 to 2021) on MPs contamination in mollusks with the objectives of (1) elucidating the current status of MPs pollution levels in mollusks, (2) highlighting the main methods and techniques for separation, extraction, and identification of MPs in soft tissues of bivalves and (3) presenting the current research progress and future directions. The review visually presents some of the important results in graphic form, which shows that the most common polymer plastics in bivalves are polypropylene, polystyrene, and polyethylene, and the shapes were mainly fiber and threadiness, mollusks are more likely to feed smaller MPs, most of the MPs in bivalves are less than 500 μm, and the abundance of MPs in seawater and the abundance of MPs in mollusks have a positive relationship, etc. This review will provide a comprehensive reference for studies of microplastics in marine organisms and the ecological pollution, and also has scientific guiding significance in the research method.

Two new pyrrolidine alkaloids from the red alga Acanthophora spicifera - Zhuo-Bin Guan; Yong-Qian Liang; Jia-Li Lin; Xiao-Jian Liao; Shi-Hai Xu; Bing-Xin Zhao (Natural Product Research, 2021)

3D-QSAR-aided toxicity assessment of synthetic musks and their transformation by-products - Xixi Li; Guangzhu Li; Bing Chen; Weiyun Lin; Baiyu Zhang (Environmental Science and Pollution Research, 2021)

Two new cephalochromin derivative from the Alternaria sp. ZG22 - Xin-Ming Song; Xue-Ming Zhou; Ya-Ling Li; Li-Bing Huang; Cai-Cui Chen; Yan Gao; Lin He; Xiao-qun Mao; Bing Chen; Jing-Wen Liu; Hui-Jie Liu; Xiao-Ping Song; et al. (Natural Product Research, 2021)

Close encounters of the worst kind: reforms needed to curb coral reef damage by recreational divers - Bing Lin (Coral Reefs, 2021)
Intentional and unintentional physical contact between scuba divers and the seabed is made by most divers and multiple times per dive, which often results in damage to corals and other marine life. Current efforts to reduce reef contacts (e.g., voluntary dive operator recognition programs and voluntary dive standards) can be effective, but lack sufficient incentive structures for long-term compliance. In their current capacity, these programs fail to reduce reef contacts to tolerable levels. Regulatory policies can facilitate pervasive and permanent shifts in human behavior, but have been underutilized to change unsustainable underwater norms. Most coral reefs open to recreational diving lie within territorial waters of individual countries, and many already have existing forms of protection with legislation that can be easily modified. Successful policy precedents in Marine Protected Areas (e.g., bans on underwater glove use) and elsewhere (e.g., anti-smoking laws in public spaces and legislation enforcing seat belt use) demonstrate the largely untapped potential of using effective governance to change destructive diving norms for good. To reduce intentional reef contacts, policy-makers can enact regulations in MPAs directly banning all contact between divers and the seabed. To reduce unintentional contacts, policy-makers can create policy safeguards that preempt such occurrences (e.g., requiring divers to keep a certain distance from the seabed). Crucially, such policies will need accompanying formal and informal enforcement measures that are equitable, effective, and efficient to motivate compliance and effect lasting behavior change. Having a robust, well-enforced, regulatory framework to tackle both types of reef contacts lends credence to the efforts of existing conservation programs, and is key to permanently changing divers’ underwater attitudes and fostering sustainable scuba diving behavior to the benefit of all.

Shared and specific patterns of structural and functional thalamo-frontal disturbances in manic and euthymic pediatric bipolar disorder - Yi-Bing Guo; Wei-Jia Gao; Zhi-Liang Long; Wei-Fang Cao; Dong Cui; Yong-Xin Guo; Qing Jiao; Jian-Feng Qiu; Lin-Yan Su; Guang-Ming Lu (Brain Imaging and Behavior, 2021)
Bipolar disorder (BD) is clinically defined by alternating depressive and manic episodes with a separated period of euthymia. Thalamo-frontal loop plays vital role in psychotic symptoms, altered motor control and executive difficulties in BD. It remains unclear that structural and functional alterations of thalamo-frontal loop among the different mood states in BD, especially in pediatric BD(PBD). Twenty manic PBD (mPBD), 20 euthymic PBD (ePBD) and 19 healthy controls (HCs) were included in the study. By analyzing the T1 images and fMRI signals, thalamus volume and frontal grey matter cortical thickness were tested, and functional connectivity (FC) between bilateral thalamus and frontal cortex was calculated. Relationship between clinical indices and thalamo-frontal FC was also evaluated in mPBD and ePBD adolescents. Compared to HCs, the cortical thickness of left middle frontal gyrus (MFG), bilateral superior frontal gyrus (SFG) was significantly decreased in both mPBD and ePBD patients, and volume of left thalamus and cortical thickness of right MFG significantly decreased in mPBD patients. Compared to that of the HCs and ePBD subjects, thalamo-frontal hyperconnectivity with MFG was found in mPBD, and compared with that of HCs, thalamo-frontal hypoconnectivity with precentral gyrus/SFG was found in ePBD. In ePBD patients, episode times positively correlated with FC values between thalamus and precentral gyrus. The findings of the present study demonstrate detailed knowledge regarding shared and specific structural and functional disruption in thalamo-frontal loop in mPBD and ePBD subjects. Thalamo-frontal abnormalities reported in adult BD subjects were also observed in adolescent BD patients, and thalamo-frontal dysfunction may be a crucial treatment target in BD.

Marinomonas vulgaris sp. nov., a marine bacterium isolated from seawater in a coastal intertidal zone of Zhoushan island - Jun-Jie Ying; Yuan-Chun Fang; Yong-Lian Ye; Zhi-Cheng Wu; Lin Xu; Bing-Nan Han; Cong Sun (Archives of Microbiology, 2021)

Protective effect of Bombyx mori gloverin on intestinal epithelial cells exposure to enterotoxigenic E. coli - Qian Lin; Qingqing Fu; Guoqi Su; Daiwen Chen; Bing Yu; Yuheng Luo; Ping Zheng; Xiangbing Mao; Zhiqing Huang; Jie Yu; Junqiu Luo; Hui Yan; et al. (Brazilian Journal of Microbiology, 2021)

Mild encephalitis/encephalopathy with a reversible splenial lesion associated with respiratory syncytial virus infection in infants - Xue-Lin Li; Jinming Han; Zhong-Rui Yan; Bing-Wei Zhang; Hai-Yang Wang (Journal of NeuroVirology, 2021)

Defense of COVID-19 by Human Organoids - Ting Lv; Fanlu Meng; Meng Yu; Haihui Huang; Xinhua Lin; Bing Zhao (Phenomics, 2021)

LncRNA RNCR3 promotes endothelial cell proliferation and inflammatory cytokine secretion via regulating miR-185-5p/cyclin D2 axis - Quanlong Hong; Lin Ling; Wenli Huang; Yilan Liu; Yafen Zhuo; Zhenzhen Hong; Bing Wu; Yi Zhang (Environmental Science and Pollution Research, 2021)

Cytotoxic meroterpenoids from the marine sponge Dactylospongia elegans - Hao-Bing Yu; Zi-Fei Yin; Bin-Bin Gu; Jian-Peng Zhang; Shu-Ping Wang; Fan Yang; Hou-Wen Lin (Natural Product Research, 2021)

Identification of two UDP-glycosyltransferases involved in the main oleanane-type ginsenosides in Panax japonicus var. major - Jun-Rong Tang; Geng Chen; Ying-Chun Lu; Qing-Yan Tang; Wan-Ling Song; Yuan Lin; Ying Li; Su-Fang Peng; Sheng-Chao Yang; Guang-Hui Zhang; Bing Hao (Planta, 2021)

Prediction of oral hepatotoxic dose of natural products derived from traditional Chinese medicines based on SVM classifier and PBPK modeling - Size Li; Yiqun Yu; Xiaolan Bian; Li Yao; Min Li; Yan-Ru Lou; Jing Yuan; Hai-shu Lin; Lucy Liu; Bing Han; Xiaoqiang Xiang (Archives of Toxicology, 2021)

Structure of SARS-CoV-2 main protease in the apo state - Xuelan Zhou; Fanglin Zhong; Cheng Lin; Xiaohui Hu; Yan Zhang; Bing Xiong; Xiushan Yin; Jinheng Fu; Wei He; Jingjing Duan; Yang Fu; Huan Zhou; et al. (Science China Life Sciences, 2021)

Human β-Defensin 118 Attenuates Escherichia coli K88–Induced Inflammation and Intestinal Injury in Mice - Qian Lin; Qingqing Fu; Xiang Li; Yuheng Luo; Junqiu Luo; Daiwen Chen; Xiangbing Mao; Bing Yu; Ping Zheng; Zhiqing Huang; Jie Yu; Hui Yan; et al. (Probiotics and Antimicrobial Proteins, 2021)

Activating Transcription Factor 6 Contributes to Functional Recovery After Spinal Cord Injury in Adult Zebrafish - Zhe Ji; Zhi-Lan Zhou; Qin Hao; Lin Zhao; Chun Cui; Shu-Bing Huang; Yan-Ling Yang; Yan-Qin Shen (Journal of Molecular Neuroscience, 2021)

Molecular cloning and functional characterization of the hypoxia-inducible factor-1α in bighead carp (Aristichthys nobilis) - Yan Lin; Ling-Hong Miao; Bo Liu; Bing-Wen Xi; Liang-Kun Pan; Xian-Ping Ge (Fish Physiology and Biochemistry, 2021)

A review on furan: Formation, analysis, occurrence, carcinogenicity, genotoxicity and reduction methods - Zahra Batool; Dan Xu; Xia Zhang; Xiaoxi Li; Yuting Li; Zhiyi Chen; Bing Li; Lin Li (Critical Reviews in Food Science and Nutrition, 2021)

Genome-wide analysis of CBL and CIPK family genes in cotton: conserved structures with divergent interactions and expression - Weinan Sun; Bing Zhang; Jinwu Deng; Lin Chen; Abid Ullah; Xiyan Yang (Physiology and Molecular Biology of Plants, 2021)

Community structure of bacterioplankton and its relationship with environmental factors in the upper reaches of the Heihe River in Qinghai Plateau - Zhang Qian‐Qian; Jian Sheng‐Long; Li Ke‐Mao; Wu Zhen‐Bing; Guan Hong‐Tao; Hao Jin‐Wen; Wang Shu‐Yi; Lin Yao‐Yao; Wang Guo‐Jie; Li Ai‐Hua (Environmental Microbiology, 2021)
Summary Planktonic microorganisms play a key role in the biogeochemical processes of the aquatic system, and they may be affected by many factors. High‐throughput sequencing technology was used in this study to investigate and study the bacterioplankton community of water bodies in the upper reaches of the Heihe River Basin in Qinghai Plateau. Results showed that Proteobacteria, Firmicutes, Bacteroidetes and Actinobacteria are the predominant phyla in this river section, while the main genera are Thiomonas , Acidibacillus , Acidocella , Rhodanobacter , Acidithiobacter and Gallionella , which are autochthonous in the acid‐mine drainage. Additionally, total nitrogen, total phosphorus, permanganate index and pH are significantly correlated with the bacterioplankton abundance and are the main limiting factors for the spatial distribution of the bacterioplankton. PICRUSt inferred that the mainstream microbial assemblages had a higher abundance of KOs belong to metabolism of terpenoids and polyketides, while the tributary had higher abundance of KOs belong to the immune system. The relationship between bacterioplankton community composition and environmental factors in the Heihe River basin was discussed for the first time in this study, which provides a theoretical basis for the healthy, orderly development of the water environment in the Heihe River Basin.

Isolation and characterization of two new chroman-4-ones from the endophytic fungus Penicillium chrysogenum obtained from Eucommia ulmoides Oliver - Sheng-Yue Liu; Li-Zhi Wang; Yue-Fei Wang; Lin Li; Guo-Ying Han; Bing-Yang Zhang; Ying Guo; Yong-Zhi He; Shi-Ming Fang; Han Zhang (Natural Product Research, 2020)

Wave Attenuation by Spartina alterniflora under Macro-Tidal and Storm Surge Conditions - Xiaoxia Zhang; Pengzhi Lin; Zelin Gong; Bing Li; Xinping Chen (Wetlands, 2020)

Long non-coding RNA LINC00460 promotes proliferation and inhibits apoptosis of cervical cancer cells by targeting microRNA-503-5p - Lin Lin; Bing Xin; Tao Jiang; Xin-lu Wang; Hua Yang; Tie-mei Shi (Molecular and Cellular Biochemistry, 2020)

Gut dysbiosis-influence on amygdala-based functional activity in patients with end stage renal disease: a preliminary study - Li Juan Zheng; Li Lin; Jianhui Zhong; Zhihong Zhang; Yu Bing Ye; Xin Yuan Zhang; Yun Fei Wang; Han Zhang; Ya Liu; Guang Ming Lu; Dehua Gong; Long Jiang Zhang (Brain Imaging and Behavior, 2020)

The fate of dietary advanced glycation end products in the body: from oral intake to excretion - Zhili Liang; Xu Chen; Lin Li; Bing Li; Zhao Yang (Critical Reviews in Food Science and Nutrition, 2020)

Whether the carbon emission from green roofs can be effectively mitigated by recycling waste building material as green roof substrate during five-year operation? - Liangqian Fan; Jingting Wang; Xiaoling Liu; Hongbing Luo; Ke Zhang; Xiaoying Fu; Mei Li; Xiaoting Li; Bing Jiang; Jia Chen; Shuzhi Fu; You Mo; et al. (Environmental Science and Pollution Research, 2020)

Characterization of a Protease Hyper-Productive Mutant of Bacillus pumilus by Comparative Genomic and Transcriptomic Analysis - Yong-Cheng Liu; Lin-Li Han; Tian-Yu Chen; Yan-Bing Lu; Hong Feng (Current Microbiology, 2020)

Evaluation of the Impacts of Formulation Parameters on the Pharmacokinetics and Bioequivalence of Risperidone Orodispersible Film: a Physiologically Based Pharmacokinetic Modeling Approach - Fang Chen; Hongrui Liu; Bing Wang; Zhou Yang; Yusheng Chen; Liuliu Yang; Bing Wang; Zheng Jiao; Hai-Shu Lin; Yingjun Quan; Hao Wang; Xiaoqiang Xiang (AAPS PharmSciTech, 2020)

Chemical composition, antioxidant, antimicrobial and anticancer activities of the essential oil from the rhizomes of Zingiber striolatum Diels - Minyi Tian; Tingting Liu; Xianghuan Wu; Yi Hong; Xiongli Liu; Bing Lin; Ying Zhou (Natural Product Research, 2020)

Future trends and guidance for the triple bottom line and sustainability: a data driven bibliometric analysis - Ming-Lang Tseng; Chia-Hao Chang; Chun-Wei Remen Lin; Kuo-Jui Wu; Qing Chen; Li Xia; Bing Xue (Environmental Science and Pollution Research, 2020)
This study conducts a comprehensive literature review of articles on the triple bottom line (TBL) published from January 1997 to September 2018 to provide significant insights and support to guide further discussion. There were three booms in TBL publications, occurring in 2003, 2011, and 2015, and many articles attempt to address the issue of sustainability by employing the TBL. This literature analysis includes 720, 132, and 58 articles from the Web of Science (WOS), Inspec, and Scopus databases, respectively, and reveals the gaps in existing research. To discover the barriers and points of overlap, these articles are categorized into six aspects of the TBL: economic, environmental, social, operations, technology, and engineering. Examining the top 3 journals in terms of published articles on each aspect reveals the research trends and gaps. The findings provide solid evidence confirming the argument that the TBL as currently defined is insufficient to cover the entire concept of sustainability. The social and engineering aspects still require more discussion to support the linkage of the TBL and to reinforce its theoretical basis. Additionally, to discover the gaps in the data sources, theories applied, methods adopted, and types of contributions, this article summarizes 82 highly cited articles covering each aspect. This article offers theoretical insights by identifying the top contributing countries, institutions, authors, keyword networks, and authorship networks to encourage scholars to push the current discussion further forward, and it provides practical insights to bridge the gap between theory and practice for enhancing the efficiency and effectiveness of improvements.

Anthraquinone derivatives from a coral associated fungus Stemphylium lycopersici - Jiao Li; Yu-Bing Zheng; Tibor Kurtán; Ming-Xiang Liu; Hua Tang; Chun-Lin Zhuang; Wen Zhang (Natural Product Research, 2020)

Neo-debromoaplysiatoxin C, with new structural rearrangement, derived from debromoaplysiatoxin - Yang-Hua Tang; Ting-Ting Liang; Ting-Ting Fan; Lawrence Jordan Keen; Xiao-Dan Zhang; Lin Xu; Qi Zhao; Rong Zeng; Bing-Nan Han (Natural Product Research, 2020)

Acanthophoraine A, a new pyrrolidine alkaloid from the red alga Acanthophora spicifera - Jia-Li Lin; Yong-Qian Liang; Xiao-Jian Liao; Jian-Ting Yang; Dai-Chun Li; Yu-Ling Huang; Zhi-Hui Jiang; Shi-Hai Xu; Bing-Xin Zhao (Natural Product Research, 2020)

A new epicatechin glucopyranoside derivative from Styrax suberifolius - Bing-Lei Liu; Xin Hu; Hua-Liang He; Lin Qiu; You-Zhi Li; Wen-Bing Ding (Natural Product Research, 2020)

Comparative transcriptomic analysis of fireflies (Coleoptera: Lampyridae) to explore the molecular adaptations to fresh water - Qi‐Lin Zhang; Hong‐Wei Li; Zhi‐Xiang Dong; Xiao‐Jie Yang; Lian‐Bing Lin; Jun‐Yuan Chen; Ming‐Long Yuan (Molecular Ecology, 2020)
Aquatic insects are well adapted to freshwater environments, but the molecular basis of these adaptations remains largely unknown. Most firefly species (Coleoptera: Lampyridae) are terrestrial, but the larvae of several species are aquatic. Here, larval and adult transcriptomes from Aquatica leii (freshwater) and Lychnuris praetexta (terrestrial) were generated to test whether the genes associated with metabolic efficiency and morphology have undergone adaptive evolution to fresh water. The aquatic fireflies had a significantly lower ratio of nonsynonymous to synonymous substitutions than the terrestrial insects, indicating a genomewide evolutionary constraint in the aquatic fireflies. We identified 341 fast‐evolving genes and 116 positively selected genes in the aquatic fireflies. Of these, 76 genes exhibiting both fast evolution and positive selection were primarily involved in ATP production, energy metabolism and the hypoxia response. We identified 7,271 differentially expressed genes (DEGs) in A . leii (adults versus larvae) and 8,309 DEGs in L . praetexta (adults versus larvae). DEGs specific to the aquatic firefly ( n = 1,445) were screened via interspecific comparisons ( A . leii versus L . praetexta ) and were significantly enriched for genes involved in metabolic efficiency (e.g., ATP production, hypoxia, and immune responses) and certain aspects of morphology (e.g., cuticle chitin, tracheal and compound eye morphology). These results indicate that sequence and expression‐level changes in genes associated with both metabolic efficiency and morphological attributes related to the freshwater lifestyle contributed to freshwater adaptation in fireflies. This study provides new insights into the molecular mechanisms of aquatic adaptation in insects.

Short-term associations between ambient fine particulate matter pollution and hospital visits for chronic obstructive pulmonary disease in Yinzhou District, China - Cheng-yi Lin; Die Li; Jie-ming Lu; Zhe-bin Yu; Yao Zhu; Peng Shen; Meng-ling Tang; Ming-juan Jin; Hong-bo Lin; Li-ming Shui; Kun Chen; Jian-bing Wang (Environmental Science and Pollution Research, 2020)

Ribosome profiling analysis identified a KRAS-interacting microprotein that represses oncogenic signaling in hepatocellular carcinoma cells - Wenli Xu; Bing Deng; Penghui Lin; Chang Liu; Bin Li; Qiaojuan Huang; Hui Zhou; Jianhua Yang; Lianghu Qu (Science China Life Sciences, 2020)

Next-generation sequencing technology as a powerful detection and semi-quantitative method for herpes simplex virus type 1 in pediatric encephalitis - Lin-lin Liu; Ling-yun Guo; Jie Dong; Wen-hua Huang; Li Zhao; Bing Liu; Xi-xi Zhang; Yong-qiang Jiang; Gang Liu (Journal of NeuroVirology, 2020)

Impacts of irrigation methods on greenhouse gas emissions/absorptions from vegetable soils - Xuhong Ye; Hongdou Liu; Xichao Zhang; Jianhui Ma; Bing Han; Wen Li; Hongtao Zou; Yulong Zhang; Xiangui Lin (Journal of Soils and Sediments, 2020)

Glutamate and aspartate alleviate testicular/epididymal oxidative stress by supporting antioxidant enzymes and immune defense systems in boars - Wenjie Tang; Jian Wu; Shunshun Jin; Liuqin He; Qinlu Lin; Feijun Luo; Xingguo He; Yanzhong Feng; Binsheng He; Pingping Bing; Tiejun Li; Yulong Yin (Science China Life Sciences, 2020)

Evaluation on activation energy of deposited clay based on thermo-gravimetric analysis (TGA) and four kinetics models - Rui-xin Yan; Jian-bing Peng; Yan-jun Shen; Yu-liang Zhang; Lin-jun Gu; Shao-kai Wang (Bulletin of Engineering Geology and the Environment, 2020)

Characteristics and Prognosis of Talaromyces marneffei Infection in Non-HIV-Infected Children in Southern China - Jing Guo; Bing-Kun Li; Tian-Min Li; Fang-Lin Wei; Yu-Jiao Fu; Yan-Qing Zheng; Kai-Su Pan; Chun-Yang Huang; Cun-Wei Cao (Mycopathologia, 2019)

Age- and Nicotine-Associated Gene Expression Changes in the Hippocampus of APP/PS1 Mice - Jie Yang; Yan Long; De-Mei Xu; Bing-Lin Zhu; Xiao-Juan Deng; Zhen Yan; Fei Sun; Guo-Jun Chen (Journal of Molecular Neuroscience, 2019)

Relationship between phenotype and genotype of 102 Chinese newborns with Prader–Willi syndrome - Meng-Meng Ge; Yan-Yan Gao; Bing-Bing Wu; Kai Yan; Qian Qin; HuiJun Wang; WenHao Zhou; Lin Yang (Molecular Biology Reports, 2019)

Potential value of autoantibodies as biomarkers of chronic graft-versus-host disease after allogeneic stem cell transplantation - Bing Hao; Song Gao; Yi-wen Sang; Lin Wang; Xue-qin Meng; Jing-ya You (Journal of Zhejiang University-SCIENCE B, 2019)

Improved Fourier modeling of gravity fields caused by polyhedral bodies: with applications to asteroid Bennu and comet 67P/Churyumov–Gerasimenko - Leyuan Wu; Longwei Chen; Bin Wu; Bing Cheng; Qiang Lin (Journal of Geodesy, 2019)

Quantifying the carbon source of pedogenic calcite veins in weathered limestone: implications for the terrestrial carbon cycle - Lin Zou; Lin Dong; Meng Ning; Kangjun Huang; Yongbo Peng; Shujian Qin; Honglin Yuan; Bing Shen (Acta Geochimica, 2019)

Recent advances in carbohydrate-based cancer vaccines - Ke-Tao Jin; Huan-Rong Lan; Xiao-Yi Chen; Shi-Bing Wang; Xiao-Jiang Ying; Yan Lin; Xiao-Zhou Mou (Biotechnology Letters, 2019)

QTL mapping for maize starch content and candidate gene prediction combined with co-expression network analysis - Feng Lin; Ling Zhou; Bing He; Xiaolin Zhang; Huixue Dai; Yiliang Qian; Long Ruan; Han Zhao (Theoretical and Applied Genetics, 2019)

Formation of high crystalline LDH sludge for removing Cu and Zn from wastewater by controlled double-jet precipitation - Lanyan Wu; Bing Peng; Qingzhu Li; Qingwei Wang; Xu Yan; Qiuhong Lin; Chunlei Ji (Environmental Science and Pollution Research, 2019)

Identification and characterization of plant growth–promoting endophyte RE02 from Trifolium repens L. in mining smelter - Chenjing Liu; Hai Lin; Yingbo Dong; Bing Li; Liang Wang (Environmental Science and Pollution Research, 2019)

Seasonal climatic effects and feedbacks of anthropogenic heat release due to global energy consumption with CAM5 - Bing Chen; C. Wu; X. Liu; L. Chen; Jian Wu; H. Yang; Tao Luo; Xue Wu; Yiquan Jiang; Lei Jiang; H. Y. Brown; Z. Lu; et al. (Climate Dynamics, 2019)

Helmert transformation solutions combination and update with new measurements - Shengquan Li; Bing Ji; Guobin Chang; Peng Lin; Shaofeng Bian (Acta Geodaetica et Geophysica, 2019)

Exogenous and endogenous nitrogen differentially affect the decomposition of fine roots of different diameter classes of Mongolian pine in semi-arid northeast China - Qun Gang; Scott X. Chang; Guigang Lin; Qiong Zhao; Bing Mao; De-Hui Zeng (Plant and Soil, 2019)

Pond-bottom decomposition of leaf litters canopied by free-floating vegetation - Ya-Lin Zhang; Hong-Bin Li; Li Xu; Xu Pan; Wen-Bing Li; Jian Liu; Yue-Ping Jiang; Yao-Bin Song; Ming Dong (Environmental Science and Pollution Research, 2019)

New lignan from the rattan stems of Schisandra chinensis - Bing-You Yang; Zhang-Lin Chen; Yan Liu; Jiang-Tao Guo; Hai-Xue Kuang (Natural Product Research, 2019)

Effects of Long-Term Application of Vinasse on Physicochemical Properties, Heavy Metals Content and Microbial Diversity in Sugarcane Field Soil - Juan Yin; Chao-Bing Deng; Xiao-Fei Wang; Gan-lin Chen; Viktor Gábor Mihucz; Gui-Ping Xu; Qu-Cheng Deng (Sugar Tech, 2019)

Mechanistic studies of the apoptosis induced by the macrocyclic natural product tetrandrine in MGC 803 cells - Sai-Qi Wang; Hong-Lin Hou; Liang-Yu Bie; Cai-Yun Nie; Luo-Nan Wang; Shaobing Gao; Ting-Ting Hu; Xiao-Bing Chen (Medicinal Chemistry Research, 2019)

A refined model for lithosphere evolution beneath the decratonized northeastern North China Craton - A-Bing Lin; Jian-Ping Zheng; Qing Xiong; Sonja Aulbach; Jiang-Gu Lu; Shao-Kui Pan; Hong-Kun Dai; Hui Zhang (Contributions to Mineralogy and Petrology, 2019)

Unidirectional monosynaptic connections from auditory areas to the primary visual cortex in the marmoset monkey - Piotr Majka; Marcello G. P. Rosa; Shi Bai; Jonathan M. Chan; Bing-Xing Huo; Natalia Jermakow; Meng K. Lin; Yeonsook S. Takahashi; Ianina H. Wolkowicz; Katrina H. Worthy; Ramesh Rajan; David H. Reser; et al. (Brain Structure and Function, 2019)

Human activity during the late Pleistocene in the Lop Nur region, northwest China: Evidence from a buried stone artifact - Kangkang Li; Xiaoguang Qin; Xiaoyan Yang; Bing Xu; Lei Zhang; Guijin Mu; Dong Wei; Chunxue Wang; Yong Wu; Xiaohong Tian; Yongchong Lin; Wen Li; et al. (Science China Earth Sciences, 2018)

Acute effect of fine and coarse particular matter on cardiovascular visits in Ningbo, China - Pei-wen Zheng; Peng Shen; Zhen-hua Ye; Zhen-yu Zhang; Peng-fei Chai; Die Li; Ming-juan Jin; Meng-Ling Tang; Huai-chu Lu; Hong-bo Lin; Jian-bing Wang; Kun Chen (Environmental Science and Pollution Research, 2018)

Detection, sequence analysis, and antibody prevalence of porcine deltacoronavirus in Taiwan - Tien-Huan Hsu; Hao-Ping Liu; Chieh-Yu Chin; Chinling Wang; Wan-Zhen Zhu; Bing-Lin Wu; Yu-Chung Chang (Archives of Virology, 2018)

Docking study and antiosteoporosis effects of a dibenzylbutane lignan isolated from Litsea cubeba targeting Cathepsin K and MEK1 - Wei Peng; Hui Shen; Bing Lin; Ping Han; Changhui Li; Qiaoyan Zhang; Bingzhu Ye; Khalid Rahman; Hailiang Xin; Luping Qin; Ting Han (Medicinal Chemistry Research, 2018)

Enhanced catalytic activities and modified substrate preferences for taxoid 10β-O-acetyl transferase mutants by engineering catalytic histidine residues - Lin-Feng You; Jia-Jun Huang; Tao Wei; Shu-Ling Lin; Bing-Hua Jiang; Li-Qiong Guo; Jun-Fang Lin (Biotechnology Letters, 2018)

Calpain inhibition attenuates bleomycin-induced pulmonary fibrosis via switching the development of epithelial-mesenchymal transition - Yuan Liu; Bing Liu; Gu-qin Zhang; Jing-feng Zou; Meng-lin Zou; Zhen-shun Cheng (Naunyn-Schmiedeberg's Archives of Pharmacology, 2018)

Deletion of Type-2 Cannabinoid Receptor Induces Alzheimer’s Disease-Like Tau Pathology and Memory Impairment Through AMPK/GSK3β Pathway - Lin Wang; Bing-Jin Liu; Yun Cao; Wei-Qi Xu; Dong-Sheng Sun; Meng-Zhu Li; Fang-Xiao Shi; Man Li; Qing Tian; Jian-Zhi Wang; Xin-Wen Zhou (Molecular Neurobiology, 2018)

CLDN6 enhances chemoresistance to ADM via AF-6/ERKs pathway in TNBC cell line MDAMB231 - Minlan Yang; Yanru Li; Yang Ruan; Yan Lu; Dongjing Lin; Yinping Xie; Bing Dong; Qihua Dang; Chengshi Quan (Molecular and Cellular Biochemistry, 2018)

Association between short-term exposure to ambient air pollution and daily mortality: a time-series study in Eastern China - Die Li; Jian-bing Wang; Zhen-yu Zhang; Peng Shen; Pei-wen Zheng; Ming-juan Jin; Huai-chu Lu; Hong-bo Lin; Kun Chen (Environmental Science and Pollution Research, 2018)

Human infection with a further evolved avian H9N2 influenza A virus in Sichuan, China - Jianan Xu; Shuang Li; Yong Yang; Bing Liu; Huiping Yang; Tiansu Li; Lin Zhang; Wei Li; Xiaohu Luo; Liquan Zhang; Ming Pan (Science China Life Sciences, 2018)

Phylogenetic analysis of IRIS L. from China on chloroplast TRNL-F sequences - Yu-Lin Jiang; Zhuo Huang; Jin-Qiu Liao; Hui-Xing Song; Xiao-Mei Luo; Su-Ping Gao; Ting Lei; Ming-Yan Jiang; Yin Jia; Qi-Bing Chen; Xiao-Fang Yu; Yong-Hong Zhou (Biologia, 2018)

Effects of air pollution on hospital visits for pneumonia in children: a two-year analysis from China - Die Li; Jian-bing Wang; Zhen-yu Zhang; Peng Shen; Pei-wen Zheng; Ming-juan Jin; Huai-chu Lu; Hong-bo Lin; Kun Chen (Environmental Science and Pollution Research, 2018)

Coulomb Stress Evolution History as Implication on the Pattern of Strong Earthquakes along the Xianshuihe-Xiaojiang Fault System, China - Bing Yan; Shinji Toda; Aiming Lin (Journal of Earth Science, 2018)

The role of unfolded protein response and ER-phagy in quantum dots-induced nephrotoxicity: an in vitro and in vivo study - Shengwei Jiang; Yuchun Lin; Huan Yao; Chuanli Yang; Liyin Zhang; Bing Luo; Zhao Lei; Liwei Cao; Naibo Lin; Xiangyang Liu; Zhongning Lin; Chengyong He (Archives of Toxicology, 2018)

Correlation analyses revealed global microRNA–mRNA expression associations in human peripheral blood mononuclear cells - Lan Wang; Jiang Zhu; Fei-Yan Deng; Long-Fei Wu; Xing-Bo Mo; Xiao-Wei Zhu; Wei Xia; Fang-Fei Xie; Pei He; Peng-Fei Bing; Ying-Hua Qiu; Xiang Lin; et al. (Molecular Genetics and Genomics, 2018)

An Improved Dimidiated Pixel Model for Vegetation Fraction in the Yarlung Zangbo River Basin of Qinghai-Tibet Plateau - Bing Guo; Fang Han; Lin Jiang (Journal of the Indian Society of Remote Sensing, 2018)

Using circulating tumor cells to evaluate the efficacy of irreversible electroporation for unresectasble pancreatic cancer - Mao Lin; Mohammed Alnaggar; Shu-Zhen Liang; Jian Shi; Li-Zhi Niu; Ji-Bing Chen; Ke-Cheng Xu (Immunologic Research, 2018)

Correction to: Age at menarche and age at natural menopause in East Asian women: a genome-wide association study - Jiajun Shi; Ben Zhang; Ji-Yeob Choi; Yu-Tang Gao; Huaixing Li; Wei Lu; Jirong Long; Daehee Kang; Yong-Bing Xiang; Wanqing Wen; Sue K. Park; Xingwang Ye; et al. (GeroScience, 2018)

Effect of the dark septate endophytic fungus Acrocalymma vagum on heavy metal content in tobacco leaves - Hui-Qing Jin; Hua-Bing Liu; Ying-Ying Xie; Yong-Gang Zhang; Qing-Quan Xu; Li-Juan Mao; Xin-Jun Li; Jin Chen; Fu-Cheng Lin; Chu-Long Zhang (Symbiosis, 2018)

Echinacoside, a phenylethanoid glycoside from Cistanche deserticola, extends lifespan of Caenorhabditis elegans and protects from Aβ-induced toxicity - Wei Chen; Hong-Ru Lin; Cong-Min Wei; Xiao-Hua Luo; Meng-Lu Sun; Zhen-Zhou Yang; Xin-Yan Chen; Hong-Bing Wang (Biogerontology, 2018)

A new ent -kaurane diterpene derivative from the stems of Eurya chinensis R.Br - Jia-Ling Song; Yao Yuan; Ling-Hui Nie; Bai-Lin Li; Xu-Bing Qin; Yan Li; Jie-Wei Wu; Sheng-Xiang Qiu (Natural Product Research, 2018)

Nanoparticle-encapsulated emodin decreases diabetic neuropathic pain probably via a mechanism involving P2X3 receptor in the dorsal root ganglia - Lin Li; Xuan Sheng; Shanhong Zhao; Lifang Zou; Xinyao Han; Yingxin Gong; Huilong Yuan; Liran Shi; Lili Guo; Tianyu Jia; Shuangmei Liu; Bing Wu; et al. (Purinergic Signalling, 2017)

Mechanical stress promotes matrix synthesis of mandibular condylar cartilage via the RKIP-ERK pathway - Lian Sun; Jing Zhao; Hua Wang; Yongchu Pan; Lin Wang; Wei-Bing Zhang (Journal of Molecular Histology, 2017)

Spatiotemporal expression of proprotein convertase subtilisin/kexin type 5 in the development of anorectal malformations in fetal rats - Xiao Bing Tang; Li Chen; Wei Lin Wang; Zheng Wei Yuan; Yu Zuo Bai (Journal of Molecular Histology, 2017)

Molecular diversity of phenothiazines: design and synthesis of phenothiazine–dithiocarbamate hybrids as potential cell cycle blockers - Dong-Jun Fu; Ruo-Han Zhao; Jia-Huan Li; Jia-Jia Yang; Ruo-Wang Mao; Bo-Wen Wu; Ping Li; Xiao-Lin Zi; Qing-Qing Zhang; Hui-Jie Cai; Sai-Yang Zhang; Yan-Bing Zhang; et al. (Molecular Diversity, 2017)

The effects of different irrigation regimes on nitrous oxide emissions and influencing factors in greenhouse tomato fields - Bing Han; Xuhong Ye; Wen Li; Xichao Zhang; Yulong Zhang; Xiangui Lin; Hongtao Zou (Journal of Soils and Sediments, 2017)

The association study of nonsyndromic cleft lip with or without cleft palate identified risk variants of the $$\varvec{GLI3}$$ G L I 3 gene in a Chinese population - Yirui Wang; Yimin Sun; Yongqing Huang; Yongchu Pan; Bing Shi; Jian Ma; Lan Ma; Feifei Lan; Yuxi Zhou; Jiayu Shi; Jinfang Zhu; Hongbing Jiang; et al. (Journal of Genetics, 2017)

Clinical efficacy of percutaneous cryoablation combined with allogenic NK cell immunotherapy for advanced non-small cell lung cancer - Mao Lin; Shu-Zhen Liang; Xiao-Hua Wang; Ying-Qing Liang; Ming-Jie Zhang; Li-Zhi Niu; Ji-Bing Chen; Hai-Bo Li; Ke-Cheng Xu (Immunologic Research, 2017)

Air pollution and hospital visits for acute upper and lower respiratory infections among children in Ningbo, China: A time-series analysis - Pei-wen Zheng; Jian-bing Wang; Zhen-yu Zhang; Peng Shen; Peng-fei Chai; Die Li; Ming-juan Jin; Meng-Ling Tang; Huai-chu Lu; Hong-bo Lin; Kun Chen (Environmental Science and Pollution Research, 2017)

Paleoseismic study of the Kamishiro Fault on the northern segment of the Itoigawa–Shizuoka Tectonic Line, Japan - Aiming Lin; Mikako Sano; Maomao Wang; Bing Yan; Di Bian; Ryoji Fueta; Takashi Hosoya (Journal of Seismology, 2017)

Puerarin may protect against Schwann cell damage induced by glucose fluctuation - Bing Xue; Lin Wang; Zhe Zhang; Rui Wang; Xin-xin Xia; Ping-ping Han; Li-jun Cao; Yong-hui Liu; Lian-qing Sun (Journal of Natural Medicines, 2017)

A review of diffuse pollution modeling and associated implications for watershed management in China - Wei Ouyang; Xiang Gao; Peng Wei; Bing Gao; Chunye Lin; Fanghua Hao (Journal of Soils and Sediments, 2017)

Observation and modeling on irregular purple soil water infiltration process - Dong-bing Cheng; Lin-yao Dong; Feng Qian; Bei Sun (Journal of Mountain Science, 2017)

Spatial and temporal change patterns of freeze-thaw erosion in the three-river source region under the stress of climate warming - Bing Guo; Wei Luo; Dong-liang Wang; Lin Jiang (Journal of Mountain Science, 2017)

Relationship between landslides and active normal faulting in the epicentral area of the AD 1556 M~8.5 Huaxian Earthquake, SE Weihe Graben (Central China) - Gang Rao; Yali Cheng; Aiming Lin; Bing Yan (Journal of Earth Science, 2017)

Recombinant heat shock protein 78 enhances enterovirus 71 propagation in Vero cells and is induced in SK-N-SH cells during the infection - Bing Zhu; Tiantian Xu; Zhengfang Lin; Changbing Wang; Yinghua Li; Mingqi Zhao; Liang Hua; Misi Xiao; Ning Deng (Archives of Virology, 2017)

MicroRNA-150 targets ELK1 and modulates the apoptosis induced by ox-LDL in endothelial cells - Bing Qin; Yaqing Shu; Li Xiao; Tingting Lu; Yinyao Lin; Huan Yang; Zhengqi Lu (Molecular and Cellular Biochemistry, 2017)

First complete genome sequence of parainfluenza virus 5 isolated from lesser panda - Jun-Qiong Zhai; Shao-Lun Zhai; Tao Lin; Jian-Kui Liu; He-Xing Wang; Bing Li; He Zhang; Shu-Zhan Zou; Xia Zhou; Meng-Fan Wu; Wu Chen; Man-Lin Luo (Archives of Virology, 2017)

RETRACTED ARTICLE: Role of Glibenclamide in Brain Injury After Intracerebral Hemorrhage - Bing Jiang; Lin Li; Qianwei Chen; Yihao Tao; Liming Yang; Bo Zhang; John H. Zhang; Hua Feng; Zhi Chen; Jun Tang; Gang Zhu (Translational Stroke Research, 2017)

Transient Receptor Potential-canonical 1 is Essential for Environmental Enrichment-Induced Cognitive Enhancement and Neurogenesis - Lai-Ling Du; Lin Wang; Xi-Fei Yang; Ping Wang; Xiao-Hong Li; Da-Min Chai; Bing-Jin Liu; Yun Cao; Wei-Qi Xu; Rong Liu; Qing Tian; Jian-Zhi Wang; et al. (Molecular Neurobiology, 2017)

Effects of DDIT4 in Methamphetamine-Induced Autophagy and Apoptosis in Dopaminergic Neurons - Bing Li; Rui Chen; Ling Chen; Pingming Qiu; Xiuyun Ai; Enping Huang; Weiye Huang; Chuanxiang Chen; Chao Liu; Zhoumeng Lin; Wei-Bing Xie; Huijun Wang (Molecular Neurobiology, 2017)

Integrative multi-omics analysis revealed SNP-lncRNA-mRNA (SLM) networks in human peripheral blood mononuclear cells - Wei Xia; Xiao-Wei Zhu; Xin-Bo Mo; Long-Fei Wu; Jian Wu; Yu-Fan Guo; Ke-Qin Zeng; Ming-Jun Wang; Xiang Lin; Ying-Hua Qiu; Lan Wang; Pei He; et al. (Human Genetics, 2017)

Complete genomic characterization of two European-genotype porcine reproductive and respiratory syndrome virus isolates in Fujian province of China - Jian-Kui Liu; Chun-Hua Wei; AI-Ling Dai; Ke-Wei Fan; Bing-Hui Yang; Chun-Fang Huang; Xiao-Hua Li; Xiao-Yan Yang; Man-Lin Luo (Archives of Virology, 2017)

Insulin-independent GLUT4 translocation in proliferative vascular smooth muscle cells involves SM22α - Li-Li Zhao; Fan Zhang; Peng Chen; Xiao-Li Xie; Yong-Qing Dou; Yan-Ling Lin; Lei Nie; Pin Lv; Dan-Dan Zhang; Xiao-Kun Li; Sui-Bing Miao; Ya-Juan Yin; et al. (Journal of Molecular Medicine, 2017)

An integrated earthquake early warning system and its performance at schools in Taiwan - Bing-Ru Wu; Nai-Chi Hsiao; Pei-Yang Lin; Ting-Yu Hsu; Chiou-Yun Chen; Shieh-Kung Huang; Hung-Wei Chiang (Journal of Seismology, 2017)

A novel trichosanthin fusion protein with increased cytotoxicity to tumor cells - Bing Lin; Xu-Zhong Yang; Xue-Wei Cao; Tao-Zhu Zhang; Fu-Jun Wang; Jian Zhao (Biotechnology Letters, 2017)

Chromogenic media for MRSA diagnostics - Zhenbo Xu; Yuchao Hou; Brian M. Peters; Dingqiang Chen; Bing Li; Lin Li; Mark E. Shirtliff (Molecular Biology Reports, 2016)

Regulation and the Mechanism of Estrogen on Cav1.2 Gene in Rat-Cultured Cortical Astrocytes - Ling He; Xiao-Tong Hu; Yu-Jie Lai; Yan Long; Lu Liu; Bing-lin Zhu; Guo-Jun Chen (Journal of Molecular Neuroscience, 2016)

Crystal Violet and XTT Assays on Staphylococcus aureus Biofilm Quantification - Zhenbo Xu; Yanrui Liang; Shiqi Lin; Dingqiang Chen; Bing Li; Lin Li; Yang Deng (Current Microbiology, 2016)

Effects of Replacing of Inorganic Trace Minerals by Organically Bound Trace Minerals on Growth Performance, Tissue Mineral Status, and Fecal Mineral Excretion in Commercial Grower-Finisher Pigs - Bing Liu; Pingwen Xiong; Nana Chen; Junna He; Gang Lin; Yan Xue; Weifen Li; Dongyou Yu (Biological Trace Element Research, 2016)

Biosurfactant Production by Marine-Originated Bacteria Bacillus Subtilis and Its Application for Crude Oil Removal - Zhiwen Zhu; Baiyu Zhang; Bing Chen; Qinghong Cai; Weiyun Lin (Water, Air, & Soil Pollution, 2016)

Improving the Long Lead-Time Inundation Forecasts Using Effective Typhoon Characteristics - Bing-Chen Jhong; Jhih-Huang Wang; Gwo-Fong Lin (Water Resources Management, 2016)

Hypocrol A, a new tyrosol derivative from a sponge-derived strain of the fungus Hypocrea koningii - Li-Jian Ding; Wei Yuan; Ying-Xin Li; Xiao-Jian Liao; Huan Sun; Qi Peng; Bing-Nan Han; Hou-Wen Lin; Zhi-Yong Li; Fan Yang; Shi-Hai Xu (Natural Product Research, 2016)

Chidamide alleviates TGF-β-induced epithelial–mesenchymal transition in lung cancer cell lines - Sheng-Hao Lin; Bing-Yen Wang; Ching-Hsiung Lin; Peng-Ju Chien; Yueh-Feng Wu; Jiunn-Liang Ko; Jeremy J. W. Chen (Molecular Biology Reports, 2016)

Mapping the vegetation distribution of the permafrost zone on the Qinghai-Tibet Plateau - Zhi-wei Wang; Qian Wang; Lin Zhao; Xiao-dong Wu; Guang-yang Yue; De-fu Zou; Zhuo-tong Nan; Guang-yue Liu; Qiang-qiang Pang; Hong-bing Fang; Tong-hua Wu; Jian-zong Shi; et al. (Journal of Mountain Science, 2016)

Gray algebraic curve model-based roof separation prediction method for the warning of roof fall accidents - Jian-Lin Xie; Jia-Lin Xu; Wei-Bing Zhu (Arabian Journal of Geosciences, 2016)

Genetic diversity analysis of Jatropha curcas L. accessions cultivated in Taiwan using inter simple sequence repeats (ISSR) markers - Celimphilo Mavuso; Yong-Pei Wu; Fure-Chyi Chen; Bing-Hong Huang; Su-Ju Lin (Agroforestry Systems, 2016)

Blood Cadmium Level Associates with Lower Testosterone and Sex Hormone-Binding Globulin in Chinese men: from SPECT-China Study, 2014 - Chi Chen; Ningjian Wang; Xiaomin Nie; Bing Han; Qin Li; Yi Chen; Hualing Zhai; Chunfang Zhu; Yingchao Chen; Fangzhen Xia; Meng Lu; Dongping Lin; et al. (Biological Trace Element Research, 2016)

Molecular Characterization of Ethylene Response Sensor 1 (BoERS1) in Bambusa oldhamii - Yi-Lin Hsieh; Ching-Fang Lu; Bing-Yu Chiang; Shu-Chien Liao; Rita P.-Y. Chen; Choun-Sea Lin; Ai-Yu Wang; Chien-Chih Yang (Plant Molecular Biology Reporter, 2016)

Millennium recurrence interval of morphogenic earthquakes on the Qingchuan fault, northeastern segment of the Longmen Shan Thrust Belt, China - Aiming Lin; Bing Yan; Gang Rao (Journal of Seismology, 2016)

Increased night duty loading of physicians caused elevated blood pressure and sympathetic tones in a dose-dependent manner - Hsiu-Hao Lee; Shih-Hsiang Lo; Bing-Yu Chen; Yen-Hung Lin; Dachen Chu; Tsun-Jen Cheng; Pau-Chung Chen; Yue-Liang Guo (International Archives of Occupational and Environmental Health, 2016)

Transcriptional and posttranscriptional regulation of CXCL8/IL-8 gene expression induced by connective tissue growth factor - Chien-Huang Lin; Yuan-Hung Wang; Yu-Wen Chen; Yu-Liang Lin; Bing-Chang Chen; Mei-Chieh Chen (Immunologic Research, 2016)

Experimental analysis for the dynamic initiation mechanism of debris flows - Chi Li; Wen-hui Zhu; Lin Li; Xiao-bing Lu; De Yao; Farshad Amini (Journal of Mountain Science, 2016)

New Re-Os isotopic constrains on the formation of the metalliferous deposits of the Lower Cambrian Niutitang formation - Yong Fu; Lin Dong; Chao Li; Wenjun Qu; Haoxiang Pei; Wenlang Qiao; Bing Shen (Journal of Earth Science, 2016)

Arbuscular Mycorrhizal Fungus Alleviates Chilling Stress by Boosting Redox Poise and Antioxidant Potential of Tomato Seedlings - Airong Liu; Shuangchen Chen; Mengmeng Wang; Dilin Liu; Rui Chang; Zhonghong Wang; Xiaomin Lin; Bing Bai; Golam Jalal Ahammed (Journal of Plant Growth Regulation, 2016)

Complete Genome of a Novel Pseudoalteromonas Phage PHq0 - Duo-bing Wang; Yan Li; Meng-qi Sun; Jin-peng Huang; Hong-bing Shao; Qi-lin Xin; Min Wang (Current Microbiology, 2016)

Autoinducer-2 signaling is involved in regulation of stress-related genes of Deinococcus radiodurans - Lin Lin; Tao Li; Shang Dai; Jiangliu Yu; Xiuqin Chen; Liangyan Wang; Yunguang Wang; Yuejin Hua; Bing Tian (Archives of Microbiology, 2016)

Soil taxonomy and distribution characteristics of the permafrost region in the Qinghai-Tibet Plateau, China - Hong-bing Fang; Lin Zhao; Xiao-dong Wu; Yu-guo Zhao; Yong-hua Zhao; Guo-jie Hu (Journal of Mountain Science, 2015)

Two new eudesmane-type glucopyranosides from the fruits of Daucus carota L. - Jin-Ke Xu; Xiang-Hong Lu; Wei Zhu; Bing-Xian Yang; Lin Zhang; Jing-Kui Tian (Natural Product Research, 2015)

Effect of antioxidants and light stabilisers on silver migration from nanosilver-polyethylene composite packaging films into food simulants - Qi-Zhi Su; Qin-Bao Lin; Chao-Fang Chen; Yu-Mei Wu; Li-Bing Wu; Xiao-Qing Chen; Zhi-Wei Wang (Food Additives & Contaminants: Part A, 2015)

An estimation method of soil freeze-thaw erosion in the Qinghai–Tibet Plateau - Bing Guo; Yi Zhou; Jinfeng Zhu; Wenliang Liu; Futao Wang; Litao Wang; Lin Jiang (Natural Hazards, 2015)

Expression and characterization of LacMP, a novel fungal laccase of Moniliophthora perniciosa FA553 - Huiping Liu; Chaofan Tong; Bing Du; Shuli Liang; Ying Lin (Biotechnology Letters, 2015)

Effects of Fluoride on DNA Damage and Caspase-Mediated Apoptosis in the Liver of Rats - Guo Hua Song; Fu Bing Huang; Ji Ping Gao; Mao Lin Liu; Wen Biao Pang; Wei bin Li; Xiao Yan Yan; Mei Jun Huo; Xia Yang (Biological Trace Element Research, 2015)

Overexpression of AT14A confers tolerance to drought stress-induced oxidative damage in suspension cultured cells of Arabidopsis thaliana - Lin Wang; Jie He; Haidong Ding; Hui Liu; Bing Lü; Jiansheng Liang; L. Wang; J. He; H. D. Ding; H. Liu; B. Lü; J. S. Liang (Protoplasma, 2015)

Microstructural and mineral analysis on the fault gouge in the coseismic shear zone of the 2008 M w 7.9 Wenchuan earthquake - Ren-mao Yuan; Bing-liang Zhang; Xi-wei Xu; Chuan-yong Lin; Zhu-jun Han (International Journal of Earth Sciences, 2015)

Development of quantification bioassays for live propagules of Phytophthora sojae in soil - Bing Suo; Caixia Xiao; Haocheng Lin; Qiuming Chen; Liming Zhao; Miao Tian; Qianqian Sun; Jingzhi Wen (Journal of General Plant Pathology, 2015)

Genetic relationships and ecological divergence in Salix species and populations in Taiwan - Chun-Lin Huang; Chung-Te Chang; Bing-Hong Huang; Jeng-Der Chung; Jui-Hung Chen; Yu-Chung Chiang; Shih-Ying Hwang (Tree Genetics & Genomes, 2015)

P2X7 receptor of rat dorsal root ganglia is involved in the effect of moxibustion on visceral hyperalgesia - Shuangmei Liu; Qingming Shi; Qicheng Zhu; Ting Zou; Guilin Li; An Huang; Bing Wu; Lichao Peng; Miaomiao Song; Qin Wu; Qiuyu Xie; Weijian Lin; et al. (Purinergic Signalling, 2015)

Compromised small-world efficiency of structural brain networks in schizophrenic patients and their unaffected parents - Hao Yan; Lin Tian; Qifeng Wang; Qiang Zhao; Weihua Yue; Jun Yan; Bing Liu; Dai Zhang (Neuroscience Bulletin, 2015)

Endoplasmic Reticulum Stress: Relevance and Therapeutics in Central Nervous System Diseases - Hong-Yu Zhang; Zhou-guang Wang; Xiang-Hong Lu; Xiao-Xia Kong; Fen-Zan Wu; Li Lin; Xiaohua Tan; Li-Bing Ye; Jian Xiao (Molecular Neurobiology, 2015)

Experimental Investigation About Influence of Pre-existing Fracture on Hydraulic Fracture Propagation Under Tri-axial Stresses - Wan Cheng; Yan Jin; Qing Lin; Mian Chen; Yakun Zhang; Ce Diao; Bing Hou (Geotechnical and Geological Engineering, 2015)

Diaphorobacter ruginosibacter sp. nov., isolated from soybean root nodule, and emended description of the genus Diaphorobacter - Xiu Li Wei; Meng Sha Han; Cong Cong Xia; Shu Lan Ding; Lin Xu; Yan Bing Lin; Li Wang; Ge Hong Wei (Archives of Microbiology, 2015)

Pilot study of mold in homes of asthmatic children in Taipei, Taiwan, using the Environmental Relative Moldiness Index - Chi-Hsien Chen; H. Jasmine Chao; Wei-Chiang Shen; Bing-Yu Chen; King-Teh Lin; Yue Leon Guo; Stephen Vesper (Aerobiologia, 2015)

Smooth muscle 22α facilitates angiotensin II-induced signaling and vascular contraction - Xiao-Li Xie; Xi Nie; Jun Wu; Fan Zhang; Li-Li Zhao; Yan-Ling Lin; Ya-Juan Yin; Hui Liu; Ya-Nan Shu; Sui-Bing Miao; Huan Li; Peng Chen; et al. (Journal of Molecular Medicine, 2015)

Safety and efficacy study of lung cancer stem cell vaccine - Mao Lin; Shu-Ying Li; Ke-Cheng Xu; Zheng-Ping Liu; Feng Mu; Yuan-Ying Yuan; Xiao-Hua Wang; Ji-Bing Chen; Qiao Li (Immunologic Research, 2015)

Erratum to: Elevated Cerebral Cortical CD24 Levels in Patients and Mice with Traumatic Brain Injury: A Potential Negative Role in Nuclear Factor Kappa B/Inflammatory Factor Pathway - Wei Li; Hai-Ping Ling; Wan-Chun You; Huan-Dong Liu; Qing Sun; Meng-Liang Zhou; Wei Shen; Jin-Bing Zhao; Lin Zhu; Chun-Hua Hang (Molecular Neurobiology, 2015)

Permeability Imaging as a Biomarker of Leptomeningeal Collateral Flow in Patients with Intracranial Arterial Stenosis - Hui Chen; Bing Wu; Guangming Zhu; Max Wintermark; Xinhuai Wu; Zihua Su; Xiao Xu; Chenglin Tian; Lin Ma; Weiwei Zhang; Xin Lou (Cell Biochemistry and Biophysics, 2015)

Interactions between household air pollution and GWAS-identified lung cancer susceptibility markers in the Female Lung Cancer Consortium in Asia (FLCCA) - H. Dean Hosgood; Minsun Song; Chao Agnes Hsiung; Zhihua Yin; Xiao-Ou Shu; Zhaoming Wang; Nilanjan Chatterjee; Wei Zheng; Neil Caporaso; Laurie Burdette; Meredith Yeager; Sonja I. Berndt; et al. (Human Genetics, 2015)

Isolation and characterization of 25 polymorphic microsatellite loci from the Hynobius maoershanensis (Caudata: Hynobiidae) - Bing-jie Lin; Hua-yuan Huang; Zhong-hui Wei; Ze-ning Chen; Shao-neng Wang; Zheng-jun Wu (Conservation Genetics Resources, 2015)

A putative soybean GmsSOS1 confers enhanced salt tolerance to transgenic Arabidopsis sos1-1 mutant - Wang-xing Nie; Lin Xu; Bing-jun Yu (Protoplasma, 2015)

Effects of rapamycin against paraquat-induced pulmonary fibrosis in mice - Xue Shao; Meng Li; Chong Luo; Ying-ying Wang; Ying-ying Lu; Shi Feng; Heng Li; Xia-bing Lang; Yu-cheng Wang; Chuan Lin; Xiu-jin Shen; Qin Zhou; et al. (Journal of Zhejiang University-SCIENCE B, 2015)

A novel method to identify the DNA motifs recognized by a defined transcription factor - Xiaoyu Ji; Liuqiang Wang; Xianguang Nie; Lin He; Dandan Zang; Yujia Liu; Bing Zhang; Yucheng Wang (Plant Molecular Biology, 2014)

Development of an empirical model for rainfall-induced hillside vulnerability assessment: a case study on Chen-Yu-Lan watershed, Nantou, Taiwan - Tsu-Chiang Lei; Yi-Min Huang; Bing-Jean Lee; Meng-Hsun Hsieh; Kuan-Ting Lin (Natural Hazards, 2014)

Impacts of uncertainty in AVOC emissions on the summer ROx budget and ozone production rate in the three most rapidly-developing economic growth regions of China - Feng Wang; Junling An; Ying Li; Yujia Tang; Jian Lin; Yu Qu; Yong Chen; Bing Zhang; Jing Zhai (Advances in Atmospheric Sciences, 2014)

Variation in β-amylase activity and thermostability in Tibetan annual wild and cultivated barley genotypes - Hai-tao Zhang; Tian-long Chen; Bing-lin Zhang; De-zhi Wu; Ye-chang Huang; Fei-bo Wu; Guo-ping Zhang (Journal of Zhejiang University-SCIENCE B, 2014)

Identification and expression of the elongator protein 2 (Ajelp2) gene, a novel regeneration-related gene from the sea cucumber Apostichopus japonicus - Yanli Mei; Feng Yao; Yang Wu; Bing Chu; Cheng Cheng; Yan Liu; Xuejie Li; Xiangyang Zou; Lin Hou (Molecular Biology Reports, 2014)

Critical mechanisms for the formation of extreme arctic sea-ice extent in the summers of 2007 and 1996 - Xiquan Dong; Behnjamin J. Zib; Baike Xi; Ryan Stanfield; Yi Deng; Xiangdong Zhang; Bing Lin; Charles N. Long (Climate Dynamics, 2014)

The variability of the snow and ice melt in alpine rivers in northwestern China - Chang-bin Li; Jia-guo Qi; Lin-shan Yang; Wen-jin Yang; Gao-feng Zhu; Shuai-bing Wang (Journal of Mountain Science, 2014)

Temporal and spatial expression of caudal-type homeobox gene-2 during hindgut development in rat embryos with ethylenethiourea-induced anorectal malformations - Xiao Bing Tang; Tao Zhang; Wei Lin Wang; Zheng Wei Yuan; Yu Zuo Bai (Cell and Tissue Research, 2014)

Assessing inundation damage and timing of adaptation: sea level rise and the complexities of land use in coastal communities - Brenda B. Lin; Yong Bing Khoo; Matthew Inman; Chi-Hsiang Wang; Sorada Tapsuwan; Xiaoming Wang (Mitigation and Adaptation Strategies for Global Change, 2014)

The role of HMGB1-RAGE axis in migration and invasion of hepatocellular carcinoma cell lines - Ruo-Chan Chen; Pan-Pan Yi; Rong-Rong Zhou; Mei-Fang Xiao; Ze-Bing Huang; Dao-Lin Tang; Yan Huang; Xue-Gong Fan (Molecular and Cellular Biochemistry, 2014)

Medullo-ponto-cerebellar white matter degeneration altered brain network organization and cortical morphology in multiple system atrophy - Chia-Feng Lu; Po-Shan Wang; Yuan-Lin Lao; Hsiu-Mei Wu; Bing-Wen Soong; Yu-Te Wu (Brain Structure and Function, 2014)

Cloning and expression analysis of the gene encoding fibrinogen-like protein A, a novel regeneration-related protein from Apostichopus japonicus - Yang Wu; Feng Yao; Yanli Mei; Bing Chu; Cheng Cheng; Yan Liu; Xuejie Li; Xiangyang Zou; Lin Hou (Molecular Biology Reports, 2014)

Rhodamine B induces long nucleoplasmic bridges and other nuclear anomalies in Allium cepa root tip cells - Dehong Tan; Bing Bai; Donghua Jiang; Lin Shi; Shunchang Cheng; Dongbing Tao; Shujuan Ji (Environmental Science and Pollution Research, 2014)

Transcriptome and Gene Expression Analysis of an Oleaginous Diatom Under Different Salinity Conditions - Ruo-lin Cheng; Jia Feng; Bing-Xin Zhang; Yun Huang; Jun Cheng; Chuan-Xi Zhang (BioEnergy Research, 2014)

Synthesis and anti-cancer activity of a glycosyl library of $$\varvec{N}$$ N -acetylglucosamine-bearing oleanolic acid - Yi-Bing Zeng; Hsin-Min Hsiao; She-Hung Chan; Ying-Hsin Wang; You-Yu Lin; Yu-Hsuan Kuo; Jih-Hwa Guh; Pi-Hui Liang (Molecular Diversity, 2014)

Elevated Cerebral Cortical CD24 Levels in Patients and Mice with Traumatic Brain Injury: A Potential Negative Role in Nuclear Factor Kappa B/Inflammatory Factor Pathway - Wei Li; Hai-Ping Ling; Wan-Chun You; Huan-Dong Liu; Qing Sun; Meng-Liang Zhou; Wei Shen; Jin-Bing Zhao; Lin Zhu; Chun-Hua Hang (Molecular Neurobiology, 2014)

MicroRNA Expression Aberration in Chinese Patients with Relapsing Remitting Multiple Sclerosis - Dan Yang; Wei-Zhi Wang; Xue-Mei Zhang; Hui Yue; Bing Li; Lin Lin; Jin Fu (Journal of Molecular Neuroscience, 2014)

A new indole alkaloidal glucoside from the aerial parts of Clematis terniflora DC. - Wen-Ting Li; Bing-Xian Yang; Wei Zhu; Ming-Hua Gong; Xiang-Dong Xu; Xiang-Hong Lu; Lian-Li Sun; Jing-Kui Tian; Lin Zhang (Natural Product Research, 2013)

Regulation of Autophagy and Ubiquitinated Protein Accumulation by bFGF Promotes Functional Recovery and Neural Protection in a Rat Model of Spinal Cord Injury - Hong-Yu Zhang; Zhou-Guang Wang; Fen-Zan Wu; Xiao-Xia Kong; Jie Yang; Bei-Bei Lin; Shi-Ping Zhu; Li Lin; Chao-Shi Gan; Xiao-Bing Fu; Xiao-Kun Li; Hua-Zi Xu; et al. (Molecular Neurobiology, 2013)

Menstrual blood-derived mesenchymal stem cells differentiate into functional hepatocyte-like cells - Xiao-zhou Mou; Jian Lin; Jin-yang Chen; Yi-fei Li; Xiao-xing Wu; Bing-yu Xiang; Cai-yun Li; Ju-ming Ma; Charlie Xiang (Journal of Zhejiang University-SCIENCE B, 2013)

Mutation of mpk6 enhances cadmium tolerance in Arabidopsis plants by alleviating oxidative stress - Chong-Wei Jin; Qian-Qian Mao; Bing-Fang Luo; Xian-Yong Lin; Shao-Ting Du (Plant and Soil, 2013)

Development of medium- and low-rise reinforced concrete building fragility curves based on Chi-Chi Earthquake data - Meng-Hsun Hsieh; Bing-Jean Lee; Tsu-Chiang Lei; Jer-Yan Lin (Natural Hazards, 2013)

The first complete genomic characterization of an Amur virus isolate from China - Yu Zhang; Bo-Hua Liu; Fang Lin; Yong-Guo Zhang; Bing-Yin Si; Xiao-Ping Kang; Yi Hu; Jing Li; Xiao-Yan Wu; Yu-Chang Li; Qing-Yu Zhu; Yin-Hui Yang (Archives of Virology, 2013)

The effects of the codon usage and translation speed on protein folding of 3Dpol of foot-and-mouth disease virus - Xiao-xia Ma; Yu-ping Feng; Jun-lin Liu; Bing Ma; Li Chen; Yong-qing Zhao; Peng-hui Guo; Jun-zhen Guo; Zhong-ren Ma; Jie Zhang (Veterinary Research Communications, 2013)

Isolation and identification of a new ent -kaurane diterpenoid from the leaves of Isodon japonica - Wei Liu; Bing-Lin Fan; Hong-Yun Guo; Yong-Liang Yuan; Hui-Juan Liang; Su-Ping Bai (Natural Product Research, 2013)

The Transurethral Seminal Vesiculoscopy in the Diagnosis and Treatment of the Seminal Vesicle Disease - Cong-hui Han; Qing Liang; Bing-zheng Dong; Lin Hao; Tao Fan; Jun-jie Zhang; Wen-da Zhang; Bo Chen; Xiang-zheng Qiu; Xiang-ju Zhou; Chang-song Pei (Cell Biochemistry and Biophysics, 2013)

Adhesion of osteoblast-like cell on silicon-doped TiO2 film prepared by cathodic arc deposition - Bing Wang; Jun-Ying Sun; Shi Qian; Xuan-Yong Liu; Shai-Lin Zhang; Sheng-Jie Dong; Guo-Chun Zha (Biotechnology Letters, 2013)

Catalog of Erycina pusilla miRNA and categorization of reproductive phase-related miRNAs and their target gene families - Choun-Sea Lin; Jeremy J. W. Chen; Yao-Ting Huang; Chen-Tran Hsu; Hsiang-Chia Lu; Ming-Lun Chou; Li-Chi Chen; Chia-I Ou; Der-Chih Liao; Ysuan-Yu Yeh; Song-Bing Chang; Su-Chen Shen; et al. (Plant Molecular Biology, 2013)

Prevalence of type-specific human papillomavirus and pap results in Chinese women: a multi-center, population-based cross-sectional study - En-Qi Wu; Bin Liu; Jian-Feng Cui; Wen Chen; Jian-Bing Wang; Liang Lu; Mayineur Niyazi; Chao Zhao; Sheng-Da Ren; Chang-Qing Li; Xiang-Zhen Gong; Jennifer S. Smith; et al. (Cancer Causes & Control, 2013)

Mamu-B genes and their allelic repertoires in different populations of Chinese-origin rhesus macaques - Yi Liu; Aixue Li; Xin Wang; Lihua Sui; Min Li; Yanbin Zhao; Bing Liu; Lin Zeng; Zhaozeng Sun (Immunogenetics, 2013)

Quantitative evaluation of Candia antarctica lipase B displayed on the cell surface of a Pichia pastoris based on an FS anchor system - Xing-xiang Liang; Bei-bei Wang; Yu-fei Sun; Ying Lin; Shuang-yan Han; Sui-ping Zheng; Tang-bing Cui (Biotechnology Letters, 2013)

Spatial patterns and climate drivers of carbon fluxes in terrestrial ecosystems of China - Gui‐Rui Yu; Xian‐Jin Zhu; Yu‐Ling Fu; Hong‐Lin He; Qiu‐Feng Wang; Xue‐Fa Wen; Xuan‐Ran Li; Lei‐Ming Zhang; Li Zhang; Wen Su; Sheng‐Gong Li; Xiao‐Min Sun; et al. (Global Change Biology, 2013)
Understanding the dynamics and underlying mechanism of carbon exchange between terrestrial ecosystems and the atmosphere is one of the key issues in global change research. In this study, we quantified the carbon fluxes in different terrestrial ecosystems in China, and analyzed their spatial variation and environmental drivers based on the long‐term observation data of China FLUX sites and the published data from other flux sites in China. The results indicate that gross ecosystem productivity ( GEP ), ecosystem respiration ( ER ), and net ecosystem productivity ( NEP ) of terrestrial ecosystems in China showed a significantly latitudinal pattern, declining linearly with the increase of latitude. However, GEP , ER , and NEP did not present a clear longitudinal pattern. The carbon sink functional areas of terrestrial ecosystems in China were mainly located in the subtropical and temperate forests, coastal wetlands in eastern China, the temperate meadow steppe in the northeast China, and the alpine meadow in eastern edge of Qinghai‐Tibetan Plateau. The forest ecosystems had stronger carbon sink than grassland ecosystems. The spatial patterns of GEP and ER in China were mainly determined by mean annual precipitation ( MAP ) and mean annual temperature ( MAT ), whereas the spatial variation in NEP was largely explained by MAT . The combined effects of MAT and MAP explained 79%, 62%, and 66% of the spatial variations in GEP , ER , and NEP , respectively. The GEP , ER , and NEP in different ecosystems in China exhibited ‘positive coupling correlation’ in their spatial patterns. Both ER and NEP were significantly correlated with GEP , with 68% of the per‐unit GEP contributed to ER and 29% to NEP . MAT and MAP affected the spatial patterns of ER and NEP mainly by their direct effects on the spatial pattern of GEP .

A New Elasto-Viscoplastic Damage Model Combined with the Generalized Hoek–Brown Failure Criterion for Bedded Rock Salt and its Application - Lin-jian Ma; Xin-yu Liu; Qin Fang; Hong-fa Xu; Hui-min Xia; Er-bing Li; Shi-gang Yang; Wen-pei Li (Rock Mechanics and Rock Engineering, 2013)

Structure and evolution of the mitochondrial genome of Exorista sorbillans: the Tachinidae (Diptera: Calyptratae) perspective - Yuan-jun Shao; Xian-qiong Hu; Guang-da Peng; Rui-xian Wang; Rui-na Gao; Chao Lin; Wei-de Shen; Rui Li; Bing Li (Molecular Biology Reports, 2012)

Preliminary observations of MHC class I A region polymorphism in three populations of Chinese-origin rhesus macaques - Aixue Li; Xin Wang; Yi Liu; Yanbin Zhao; Bing Liu; Lihua Sui; Lin Zeng; Zhaozeng Sun (Immunogenetics, 2012)

Antioxidant system of tea (Camellia sinensis) leaves in response to phosphorus supply - Zheng-He Lin; Li-Song Chen; Rong-Bing Chen; Fang-Zhou Zhang (Acta Physiologiae Plantarum, 2012)

Lipoxin A4 Inhibits 5-Lipoxygenase Translocation and Leukotrienes Biosynthesis to Exert a Neuroprotective Effect in Cerebral Ischemia/Reperfusion Injury - Le Wu; Sen Miao; Lin-Bing Zou; Ping Wu; Hua Hao; Ke Tang; Pan Zeng; Jing Xiong; Hong-Hua Li; Qiang Wu; Lei Cai; Du-Yun Ye (Journal of Molecular Neuroscience, 2012)

Application of 3D GPR attribute technology in archaeological investigations - Wen-Ke Zhao; Gang Tian; Bang-Bing Wang; Zhan-Jie Shi; Jin-Xin Lin (Applied Geophysics, 2012)

Occurrence of diarrheagenic Escherichia coli genes in raw water of water treatment plants - Shih-Wei Huang; Bing-Mu Hsu; Yen-Jui Su; Dar-Der Ji; Wei-Chen Lin; Jyh-Larng Chen; Feng-Cheng Shih; Po-Min Kao; Yi-Chou Chiu (Environmental Science and Pollution Research, 2012)

Gastrectomy and risk of pancreatic cancer: systematic review and meta-analysis of observational studies - Yuanfeng Gong; Quanbo Zhou; Yu Zhou; Qing Lin; Bing Zeng; Rufu Chen; Zhihua Li (Cancer Causes & Control, 2012)

Molecular detection and comparison of Acanthamoeba genotypes in different functions of watersheds in Taiwan - Po-Min Kao; Bing-Mu Hsu; Nai-Hsiung Chen; Kuan-Hao Huang; Chin-Chun Huang; Dar-Der Ji; Jung-Sheng Chen; Wei-Chen Lin; Shih-Wei Huang; Yi-Chou Chiu (Environmental Monitoring and Assessment, 2012)

Effects of 1,1,1-trichloroethane on enzymatic activity and bacterial community in anaerobic microcosm form sequencing batch reactors - Hui Li; Wei Zhang; Lu Li; Yong-Di Liu; Kuang-Fei Lin; Shu-Guang Lu; Bo-Zhong Mu; Xiao-Ming Du; Qiang Lu; Qian Zhang; Ting-Ting Shen; Bing-Zhi Li; et al. (Ecotoxicology, 2012)

Identification of a heat shock cognate protein 70 gene in Chinese soft-shell turtle (Pelodiscus sinensis) and its expression profiles under thermal stress - Xiao-liang Li; Yue Kang; Xiao-yan Zhang; Bing-lin Zhu; Wei-huan Fang (Journal of Zhejiang University-SCIENCE B, 2012)

Analysis of genetic diversity among Chinese Pleurotus citrinopileatus Singer cultivars using two molecular marker systems (ISSRs and SRAPs) and morphological traits - Qiu-sheng Zhang; Bing-lian Xu; Lin-de Liu; Qin-qin Yuan; Hong-xin Dong; Xian-hao Cheng; De-ling Lin (World Journal of Microbiology and Biotechnology, 2012)

Association between TaqIB polymorphism of cholesteryl ester transfer protein and coronary artery disease in the Chinese population - Qi Yu; En-qi Liu; Si-hai Zhao; Ya-feng Li; Yan-li Wang; Yu-long Chen; Ke-na Wei; Bing-qiao Huang; Jian-lin Fan; Peng-hui Yang (Journal of Zhejiang University-SCIENCE B, 2012)

Erratum to: Hyperhomocysteinemia and Related Genetic Polymorphisms Correlate with Ulcerative Colitis in Chinese Han population in Central China - Yi Jiang; Xuanping Xia; Wenxing Wang; Limiao Lin; Changlong Xu; Zhenzai Cai; Bo Zheng; Jihua Pei; Sujian Shen; Bing Xia (Cell Biochemistry and Biophysics, 2012)

G6PD Genotype and Its Associated Enzymatic Activity in a Chinese Population - Wei Ying Jiang; Bing Yi Zhou; Guo Long Yu; Han Liu; Jing Bo Zeng; Qun Di Lin; Hong Li Xi; Hua Liang (Biochemical Genetics, 2012)

Construction and characterization of a normalized cDNA library from the river snail Bellamya aeruginosa after exposure to copper - Zi-Cheng Li; Li-Hui An; Qing Fu; Ying Liu; Lei Zhang; Hao Chen; Xing-Ru Zhao; Li-Jing Wang; Bing-Hui Zheng; Lin-Bo Zhang (Ecotoxicology, 2012)

Hyperhomocysteinemia and Related Genetic Polymorphisms Correlate with Ulcerative Colitis in Southeast China - Yi Jiang; Xuanping Xia; Wenxing Wang; Limiao Lin; Changlong Xu; Zhenzai Cai; Bo Zheng; Jihua Pei; Sujian Shen; Bing Xia (Cell Biochemistry and Biophysics, 2012)

Aircraft noise exposure affects rat behavior, plasma norepinephrine levels, and cell morphology of the temporal lobe - Guo-qing Di; Bing Zhou; Zheng-guang Li; Qi-li Lin (Journal of Zhejiang University-SCIENCE B, 2011)

Hepcidin Treatment Modulates the Expression of Divalent Metal Transporter-1, Ceruloplasmin, and Ferroportin-1 in the Rat Cerebral Cortex and Hippocampus - Lin Li; Christian Holscher; Bing-Bing Chen; Zhi-Feng Zhang; Yue-Ze Liu (Biological Trace Element Research, 2011)

Characterization of mitochondrial genome of Formosan sambar (Rusa unicolor swinhoei) - Chia-Hsuan Chen; Hsiu-Lin Huang; Mu-Tzu Chang; Li-Chia Chiang; Shih-Lin Cheng; Bing-Tsan Liu; Chih-Hua Wang; Ming-Che Wu; Mu-Chiou Huang (Biologia, 2011)

Individual Management of Recurrent Intracranial Aneurysms: The Wuxi Experience - Lin Yu-chang; Santosh Kesari; Leng Bing; Ding Ya-suo; Pang Ming-zhi (Cell Biochemistry and Biophysics, 2011)

The relationship between competitive ability and yield stability in an old and a modern winter wheat cultivar - Yan Fang; Lin Liu; Bing-Cheng Xu; Feng-Min Li (Plant and Soil, 2011)

Evaluation of an improved strain of Porphyra yezoensis Ueda (Bangiales, Rhodophyta) with high-temperature tolerance - Bing-lei Zhang; Xing-hong Yan; Lin-bin Huang (Journal of Applied Phycology, 2011)

Estimation of cancer cases and deaths attributable to infection in China - Wang Xiang; Ju-Fang Shi; Ping Li; Jian-Bing Wang; Li-Na Xu; Wen-Qiang Wei; Fang-Hui Zhao; You-Lin Qiao; Paolo Boffetta (Cancer Causes & Control, 2011)

Production, purification and characterization of a thermostable laccase from a tropical white-rot fungus - Li-Qiong Guo; Shuo-Xin Lin; Xiao-Bing Zheng; Zi-Rou Huang; Jun-Fang Lin (World Journal of Microbiology and Biotechnology, 2011)

Prevention of cerebral ischemia-induced memory deficits by inhibition of phosphodiesterase-4 in rats - Ling-Xia Li; Yu-Fang Cheng; Huan-Bing Lin; Chuang Wang; Jiang-Ping Xu; Han-Ting Zhang (Metabolic Brain Disease, 2011)

RRM1 gene expression in peripheral blood is predictive of shorter survival in Chinese patients with advanced non-small-cell lung cancer treated by gemcitabine and platinum - Lin-run Wang; Guo-bing Zhang; Jian Chen; Jun Li; Ming-wei Li; Nong Xu; Yang Wang; Jian-zhong Shen Tu (Journal of Zhejiang University-SCIENCE B, 2011)

Biodegradation of malachite green by Pseudomonas sp. strain DY1 under aerobic condition: characteristics, degradation products, enzyme analysis and phytotoxicity - Lin-Na Du; Sheng Wang; Gang Li; Bing Wang; Xiao-Ming Jia; Yu-Hua Zhao; Yun-Long Chen (Ecotoxicology, 2011)

Photoluminescence of Rare Earth Phosphors Na0.5Gd0.5WO4: RE3+ and Na0.5Gd0.5(Mo0.75W0.25)O4: RE3+ (RE=Eu, Sm, Dy) - Bing Yan; Lixia Lin; Jianhua Wu; Fang Lei (Journal of Fluorescence, 2011)

Radiation characteristics of low and high clouds in different oceanic regions observed by CERES and MODIS - Bing Lin; Patrick Minnis; Tai-Fang Fan; Yongxiang Hu; Wenbo Sun (International Journal of Remote Sensing, 2010)

Recent trends and patterns in breast cancer incidence among Eastern and Southeastern Asian women - Hai-Rim Shin; Clementine Joubert; Mathieu Boniol; Clarisse Hery; Sei Hyun Ahn; Young-Joo Won; Yoshikazu Nishino; Tomotaka Sobue; Chien-Jen Chen; San-Lin You; Maria Rica Mirasol-Lumague; Stephen Chun-Key Law; et al. (Cancer Causes & Control, 2010)

Inhibition of phosphodiesterase-4 reverses memory deficits produced by Aβ25–35 or Aβ1–40 peptide in rats - Yu-Fang Cheng; Chuang Wang; Huan-Bing Lin; Yun-Feng Li; Ying Huang; Jiang-Ping Xu; Han-Ting Zhang (Psychopharmacology, 2010)

Novel microRNAs in silkworm (Bombyx mori) - Yimei Cai; Xiaomin Yu; Qing Zhou; Caixia Yu; Haiyan Hu; Jiucheng Liu; Hongbin Lin; Jin Yang; Bing Zhang; Peng Cui; Songnian Hu; Jun Yu (Functional & Integrative Genomics, 2010)

Estimation of cancer incidence and mortality attributable to smoking in China - Jian-Bing Wang; Yong Jiang; Wen-Qiang Wei; Gong-Huan Yang; You-Lin Qiao; Paolo Boffetta (Cancer Causes & Control, 2010)

Establishment and maintenance of three Chinese human embryonic stem cell lines - Di Zhou; Ge Lin; Chang-Qing Xie; Bo Xiong; Xiao-Ying Zhou; Xiao-Bing Qian; Yi Liao; Guang-Xiu Lu (In Vitro Cellular & Developmental Biology - Animal, 2010)

Platinum-group minerals and tellurides from the PGE-bearing Xinjie layered intrusion in the Emeishan Large Igneous Province, SW China - Wei-Guang Zhu; Hong Zhong; Rui-Zhong Hu; Bing-Guang Liu; De-Feng He; Xie-Yan Song; Hai-Lin Deng (Mineralogy and Petrology, 2010)

Salicylic Acid-Altering Arabidopsis Mutants Response to NO2 Exposure - Qiang Xu; Bing Zhou; Chunyan Ma; Xin Xu; Jia Xu; Yangao Jiang; Chang Liu; Guangzhe Li; Stephen J. Herbert; Lin Hao (Bulletin of Environmental Contamination and Toxicology, 2010)

Synergistic Action of Exogenous Salicylic Acid and Arbuscular Mycorrhizal Fungus Colonization in Avena nuda Seedlings in Response to NO2 Exposure - Runguo Li; Yangao Jiang; Jia Xu; Bing Zhou; Chunyan Ma; Chang Liu; Cui Yang; Yuhuan Xiao; Qiang Xu; Lin Hao (Bulletin of Environmental Contamination and Toxicology, 2010)

Characterization of Pseudomonas aeruginosa associated with diseased postlarval abalone in Shenzhen, China - Junpeng Cai; Shuanyu Lin; Bing Wu (Aquaculture International, 2009)

Prediction of interaction between small molecule and enzyme using AdaBoost - Bing Niu; Yuhuan Jin; Lin Lu; Kaiyan Fen; Lei Gu; Zhisong He; Wencong Lu; Yixue Li; Yudong Cai (Molecular Diversity, 2009)

Memory deficits and neurochemical changes induced by C-reactive protein in rats: implication in Alzheimer’s disease - Huan-Bing Lin; Xue-Mei Yang; Tie-Jun Li; Yu-Fang Cheng; Han-Ting Zhang; Jiang-Ping Xu (Psychopharmacology, 2009)

Transcriptional analysis of the hsp70 gene in a haloarchaeon Natrinema sp. J7 under heat and cold stress - Hao Zhang; Peng Cui; Lu Lin; Ping Shen; Bing Tang; Yu-Ping Huang (Extremophiles, 2009)

Occurrence of Fumonisin B1 in Corn from the Main Corn-Producing Areas of China - Hui-Zhi Gong; Rong Ji; Yan-Xi Li; Hong-Yu Zhang; Bing Li; Yue Zhao; Lin Sun; Fei Yu; Jun Yang (Mycopathologia, 2009)

Estimation of genetic variances in flood tolerance of poplar and selection of resistant F1 generations - Ke-Bing Du; Bao-Xian Shen; Lin Xu; Bing-Kun Tu (Agroforestry Systems, 2008)

Improved neovascularization and wound repair by targeting human basic fibroblast growth factor (bFGF) to fibrin - Wenxue Zhao; Qianqian Han; Hang Lin; Yuan Gao; Wenjie Sun; Yannan Zhao; Bin Wang; Bing Chen; Zhifeng Xiao; Jianwu Dai (Journal of Molecular Medicine, 2008)

Prediction of compounds’ biological function (metabolic pathways) based on functional group composition - Yu-Dong Cai; Ziliang Qian; Lin Lu; Kai-Yan Feng; Xin Meng; Bing Niu; Guo-Dong Zhao; Wen-Cong Lu (Molecular Diversity, 2008)

High-Level Secretion of a Chimeric Thermostable Lichenase from Bacillus subtilis by Screening of Site-Mutated Signal Peptides with Structural Alterations - Ling-lin Fu; Zi-rong Xu; Jiang-bing Shuai; Chun-xia Hu; Wei Dai; Wei-fen Li (Current Microbiology, 2008)

Cadmium tolerance and accumulation by two species of Iris - Yu-Lin Han; Hai-Yan Yuan; Su-Zhen Huang; Zhi Guo; Bing Xia; Jiguang Gu (Ecotoxicology, 2007)

Cloning, sequencing and expression analysis of the NAR promoter activated during hyphal stage of Magnaporthe grisea - Jian-ping Lu; Zhi-bing Duan; Tong-bao Liu; Fu-cheng Lin (Journal of Zhejiang University-SCIENCE B, 2007)

Rapid Evolution, Genetic Variations, and Functional Association of the Human Spermatogenesis-Related Gene NYD-SP12 - Qü Zhang; Feng Zhang; Xiao-hua Chen; Yin-qiu Wang; Wei-qi Wang; Alice A. Lin; Luca L. Cavalli-Sforza; Li Jin; Ran Huo; Jia-hao Sha; Zheng Li; Bing Su (Journal of Molecular Evolution, 2007)

A New Method for Determination of Chlorophylls in Freshwater Algae - Ting-Lin Huang; Hai-Bing Cong (Environmental Monitoring and Assessment, 2007)

Folic acid rivals ethylenetetrahydrofolate reductase (MTHFR) gene-silencing effect on MEPM cell proliferation and apoptosis - Wen-lin Xiao; Min Wu; Bing Shi (Molecular and Cellular Biochemistry, 2007)

Ex vivo expansion and pluripotential differentiation of cryopreserved human bone marrow mesenchymal stem cells - Ying Xiang; Qiang Zheng; Bing-bing Jia; Guo-ping Huang; Yu-lin Xu; Jin-fu Wang; Zhi-jun Pan (Journal of Zhejiang University-SCIENCE B, 2007)

Folic acid rivals methylenetetrahydrofolate reductase (MTHFR) gene-silencing effect on MEPM cell proliferation and apoptosis - Wen-lin Xiao; Min Wu; Bing Shi (Molecular and Cellular Biochemistry, 2006)

IGFBP7 plays a potential tumor suppressor role against colorectal carcinogenesis with its expression associated with DNA hypomethylation of exon 1 - Wen-jing Ruan; Jie Lin; En-ping Xu; Fang-ying Xu; Yu Ma; Hong Deng; Qiong Huang; Bing-jian Lv; Hu Hu; Jing Cui; Mei-juan Di; Jian-kang Dong; et al. (Journal of Zhejiang University-SCIENCE B, 2006)

Basal or bolus dose, which is the key factor in CSII? - Nai-long Yang; Bing Xue; Peng Lin (Journal of Zhejiang University-SCIENCE B, 2006)

Molecular Evolution of CXCR1, a G Protein-Coupled Receptor Involved in Signal Transduction of Neutrophils - Ying Liu; Su Yang; Alice A. Lin; Luca L. Cavalli-Sforza; Bing Su (Journal of Molecular Evolution, 2005)

Identification of a novel rice bZIP-type transcription factor gene,OsbZIP1, involved in response to infection ofMagnaporthe grisea - Xiang-Bing Meng; Wen-Sheng Zhao; Rui-Ming Lin; Min Wang; You-Liang Peng (Plant Molecular Biology Reporter, 2005)

Comparative study on residents’ perception of tourism impact at tourist places - Qin Su; You-hui Cao; Bing-yao Lin (Chinese Geographical Science, 2005)

Relationship between CYP3A activity and breast cancer susceptibility in Chinese Han women - Ping Huang; Bing Zhu; Lian-Sheng Wang; Dong-Sheng Ouyang; Song-Lin Huang; Xiao-Ping Chen; Hong-Hao Zhou (European Journal of Clinical Pharmacology, 2003)

Chloroplast Transformation in Oilseed Rape - Bing-Kai Hou; Yi-Hua Zhou; Li-Hong Wan; Zhong-Lin Zhang; Gui-Fang Shen; Zheng-Hua Chen; Zan-Min Hu (Transgenic Research, 2003)

Molecular analysis of survival motor neuron (SMN) and neuronal apoptosis inhibitory protein (NAIP) genes of spinal muscular atrophy patients and their parents - J.-G. Chang; Yuh-Jyh Jong; Shuan-Pei Lin; Bing-Wen Soong; Chang-Hai Tsai; T.-Y. Yang; Chih-Peng Chang; Wen-Shin Wang (Human Genetics, 1997)

Multiple genotypes of mitochondrial DNA within a horse population from a small region in Yunnan province of China - Wen Wang; Ai-hua Liu; Shi-ying Lin; Hong Lan; Bing Su; De-wen Xie; Li-ming Shi (Biochemical Genetics, 1994)

Multiple genotypes of mitochondrial DNA within a horse population from a small region in Yunnan province of China - Wen Wang; Ai-hua Liu; Shi-ying Lin; Hong Lan; Bing Su; De-wen Xie; Li-ming Shi (Biochemical Genetics, 1994)